Conversion of agro-industrial and fishery wastes into biosurfactants by Pseudomonas aeruginosa MELI 1: Kinetics, functional properties and process feasibility - Djaber Tazdaït; Rym Salah Tazdaït; Imene Keddou; Djura Delhoum; Samia Mouffok; Fatma Kabouche; Nadjib Drouiche; Hakim Lounici (Biomass and Bioenergy, 2027)

Prevalence of methicillin-resistant coagulase-negative staphylococci and their antibiotic resistance profile in Zagazig University intensive care units - Hend M. Elarini; Sara M. Gaafer; Fatma A. Ibrahim; Nessma H. Gandor; Walid M A. Hamad; Samia Hussein; Aya M. Bedawy (Molecular Biology Reports, 2026)

Mutation mapping and functional characterization of a missense mutation p.Arg228Cys in ALDH3A2 gene causing Sjögran-Larson syndrome - Muhammad Zeeshan Ali; Samia Sattar; Abdulfatah M. Alayoubi; Shakil Abbas; Mohammed Turki Hussain Alharthi; Alwaleed Fahad H. Altemani; Muhammad Latif; Muzammil Ahmad Khan; Christian Windpassinger (Molecular Biology Reports, 2026)

Early modulatory effects of Porphyromonas gingivalis and Lactobacillus salivarius on oncogenic processes in dysplastic oral keratinocytes - Umme Samia; Tamara Vlajic Tovilovic; Ilinka Pecinar; Milena Radunovic; Sanja Petrovic; Milos Lazarevic; Dijana Mitic; Milica Jaksic Karisik; Nadja Nikolic; Jelena Carkic; Maria Cristina Curia; Jelena Milasin (Molecular Biology Reports, 2026)

In vitro assessment of antioxidant, hypocholesterolemic and alpha-amylase inhibition of Lactiplantibacillus plantarum strains from a fermented Algerian milk - Ghania Zidi; Samia Hamma-faradji; Nacim Barache; Amel Ait Meddour; Lylia Ouarabi; Walid Zeghbib; Farés Boudjouan; Giuseppe Spano; Djamel Drider (Brazilian Journal of Microbiology, 2026)

Characterization and antioxidant activities of exopolysaccharides produced by Lactiplantibacillus plantarum strains isolated from Algerian fruits - Lylia Ouarabi; Samia Hamma-Faradji; Liza Ouarabi; Nacim Barache; Imene Trabelsi; Riadh Ben Salah; Djamel Drider (Brazilian Journal of Microbiology, 2026)

Mapping methods to assess taste and smell alterations in children with cancer: a scoping review - Samia Saraya-Jean; Mirjam Van den Brink; Séverine Bouttefroy; Florence Carrouel; Anestis Dougkas (Appetite, 2026)

The multifaceted challenge of viral nervous necrosis in fish farming: a review of current knowledge and control - Eman Zahran; Samia Elbahnaswy; Reham Karam; Noha I. ElBanna; Mahmoud G. El Sebaei (Veterinary Research Communications, 2026)

Physicochemical quality, oxidative stability, and bioactive profile of argan oil from the Northwestern Algerian coast - Samia Chabane Chaouch; Fatima Zohra Chenni; Amira Ghislaine Dra; Badra Bensabeur; Samira Meziani¹; Noreddine Menadi; Hedi Mighri (Euro-Mediterranean Journal for Environmental Integration, 2026)

Unveiling the Viral Landscape in Gastric Cancer - Diego Pereira; Fabiano Cordeiro Moreira; Daniel de Souza Avelar; Sérgio Augusto Antunes Ramos; Valéria Cristiane Santos da Silva; Jéssica Manoelli Costa da Silva; Ronald Matheus da Silva Mourão; Rubem Ferreira da Silva; Kauê Sant’Ana Pereira Guimarães; Juliana Barreto Albuquerque Pinto; Marcos da Conceição; Williams Fernandes Barra; et al. (Current Microbiology, 2026)
The present study aimed to comprehensively characterize the cancer-associated virome in patients with gastric cancer. A total of 452 samples were analyzed, including 226 tumor tissues and 202 peritumoral tissues from patients undergoing surgical resection, alongside 24 normal gastric mucosa samples obtained via endoscopy from individuals without cancer. RNA was extracted, libraries were prepared, and paired-end sequencing was performed on the NextSeq 500 platform (Illumina, US). High-quality reads were processed with Kraken2, using the standard database supplemented with the Reference Viral Database, to identify viral taxa. Taxonomic profiles, differential viral abundance, and alpha and beta diversity metrics were computed in RStudio, with statistical analyses performed to compare viral composition and diversity among tissue groups using Kruskal-Wallis, Wilcoxon, PERMANOVA, and PERMDISP tests ( p

Contrasting effects of treated wastewater irrigation and Trichoderma inoculation on tomato soil microbiomes - Raffaella Sabatino; Andrea Di Cesare; Monica Brienza; Giulia Borgomaneiro; Roberto Rosamilia; Samia Khadhar; Farah Khezami; Paolo Fanti; Vincenzo Trotta (European Journal of Soil Biology, 2026)

Does the energy transition law mark a turning point in France's path toward Greener development? - Salma Mefteh-Wali; Samia Nasreen (Energy Policy, 2026)

Climatic suitability and geospatial assessment of Black Soldier Fly Larvae (BSFL) for sustainable waste management - Muhammad Salam; Sami Ullah; Fakhri Alam; Camila Rodríguez-Ortega; Samia Elouali; Viola Vambol; Shafi'u Adamu; Viviana Bolletta; Faisal Hayat; Zhiyong Han (Environmental Development, 2026)

A thorough synthesis and structural investigation of a new generation of halide inclusion complexes of sodium β-cyclodextrin-based metal organic frameworks - Amine Ez-zoubi; Samia Benmansour; Carlos J. Gómez-García; Abdellah Farah; Safaa Elidrissi Moubtassim; Salah-Eddine Stiriba (Carbohydrate Polymers, 2026)

Occurrence and Risk Assessment of Pharmaceuticals and Heavy Metals in a Mediterranean Coastal Drain (Khniss, Tunisia) - Nouha Khiari; Samia Khadhar; Farah khezami; Nadia Khalil; Abdelkrim Charef (Water, Air, & Soil Pollution, 2026)

A phenology-weighted composite agricultural drought index for rainfed croplands in Morocco - Cheik Parfait Dieudonné Nacro; Abdelghani Chehbouni; Gohar Ghazaryan; El Houssaine Bouras; Riad Balaghi; Youssef Bammou; Samia Hasmi; Abdelhafid El Alaoui El Fels; Salah Er-Raki; Abdelhakim Amazirh (Remote Sensing Applications: Society and Environment, 2026)

Corrigendum to: “Effect of ginger extract and/or fenofibrate on the associated infertility of experimentally induced obese Wistar Albino male rats” [Reprod Biol 26 (2): 101208] - Mohamed H. Elsayed; Samia M. Abd El-Rheem; Essam A. Almadaly; Azza M. Elkattawy; Nasr EL. Nasr; Doaa A. Dorghamm; Walied S. Abdo; Mona Assas; Tarek K. Abouzed; Wael B. El-Domany (Reproductive Biology, 2026)

Synergistic impacts of dietary supplementation with Eruca sativa, Nigella sativa, and peppermint oils blend on performance, blood biochemistry, gut health, and economic efficiency in two commercial broiler strains - Seham El-Kassas; Ibrahim Elkhaiat; Karima El-Naggar; Samia Fawzy; Alaa Abdelatty; Ayman E. Taha; Mahmoud Alagawany; Abeer A. Kirrella (Livestock Science, 2026)

Morphological properties and musculature of the eyelids of the Egyptian agama, Trapelus mutabilis - Fatma Abdel-Regal Mahmoud; Amany Salah Saad Mahmoud; Samia Abdalla Gaber; Fatma A. Al-Nefeiy; Ali Gamal Gadel-Rab (Zoomorphology, 2026)

Microalgae-based aquafeeds for penaeid shrimp: progress toward improved growth, immune modulation, and sustainable production - Samia Elbahnaswy; Eman Zahran; Mai A. M. El-Son; Amany M. Shosha; El-sayed H. Eissa; Mohamed AbdElrahman; Mohamed E. Abd El-Hack; Hanan H. Abdelhafeez; Mahmoud G. El Sebaei (Veterinary Research Communications, 2026)

Splicing regulation by RS2Z36 controls ovary patterning and fruit growth in tomato - Stavros Vraggalas; Remus R. E. Rosenkranz; Mario Keller; Yolanda Pérez-Pérez; Samia Bachiri; Kerstin J. Zehl; Jessica Bold; Stefan Simm; Arindam Ghatak; Wolfram Weckwerth; Leila Afjehi-Sadat; Palak Chaturvedi; et al. (Plant Molecular Biology, 2026)
Fruit growth is mediated by cell division and expansion. In tomato, the model for fleshy fruit development, both processes are tightly linked to changes in gene expression, including transcriptional regulation and RNA processing. While several transcription factors are implicated in fruit developmental programs, the role of splicing regulators remains largely unexplored. Expression profiling of splicing-related genes revealed expression patterns. The serine/arginine-rich splicing factor RS2Z36 is expressed in ovaries and during early fruit development. Loss-of-function mutations in RS2Z36 result in ovaries with altered patterning and in smaller, ellipsoid fruits. rs2z36 mutants display elongated pericarp cells along the longitudinal axis of pre-anthesis ovaries, indicating that RS2Z36-dependent expansion patterns are established before anthesis. Based on RNA-seq analysis we identified 230 genes with altered splicing profile in ovaries of rs2z36.1 compared to WT and 235 differentially expressed genes. Proteome analysis further revealed several differentially abundant isoforms, including several cell wall proteins and modifiers that might be involved in ovary patterning and fruit growth. In addition, rs2z36-1 pericarps show increased deposition of LM6-recognized arabinan and AGP epitopes. Together, these findings identify RS2Z36 as a regulator of ovary and fruit development and highlight a previously underappreciated role for splicing control in shaping early fruit morphology.

Initial Assessment of a New Olive Mill Waste-Derived Biostimulant for Mitigating Water Stress in Pomegranate Trees - Darine Tlili; Samia Abboud; Sahar Ben Abdelwaheb; Azhar Ouni; Soumaya Dbara (Applied Fruit Science, 2026)

Toxicological assessment of Myrtus communis essential oil against major cereal aphids - Ratiba Zaid; Hichem Benddine; Radouane Zaid; Samia Daoudi-hacini; Souad Kheloufi (Euro-Mediterranean Journal for Environmental Integration, 2026)

Entomological Surveillance and Arbovirus Screening in Mosquitoes from Central Morocco: First Detection of West Nile Virus in Culex pipiens from the Marrakech-Safi Region - Abdelkrim Outammassine; Mattia Calzolari; Mohamed Daoudi; Paolo Bonilauri; Annalisa Grisendi; Samia Boussaa; Michele Dottori; Said Zouhair; Souad Loqman (Acta Parasitologica, 2026)

Correction: Sustainable Integrated Management of Olive Verticillium Wilt (Verticillium dahliae) Using a Microbial Consortium of Pseudomonas yamanarum - Trichoderma longibrachiatum, and Compost Mill Waste - Lobna Hajji-Hedfi; Omaima Bargougui; Laith Khalil Tawfeeq Al-Ani; Samia Oueslati; Dalia Sukmawati; Takwa Wannassi; Mohamed Ali Triki (Journal of Soil Science and Plant Nutrition, 2026)

Scabiosa atropurpurea mitigates oxidative stress and maintains the viability of cryopreserved ram sperm: evidence from oral and extender supplementation - Hela Derbali; Wijden Niama; Samia Ben Saïd; Sihem Amiri; Christelle Ramé; Mustapha Lahbib; Ismail Zaidi; Lamia Doghbri; Mohamed Hammadi; Pascal Froment; Mokhtar Mahouachi; Joelle Dupont (Livestock Science, 2026)

Withdrawal notice to “Detection of Enterocytozoon hepatopenaei in pond-cultured Litopenaeus vannamei shrimp: Unveiling the epidemiological significance of some invasive macrofauna, synergistic diagnostic approach and treatment trial” - Alaa Eldin Eissa; Rasha S.A. Abd El-Lateif; Eman M. Younis; Samia Alzentani; Eman H. Rashwan; Reda M. Korany; Reham H. Ragab; Suzan S. Abulelkasem; Mahmoud A. Elnakeeb; Emad Afiffi; Heba A. Abdel Hady; Eman M. Abouelhassan (Journal of Invertebrate Pathology, 2026)

WITHDRAWN: Detection of Enterocytozoon hepatopenaei in pond-cultured Litopenaeus vannamei shrimp: Unveiling the epidemiological significance of some invasive macrofauna, synergistic diagnostic approach and treatment trial - Alaa Eldin Eissa; Rasha S.A. Abd El-Lateif; Eman M. Younis; Samia Alzentani; Eman H. Rashwan; Reda M. Korany; Reham H. Ragab; Suzan S. Abulelkasem; Mahmoud A. Elnakeeb; Emad Afiffi; Heba A. Abdel Hady; Eman M. Abouelhassan (Journal of Invertebrate Pathology, 2026)

Nanoparticles in wheat (Triticum aestivum L) cultivation: a promising solution to alleviate heavy metal toxicity - Eimaan Aamer; Muhammad Saeed; Samia Muhammad Arif; Ghazala Mustafa; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2026)

Evaluating the effectiveness of the valley floor width parameter and comparing traditional and modern weighting methods in MCDM for flood hazard mapping - Reza Esmaili; Jalal Samia; Taher Safarrad (Natural Hazards, 2026)

Dual Application of Salicylic Acid Improves Salt Tolerance in Okra Seedlings Through Enhanced Antioxidant Defence and Physiological Adaptation - Mousumi Jahan Sumi; Shahin Imran; Samia Binta Zaman; Newton Chandra Paul; Fakhar Uddin Talukder; Nigar Afsana; Atanu Howlader; Noushin Jahan; Md. Asif Mahamud; Israt Jahan Harine; Marian Brestic (Journal of Plant Growth Regulation, 2026)

Potential of competitive and efficient Mesorhizobium strains to improve chickpea growth, yield, and soil health - Venkatesh Kokila; Samia Saleem; Shiv Charan Kumar; Pushpendra Tiwari; Sindhunath Chakraborty; Murugan Kumar; Hillol Chakdar; Alok Kumar Srivastava; Anil Kumar Saxena (Symbiosis, 2026)

Lignin Nanoparticles as a Sustainable Approach to Enhance Salt Tolerance in Pomegranate - Sahar Ben Abdelwaheb; Azhar Ouni; Josefina Bota; Samia Abboud; Jaume Puigserver; Darine Tlili; Mourad Jellali; Noomene Sleimi; Soumaya Dbara (Journal of Soil Science and Plant Nutrition, 2026)

Proton magnetic resonance sounding in El Atteuf (Ghardaïa, Algerian Sahara): a pilot hydrogeophysical study for characterising shallow phreatic aquifers - Mawloud Hadjadj; Samia Hadj-Said; Aziez Zeddouri; Rachid Ahmed Rahmani; Omar Hammou Ali (Acta Geophysica, 2026)

Lactic acid bacteria and their bacteriocins: promising food safety tools for controlling the foodborne pathogen Listeria monocytogenes - Nassima Mohellebi; Yanath Belguesmia; Samia Hamma-Faradji; Kamel Bendjeddou; Luis Augusto Nero; Giuseppe Spano; Alexandre Leclercq; Paul D. Cotter; Djamel Drider (World Journal of Microbiology and Biotechnology, 2026)

Foliar Applications of Gibberellic Acid Alleviates Chromium Toxicity in Pisum sativum L - Tehmeena Zafar; Asia Khatoon; Samina Yousaf; Samia Akram; Sumreen Anjum (Journal of Plant Growth Regulation, 2026)

Effect of ginger extract and/or fenofibrate on the associated infertility of experimentally induced obese Wistar Albino male rats - Mohamed H. Elsayed; Samia M. Abd El-Rheem; Essam A. Almadaly; Azza M. Elkattawy; Nasr EL. Nasr; Doaa A. Dorghamm; Walied S. Abdo; Mona Assas; Tarek K. Abouzed; Wael B. El-Domany (Reproductive Biology, 2026)

Pesticide fate and transport in the atmosphere and implications for risk assessment - Carole Bedos; Esther Fuentes-Ferragud; Boulos Samia; Meriem Djouhri; Ludovic Mayer; Raphaëlle Teysseire; Sergio Cirelli; Pere Colomer-Vidal; Jean-Paul Douzals; Benjamin Loubet; Juan Muñoz-Arnanz; Fabrizio Botta; et al. (Journal of Hazardous Materials, 2026)

Carbon-aware production scheduling for industrial decarbonization: An artificial intelligence framework integrating environmental and public health co-benefits - Samia Elattar (Journal of Cleaner Production, 2026)

Preliminary microbiome characterization of shrimp gut and pond water in Egyptian aquaculture farms: Implications for pathogen dynamics and management practices - Eman Zahran; Samia Elbahnaswy; Timothy J. Bruce; Yassmin E. Hegab; Dusan Palic (Veterinary Research Communications, 2026)
Shrimp aquaculture is a rapidly expanding food sector; however, its sustainability is challenged by disease outbreaks often linked to imbalances in the microbiome. Here, we characterized the microbial communities in the intestines of shrimp and pond water from three Egyptian farms (A, B, and C) using Oxford Nanopore long-read sequencing. Descriptive comparisons of relative abundance and diversity trends revealed that pond water harbored significantly higher alpha diversity than shrimp guts. In contrast, beta diversity confirmed a strong separation between host-associated and environmental microbiomes. For the observed phyla, taxonomic profiling revealed that shrimp guts were dominated by Proteobacteria, Actinomycota, and Bacillota, whereas pond water contained additional constituents, including Cyanobacteria and Bacteroidota. Pathogen-associated genera, particularly Vibrio spp. and Pseudomonas spp., were more abundant in water samples, with farm-specific variations linked to management practices such as salinity and feed protein content. Venn analysis highlighted that pond water harbored the largest pool of unique taxa, reinforcing its role as a putative reservoir for pathogens. These findings provide the first integrative microbiome baseline for Egyptian shrimp farms, underscoring the need for microbiome-informed management to mitigate the risk of pathogens.

Long-term supplementation of exogenous bile acids enhanced growth efficacy, hematology, non-specific immunity, and intestinal histomorphology, with significant liver dysfunction in Nile tilapia fingerlings - Elsayed A.A. Eldessouki; Gehad E. Elshopakey; Shaymaa Rezk; Mona Elsayed; Ahmed E.A. Mostafa; Samia Elbahnaswy (Veterinary Research Communications, 2026)
A 16-week feeding trial was conducted to examine the effects of dietary exogenous bile acids (BAs) on growth performance, digestive enzyme activities, biochemical indices, antioxidant capacity, non-specific immune response, gene expression of proinflammatory cytokines, and liver and intestinal morphology in Nile tilapia (initial weight, 5.10 ± 0.22 g) reared in earthen ponds over an extended period. Two isonitrogenous (31.65% protein) and isolipidic (4.71%) experimental diets were formulated by adding a control diet (BA0) and 0.25 g bile acid per kg diet (BA 0.25 ), respectively. The diets were randomly assigned to 6 hapas, each stocked with 20 fish and fed for 16 weeks. Supplementing with BA0.25 significantly enhanced growth metrics and intestinal digestive enzyme activities compared to BA0. Hematological analysis showed increased levels of white blood cells (WBC), lymphocytes, and neutrophils in the BA 0.25 group compared to the control. Additionally, respiratory burst activity, phagocytic activity, and serum lysozyme activity were notably higher in fish fed BAs at 0.25 g kg − 1 . Antioxidant parameters (SOD, CAT, GSH) were elevated, and the expression of the proinflammatory cytokine IL1β was downregulated in intestinal tissue from the BAs-supplemented group. Significant improvements in intestinal histomorphometry were observed in the BAs-supplemented group. BAs supplementation altered intestinal microbial composition, increasing total and Pseudomonas counts while reducing coliform levels. Interestingly, glucose, triglycerides, cholesterol, serum hepatic markers (ALT, AST, and ALP), hepatic oxidative MDA levels, and proinflammatory IL1β mRNA expression increased markedly in the supplemented-BAs group, while activity of antioxidant enzymes (SOD, CAT, GSH) and HSP70 mRNA expression were notably diminished. Moreover, significant alterations were shown in the hepatic tissue of the BAs-supplemented group. Consequently, dietary supplementation with bile acids for a prolonged period improves growth, intestinal health, and immunity; however, it harms the liver health of Nile tilapia.

Upcycling Olive Mill Solid Waste into Lignin Nanoparticles for an Ecofriendly Soil Fertilization of Pomegranate - Azhar Ouni; Sahar ben Abdelwaheb; Samia Abboud; Rania Aydi Benabdallah; Mourad Jellali; Darine Tlili; Messaoud Mars; Soumaya Dbara (Journal of Soil Science and Plant Nutrition, 2026)

Comparative Phytochemical and Antioxidant Analysis of Argania spinosa Oil and Leaf Extracts from the Algerian Coastal Region - Samia Chabane Chaouch; Fatima Zohra Chenni; Amira Ghislaine Dra; Badra Bensabeur; Farouk Boudou; Samira Meziani (Journal of Pharmaceutical Innovation, 2026)

Optimization of in vitro regeneration of Opuntia ficus-indica and acclimatization under humid subtropical conditions - Abul Kalam Azad; Omar Kayess; Samia Jahan Purnota; Ashraful Haque; Haider Iqbal Khan; Sazzad Hosain (Plant Biosystems, 2026)

Unlocking the antioxidant potential of removed grapevine leaves: a sustainable approach to viticultural by-products - Hassène Zemni; Samia Daldoul; Faouzia Hanzouli; Hatem Boubakri; Ramla Khiari; Asma Ben Salem (Organic Agriculture, 2026)

Appropriate selection of objective functions with constraints for successive multicycle optimization of the HPR1000 reactor core using deep learning enhanced multi-objective genetic algorithm - Muhammad Kamran Butt; Samia Nasir; Muhammad Ahmad; Muhammad Talha Bin Humayun; Ahmer Riaz; Chenghui Wan; Liangzhi Cao (Annals of Nuclear Energy, 2026)

Agronomic and Edaphoclimatic Drivers of Pomegranate Fruit Quality: A Survey-Based Assessment - Azhar Ouni; Samia Abboud; Sahar ben Abdelwaheb; Soumaya Dbara; Messaoud Mars (Applied Fruit Science, 2026)

Health literacy and prenatal screening acceptability for hemoglobinopathies in Tunisia: a pilot mediation study - Foued Maaoui; Nadine Ben Saad; Eya Zarrouk; Sonia Mahjoub; Samia Menif; Imen Moumni (Journal of Community Genetics, 2026)

Aqueous extract of Scabiosa atropurpurea counteracts oxidative stress and enhances spermatogenesis in rams under natural hot summer conditions - Wijden Niama; Hela Derbali; Christelle Rame; Didier Lomet; Maha Tissaoui; Pascal Froment; Mokhtar Mahouachi; Samia Ben Said; Joëlle Dupont (Livestock Science, 2026)

Early-life raw goat milk intake attenuates acetic acid-induced colitis in mice - Kahina Taleb; Katia Louiza Asmani; Nacira Daoudi Zerrouki; Ouardia Chaouchi; Thilali Thanina Amroun; Maya Alouane; Mona Kettane; Tinhinane Rekeb; Meriem Dahbia Chabane; Nacera Haroun; Samia Bedouhene; Karim Houali (International Dairy Journal, 2026)

Biological slow filtration reactor (BSFR) treatment leads to more fouling of reverse osmosis (RO) membrane - Hankun Yang; Yun Xiao; Xingshe Zhu; Samia Saleem; Wenzheng Yu (Chemical Engineering Journal, 2026)

Sustainable Integrated Management of Olive Verticillium Wilt (Verticillium dahliae) Using a Microbial Consortium of Pseudomonas yamanarum - Trichoderma longibrachiatum, and Compost Mill Waste - Lobna Hajji-Hedfi; Omaima Bargougui; Laith Khalil Tawfeeq Al-Ani; Samia Oueslati; Dalia Sukmawati; Takwa Wannassi; Mohamed Ali Triki (Journal of Soil Science and Plant Nutrition, 2026)

Retraction Note: Alleviation of nicotine-induced reproductive disorder, clastogenicity, and histopathological alterations by fenugreek saponin bulk and nanoparticles in male rats - Karima A. Hamed; Samia A. El-Fiky; Azza M. Gawish; Wagdy K. B. Khalil; Hanan R. H. Mohamed (Environmental Science and Pollution Research, 2026)

In silico investigation of 4-(Trifluoromethyl)benzohydrazide derivatives as potential anti-Alzheimer’s agents by targeting acetylcholinesterase and butyrylcholinesterase - Rania Kherachi; Ismail Daoud; Nadjib Melkem; Ahmed Chelihi; Mohammed Baqur Sahib Al-Shuhaib; Samia Hamouda; Samah Baleegh Meawad; Amr Ahmed El-Arabey; Mohnad Abdalla (In Silico Pharmacology, 2026)

From wastewater pollution to biocontrol: Multidrug-resistant Enterobacteriaceae, heavy metals, and phage cocktail activity in freshwater streams - Chaima Tabet; Abdelhalim Khenchouche; Samia Mezaache-Aichour; Amine Belbahi; Bilal Saoudi; Sarah Saci; Lamia Trabelsi; Karim Houali; Djihane Bouzid (Journal of Water Process Engineering, 2026)

Preparation and performance evaluation of granulated PVDF-lithium ion-sieve: An efficient direct lithium extraction (DLE) system for industrial applications - Samia Alam; David J. Shoemaker; Xiaobo Lei; Umama Rashid Lamiya; William E. Holmes; Mehdi Mokhtari; Mark E. Zappi; Daniel Dianchen Gang (Journal of Environmental Chemical Engineering, 2026)

Quantitative determination of olive oil adulteration with cheap oils using ATR-FTIR spectroscopy - Mahmoud Alkhatib; Iman Alassa; Samia Alkhatib; Mohannad Qurie; Amer Marei; Ahmad Qutob; Areen Nassar; Mutaz Qutob (Food Chemistry, 2026)

Effect of Hydrogeological System on the Mobility and Retention on the Fate of Emerging Contaminants in the Grombalia Aquifer, Tunisia - Farah Khezami; Samia Khadhar; Rihab Guellala; Anis Chekirbane; Nouha Khiari; Olga Gómez-Navarro; Maria Vittoria Barbieri; Sandra Pérez; Serge Chiron (Water, Air, & Soil Pollution, 2026)

Modeling backward bifurcation cholera diseases with time delays: insights into treatment impact - Samia Bushnaq; Anwar Zeb; Ayesha Bashir; Hijaz Ahmad; Shumaila Irum; Taha Radwan (Modeling Earth Systems and Environment, 2026)

In Vitro Characterization of Lactiplantibacillus Plantarum Strains: Probiotic Potential, Riboflavin Production, and Functional Properties - Rania Rahmani; Amel Ait Meddour; Mohammed Benhoula; Samia Hamma-Faradji; Kahina Belbachir; Sylia Terki; Marco Calvigioni; Virginia Rossi; Diletta Mazzantini; Emilia Ghelardi; Mohamed Sifour; Houria Ouled-Haddar (Current Microbiology, 2026)

Hybrid reinforcement learning based super-twisting sliding mode controller design for micro/nano satellite attitude stabilization - Hasnain Ghazanfar; Rooh ul Amin; Samia Ben Amarat (Advances in Space Research, 2026)

Assessing the efficacy of a mycotoxin detoxifier in counteracting Aflatoxicosis in Pacific white shrimp Litopenaeus vannamei - Eman Zahran; Gehad E. Elshopakey; Samia Elbahnaswy; Shaaban M. Abdel-Fattah; Ahmed I.A. Mansour; Shaymaa Rezk; Walaa El-Houseiny; Noha I. ElBanna; Dina Ibrahim; Óscar Castro; Eva León; Rokia Temmar; et al. (Aquaculture, 2026)

Enhancing root resilience through sustainable agriculture to mitigate heavy metal pollution and abiotic stresses in a changing climate - Md Shihab Uddine Khan; Nahid Afridi; Sadia Afroz Ritu; Shamsul Islam Shipar; Samia Binta Zaman; Noshin Tabassum Hasan; Shihab Uddin; Mehedi Hasan; Mehdi Rahimi; Mousumi Jahan Sumi; Shahin Imran (Rhizosphere, 2026)

The post-thaw quality, antioxidant activity, and in vivo fertility of Zaraibi buck semen frozen-stored in the presence of different concentrations of either quercetin or L-arginine - Essam A. Almadaly; Mohamed A. Elbendary; Samia M. Abd El-Rheem; Ahmed M. Shehabeldin; Wael B. El-Domany; Adel A. Ramoun (Cryobiology, 2026)

Myricetin ameliorates letrozole-induced PCOS in female rats—a mechanistic approach through in silico, in vitro, and in vivo study via P13/AKT and NF-κB pathway crosstalk - Samia Gul Niazi; Uzma Saleem; Liaqat Hussain; Ammara Saleem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sustainable garden pea cultivation: a comprehensive evaluation of organic, inorganic, and bio-fertilizer impacts on productivity, quality and nutrient dynamics - Abdul Quddus; Razu Ahmed; Shihab Uddine Khan; Samia Jahan Purnota; Torikul Islam; Nazneen Ara Sultana; Shamima Aktar; Zoheb Hasan Fahad; Mehdi Rahimi; Kamal Uddin (International Journal of Plant Production, 2026)

Advanced Nanomanagement of Chickpea Wilt through Biosynthesized Metal Oxide Nanoparticles Derived from Syzygium cumini - Samia Saleem; Bushra Solanki; Asfa Rizvi; Mohd. Saghir Khan (Agricultural Research, 2026)

Sustainable insect management for date palm in arid Gulf agro-ecosystems: challenges, bioinsecticides, and emerging innovations - Myriam Lamine; Ahlam Khallef; Ameni Ben Zineb; Samia Daldoul; Amine Elleuch; Ahmed Mliki; Sami Sayadi; Mahmoud Gargouri (International Journal of Tropical Insect Science, 2026)

Three-dimensional modelling of key parameters impacting the steam electrolysis in solid oxide electrolysis cell for clean hydrogen production - Azeem Mustafa; Yong Shuai; Zhijiang Wang; Alfredo Iranzo; Guene Lougou Bachirou; Muhammad Rafique; Muhammad Ammad Nasir; Samia Razzaq (Fuel, 2026)

Salt stress mitigation in pomegranate using olive mill solid waste derived phenolic extract - Sahar Ben Abdelwaheb; Samia Abboud; Azhar Ouni; Darine Tlili; Mourad Jellali; Amani Bchir; Noomene Sleimi; Soumaya Dbara (Biocatalysis and Agricultural Biotechnology, 2026)

Impact of chain-length of sulfhydryl-modified surface-decorated surfactants on mucoadhesive nanostructured lipid carriers - Samia Kausar; Sofia O. D. Duarte; Ahmed Raza Hashmi; Farwa Zahra; Alia Erum; Shumaila Arshad; Ume Ruqia Tulain; Mulazim Hussain Asim; Pedro Fonte (Drug Delivery and Translational Research, 2026)
Nanostructured lipid carriers (NLCs) decorated with sulfhydryl-modified surfactants have recently gained attention for delivering BCS Class IV drugs. However, the impact of the chain-length of these surfactants on the permeation and bioavailability properties of NLCs is still unknown. Therefore, this study investigates the effect of surfactant chain-length on the mucoadhesive, permeation, and bioavailability properties of NLCs. For this purpose, short- and long-chain sulfhydryl-modified polyethoxylated surfactants were generated to develop mucoadhesive NLCs and loaded with the model drug aprepitant (APT). NLCs were characterized and assessed for comprehensive physicochemical and biological evaluations. Moreover, in-vivo studies were performed for proof-of-concept to show enhanced oral drug bioavailability. NLCs showed particle size under 200 nm with 6.9 and 6.7% drug loading and 85 and 84% drug entrapment for short- and long-chain surfactants, respectively. The drug-loaded NLCs were safe and stable, and short- and long-chain surfactants containing NLCs exhibited 11.6- and 9.6-fold enhanced mucoadhesion, respectively. Moreover, in comparison to long-chain sulfhydryl-modified surfactant, short-chain surfactant is transported into deeper segments of mucus due to less interaction with the mucus. Similarly, short-chain sulfhydryl-modified surfactants showed significantly enhanced cellular permeation across Caco-2 cell lines. Furthermore, the long-chain sulfhydryl-modified surfactants showed 4.38-fold enhanced C max , whereas due to better diffusion and mucoadhesion properties, the short-chain surfactants exhibited 5.38-fold enhanced C max . Similarly, 34.8% relative bioavailability was attained for short-chain surfactants and 24.8% for long-chain surfactants. These results suggest short-chain sulfhydryl surfactants are promising candidates for improving the oral delivery of poorly soluble drugs and warrant further investigation for clinical translation. Graphical Abstract

Economic and productive impacts of dietary turnip (Brassica rapa) leaf powder on Nile tilapia (Oreochromis niloticus) fingerlings - Samia Fawzy; Sara Mohammed; Haitham G. Abo-Al-Ela; Mohamed A. Helal; Seham El-Kassas (Animal Feed Science and Technology, 2026)

Unveiling Hidden Threats: Molecular Detection and Genetic Diversity of Hepatozoon spp. and Toxoplasma Gondii in Wild Rodents of Saudi Arabia and Their Ectoparasites - Maryam Ijaz; Samia Q. Alghamdi; Abdullah D Alanazi; Mubashra Salim; Muhammad Naeem; Muhammad Ali; Shabana Mukhtiar; Kasim Sakran Abass; Hira Muqaddas; Adil Khan; Furhan Iqbal (Acta Parasitologica, 2026)

Screening of durum wheat landraces (Triticum durum Desf.) for resistance to Fusarium foot and root rot under rainfed conditions - Samira Chekali; Salem Marzougui; Samia Gargouri; Timothy Paulitz (Journal of Plant Pathology, 2026)

Using the red mullet, European hake, and common seabream as biomonitors of trace metal levels and associated health risks from the southwestern Mediterranean Sea - Ahmed Inal; Yassine Guendouzi; Redouane Benfares; Yasmina Belkacem; Sidali Kourdali; Billal Zenati; Samia Benmoussa; Mostefa Boulahdid (Marine Pollution Bulletin, 2026)

Epidemiological profile and faunistic aspects of scorpionism in central Morocco: Evidence from three provinces - Abdessamad Elmourid; Siham Namiq; Samia Boussaa; Moulay Abdelmounim El Hidan; Btissam Bouimeja; Oulaid Touloun (Toxicon, 2026)

Toxicity and bioconversion: Meta-analytical insights into microplastic effects on black soldier fly rearing - Muhammad Salam; Valentina Grossule; Chujun Li; David Renault; Amira E. Mahmoud; Samia Elouali; Fayuan Wang; Sami Ullah; Viviana Bolletta; Yongchang Cao (Science of The Total Environment, 2026)

From Cardiac to Cerebral: Exploring the Association Between Seizures and Congenital Heart Disease - Samia Aziz Sulaiman; Abdallah Alaarag; Christie Dib; Haneen A. Banihani; Dina Mohammed; Basel Al Aloul (Next Research, 2026)

Green synthesized iron-zinc oxide nanoparticles promote growth in Mesorhizobium inoculated chickpea: A promising approach for sustainable legume production - Samia Saleem; Asfa Rizvi; Mohd.Saghir Khan (Next Research, 2026)

Corrigendum to “Identification of caseinophosphopeptides generated through in vitro gastro-intestinal digestion of Beaufort cheese” [Int. Dairy J. 129–134, 0958–6946] - Isabelle Adt; Coralie Dupas; Rachel Boutrou; Samia Dhahri; Nadia Oulahal; Claude Noel; Daniel Mollé; Thierry Jouvet; Pascal Degraeve (International Dairy Journal, 2026)

Cinnamaldehyde mitigates polycystic ovary syndrome pathologies by modulating NLRP3/NF-κB mediated inflammation using letrozole-induced model in female rats: a comprehensive in vitro,in vivo, in silico investigation - Arfah Siddiqua; Abdul Malik; Samia Gul Niazi; Ambreen Malik Uttra; Malik Hassan Mehmood; Mughisa Munir; Urooj Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Liquid chromatography- mass spectrometry profiling, antioxidant and allelopathic activities of leaf extracts from Eucalyptus torquata and Eucalyptus Campaspe - Ferjani Dhaouadi; Hela Sakka; Samia Ayari; Yassine Mrabet; Ismail Amri; Oumayma Kochti; Mouldi Saidi; Abdelnaceur Boulila; Naceur Mejri (Euro-Mediterranean Journal for Environmental Integration, 2026)

Iron Balance and Cardiovascular Health: The Double-Edged Role of Deficiency and Overload - Ameer Awashra; Mohammed AbuBaha; Bayan Mahafdah; Bara AbuBaha; Samia Aldwaik; Ayman Khaled; Layan Omar; Hamza A. Abdul-Hafez; Ahmed Emara; Mohamed S. Elgendy; Abdalhakim Shubietah (Cardiovascular Toxicology, 2026)

Site conditions but not intraspecific competition impact Eastern redcedar (Juniperus virginiana) sapling growth and physiology along a stress and latitude gradient - Samia Hamati; Juliana S. Medeiros; David Ward (Journal of Plant Research, 2026)

Factors influencing antifungal activity of selected lactic acid bacteria strains and characterization of their active compounds - Tarik Lakhlifi; Samia El oirdi; Ahmed Chbihi Kaddouri; Abdelhaq Belhaj (Antonie van Leeuwenhoek, 2026)

Polyphenols from an endemic Algerian medicinal plant: Henophyton deserti, optimization and evaluation of biological activities - Oussama Boukhalfa; Khaled Sekkoum; Samia Hadj Rabia; Nasser Belboukhari (Vegetos, 2025)

Heavy metal accumulation and benthic foraminiferal response following the Peruvian Ventanilla crude oil spill (January 2022) - Leonela Rojas-Portilla; Diana Ochoa; Jorge Cardich; Elizabeth Silva-Berrospi; Sara Cárdenas-Farfán; Arturo Aguirre-Velarde; Matthieu Carré; Irina Djouraev; Samia Hidalgo; Dimitri Gutiérrez; Raul Loayza-Muro; María Rivera-Ch; et al. (Regional Studies in Marine Science, 2025)

Sharks in the Southeastern Mediterranean: Species diversity, fisheries, market, and conservation measures - Sahar F. Mehanna; Mohamed Samy-Kamal; Mohammed G. Desouky; Samia M. El-Mahdy; Yassein A. Osman; Zeinab M. Koleib; Rania Ibrahim (Regional Studies in Marine Science, 2025)

Gastronomic tourism and tourist hedonic well-being: A moderated mediation model based on perceived authenticity, emotional connection, and tourist food neophilia - Jawad Khan; Samia Ayed Al Jaeed; Qingyu Zhang; Mingxing Li (International Journal of Gastronomy and Food Science, 2025)

Enhancing microbial safety and shelf life of chicken meat with bioactive packaging incorporating bio-AgCl nanoparticles and organic acids - Ibrahim Benamar; Omar Messaoudi; Asma Cherif Anntar; Samia Bellifa; Salih Barka; Yasmine Djaid; Abdelhalim Zoukel; Mohamed Merzoug; Keltoum Bendida; Ilhem Messahli; Nahida Bendimerad; Boumedine Moussa Boudjemaa (Food Research International, 2025)

Double-layer stratification of Cross fluid flow with viscous dissipation and variable thermal conductivity - T. Salahuddin; A. Maqsood; Muhammad Awais; Mair Khan; Anum Tanveer; Samia Elattar (Dynamics of Atmospheres and Oceans, 2025)

A functional self-assembled layer with preferential sodium adsorption sites for ultra-stable sodium metal batteries - Moazzam Ali; Asif Mahmood; Muhammad Ali; Samia Aman; Hamid Hussain; Xuan Zhang; Yinzhu Jiang; Xufeng Lin; Muhammad Yousaf (Chemical Engineering Journal, 2025)

From pollutant to soil input: Phytotoxicity and physicochemical profiling of olive mill residues for safe agriculture reuse - Samia Abboud; Sahar Ben Abdelwaheb; Darine Tlili; Azhar Ouni; Mourad Jellali; Karim Lahmar; Rania Aydi Ben Abdallah; Nour Sghaier; Soumaya Dbara (Bioresource Technology Reports, 2025)

Effects of climate change on precipitation and runoff in semi-arid regions: future scenarios and implications for water - Sahar Sameer Al-Hilali; Ahmed Ali Hassan; Ahmed Moustafa Moussa; Sherien Ahmed Zahran; Samia Abou El-Fotouh (Theoretical and Applied Climatology, 2025)

Balancing efficacy and hepatotoxicity: a comprehensive review of oral medications in psoriasis management - Alaa E. Elsisi; Sally El-Sayed Abu-Risha; Mahmoud Abdelrahman Alkabbani; Laila A. Ramadan; Samia Salem Sokar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Psoriasis is a chronic, immune-mediated inflammatory disorder that significantly impacts patients’ quality of life. Oral systemic therapies, including methotrexate, cyclosporine, acitretin, and apremilast, remain integral to psoriasis management, particularly for patients with moderate-to-severe disease who cannot afford biologic therapy. While these treatments are effective, their long-term use is often limited by adverse effects, particularly hepatotoxicity. Methotrexate and acitretin are associated with liver toxicity, requiring regular monitoring, whereas cyclosporine presents a lower but notable risk. Apremilast, a phosphodiesterase 4 inhibitor, offers a safer hepatic profile but has lower efficacy than traditional systemic agents. Emerging therapies, such as TYK2 inhibitors, RORγt inhibitors, and novel PDE4 inhibitors, aim to improve treatment efficacy while minimizing adverse effects. Advances in understanding hepatotoxicity mechanisms have led to identifying predictive biomarkers and hepatoprotective strategies, including antioxidants and non-invasive imaging techniques. Personalized medicine approaches, including pharmacogenomics, are revolutionizing treatment selection by optimizing efficacy while minimizing toxicity risks. This comprehensive review examines oral psoriasis treatments’ efficacy and hepatotoxicity profiles, discusses novel therapeutic developments, and explores strategies for mitigating liver-related adverse effects. A balanced approach that integrates clinical monitoring, lifestyle modifications, and emerging precision medicine techniques is essential for optimizing long-term treatment outcomes. Future research should focus on refining predictive models for drug-induced liver injury and developing targeted therapies with improved efficacy and safety profiles. Graphical Abstract Created in BioRender. Elgindy, A. (2025) https://BioRender.com/vcab653

The potential role of long non-coding RNAs (HOTAIR and NEAT1) in patients with rheumatoid arthritis - Amira S. Al Karamany; Magdy M. Ibrahim; Youmna M. Salah Eldeen; Doaa E. Kamal; Samia Hussein; Abdallah S. Abdelazem (Molecular Biology Reports, 2025)

The role of IKZF1 rs4132601 and Δ4–7 somatic deletion in acute lymphoblastic leukemia: a bioinformatics and case-control study - Ismail Soltani; Wael Bahia; Chaker Slaymi; Hanene Gharbi; Yosra Hasni; Salima Ferchichi; Samia Menif; Wassim Y. Almawi (Molecular Biology Reports, 2025)

Phenotypic diversity of Saharan wheat landraces growing on oasis farms in Algeria: the influence of climate and geography on the distribution of traits - Sabrina Oumata; Philippe Monneveux; Maria Zaharieva; Samia Yahiaoui; Leila Mekliche-Hanifi; Jacques David (Genetic Resources and Crop Evolution, 2025)

Experimental investigation for enhancement of thermal energy storage phase change material systems based on waste date palm fronds - Yasir Al-Hamadani; Hanen Nouri; Najoua Mekaddem; Samia Ben-Ali (Euro-Mediterranean Journal for Environmental Integration, 2025)

Dynamics of metal contamination along the Monastir-Sayada coast: sediment core observations and multivariate analysis - Nouha Khiari; Abdelkrim Charef; Samia Khadhar; Faouzi Zahi (Euro-Mediterranean Journal for Environmental Integration, 2025)

Hydrogeochemical assessment of groundwater quality and controlling processes in the quaternary aquifer of Oued Souf, Southeastern Algeria - Karima Boukhallat; Samia Halimi; Khaldia Si Tayeb; Maurizio Barbieri; Dounia Dib; Noureddine Bouchareb; Abdelaziz Bouzegag (Carbonates and Evaporites, 2025)

The mediating effect of farmer’s knowledge on the relationship between agricultural services, skills acquisition and food security - Samia Nassar; Md Billal Hossain; Éva Zsuzsanna Tóth Naárné; László Vasa (Environment, Development and Sustainability, 2025)
Enhancing productivity, income, and food security requires agricultural services and skill development, especially in vulnerable areas like the Gaza Strip where farmers constantly confront obstacles. With an emphasis on the mediating function of farmers' knowledge, this study investigates the connections among household food security, skill development, and agricultural services. 379 farmers in the Gaza Strip were surveyed using a quantitative methodology. In order to examine the direct and indirect effects of agricultural services and skills on food security outcomes, data were gathered using structured questionnaires and analyzed using SPSS software. The findings show that farmers' knowledge and levels of food security are greatly and favorably impacted by agricultural services. It was discovered that having access to financial support, technical help, and agricultural inputs improved farmers' ability to provide food for their families. Additionally, learning agricultural skills helped farmers become more knowledgeable, which enhanced the results of food security. These results demonstrate how knowledge acts as a mediator in converting training and services into noticeable increases in livelihoods. The study comes to the conclusion that two important ways to improve food security in the Gaza Strip are to invest in skill development and to boost agricultural services. To optimize the impact on household resilience and food security, policymakers and development practitioners are urged to create interventions that include technical assistance, input provision, and capacity-building initiatives.

Characterisation and comparison of volatile compounds in leaves and stems essential oils of Heliotropium bacciferum (forssk.), a medicinal plant native to Algeria, by gC-mS analysis - Hanane Aissaoui; Ratiba Mekkiou; Samia Mezhoud; Jean-Claude Chalchat; Pierre Chalard; Fadila Benayache; Samir Benayache (Natural Product Research, 2025)

Identification and characterization of novel PRNP haplotypes in the Assaf sheep breed from Palestine - Muayad Salman; Ikram Ben Souf; Samia Khnissi; Angham Bani Odeh; Wael Halawa; Naceur M’Hamdi (Small Ruminant Research, 2025)

Study of the environmental and radiological aspects of municipal solid waste for energy generation - Mohamed Safwat Mohamed Tawfik; Samia Wafik Morsy; Mohamed Hegazy Mohamed Salama (Biomass and Bioenergy, 2025)

Overexpression of Grapevine Raffinose Synthase-Like Seed Imbibition Protein VvRS/SIP Gene Confers Salt Tolerance in Transgenic Tomato - Anis Ben-Amar; Dorsaf Allel; Amira Haouel; Samia Daldoul; Hatem Zaghden; Ahmed Mliki (Journal of Plant Growth Regulation, 2025)

Advances in anti-WSSV immune mechanisms of penaeid shrimp: decoding “Host–Pathogen Interactions for WSSD Resilience" - Samia Elbahnaswy; Eman Zahran; Mai A. M. El-Son; Eman A. Abd El-Gawad; Amany M. Shosha; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Shrimps are involved in diverse inherent defense reactions involving humoral and cellular immunity to recognize and eliminate viral invaders. Outbreaks provoked by the white spot syndrome virus (WSSV) have caused lethal devastation to penaeid shrimp aquaculture, with notable economic losses worldwide in the last 15 years. Despite intensive studies on WSSV characterization and infection mechanisms, information regarding WSSV-shrimp interactions must be explored to maintain the balance between immune-mediated protection and pathogenesis during viral infection. In-depth studies on cellular and humoral-mediated immune responses against WSSV have also been reported to assist in designing effective control strategies for WSSV, owing to their extensive emergence in large-scale shrimp production profits. This review discusses recent findings on the interaction of WSSV proteins recognized by shrimp receptors regulated by innate signaling immunological pathways, providing more ideas for effective prevention of viral infection. In addition, the molecular modifications exploited by WSSV evade shrimp immune responses for survival and replication. Additionally, summarizing viral reprogramming of host metabolic pathways provides basic knowledge for discovering new approaches to intensify the immune resistance of cultured shrimp against WSSV infections.

Dietary algal zinc nanoparticles improve liver function and immunity in Nile tilapia, Oreochromis niloticus - Eman Zahran; Fatma Ahmed; Samia Elbahnaswy; Omar A. Ahmed-Farid; Ahmed I. A. Mansour; Engy Risha; Hanan H. Abdelhafeez; Khalid M. Alkhodair; Mahmoud G. El Sebaei (Aquaculture International, 2025)

Enhanced plant-assisted microbial remediation of oil drill cutting from arid areas - Samia Haddadi; Christine Cagnon; Mustapha-Mohamed Benamara; Cristiana Cravo-Laureau; Robert Duran (Environmental Science and Pollution Research, 2025)

Polyphasic characterization and statistical optimization of cellulase production by Streptomyces alfalfae GHS22, a novel soil-derived Actinobacterium - Samia Gharbi; Noureddine Karkachi; Kamal Bendedouche; Mehdi Adjdir (Biologia, 2025)

Modelling mycelial responses to nitrogen limitation during litter decomposition - Samia Ghersheen; Stefano Manzoni; Marie Spohn; Björn D. Lindahl (Soil Biology and Biochemistry, 2025)

Climbing with microbes: How elevation shapes the bacterial root microbiome of wild grapevine and selects plant growth-promoting hubs for sustainable viticulture - Imane Bahlouli; Samia Daldoul; Ameni Ben zineb; Ahmed Mliki; Francesco Mercati; Mahmoud Gargouri (Science of The Total Environment, 2025)

Identification of peste des petits ruminants virus, Greece, 2024 - Aikaterini Kirtzalidou; Angeliki Katsifa; Georgios Komitas; Anna Xexaki; Athanasios Konstantinidis; Dimitrios Vourvidis; Maria Gianniou; Olivier Kwiatek; Samia Guendouz; Arnaud Bataille; Thomas Alexandropoulos; Konstantia E. Tasioudi (Research in Veterinary Science, 2025)

Titanium carbide MXenes – Early identification of safety, sustainability and regulatory issues - Samia Ouhajji; Elmer Swart; Doris Völker; Kathrin Schwirn; Bengt Fadeel; Agnes G. Oomen (NanoImpact, 2025)

Zinc oxide-modified glass-coated tin-doped indium oxide electrode for the electrocatalytic reduction of hydrogen peroxide in neutral media - Nadia Ait Ahmed; Katia Hebbache; Abderrezak Lahreche; Samia Kerakra; Katia Nasri; Nabila Aliouane; Carine Chassigneux; Marielle Eyraud (Journal of Water Process Engineering, 2025)

Structure-guided identification of potential inhibitors of MurB from S. typhimurium LT2 strain: towards therapeutic development against multidrug resistance - Fawaz M. Almufarriji; Bader S. Alotaibi; Ahlam Saleh Alamri; Samia S. Alkhalil; Nada Alkhorayef (Molecular Diversity, 2025)

The Ambiguous Role of Silicon in the Pregermination Treatment of Vigna Unguiculata Seeds - Lilya Boucelha; Réda Djebbar; Samia Benlahrech (Journal of Plant Growth Regulation, 2025)

Chitosan-enhanced hydroponic cultivation of Ocimum basilicum L.: a sustainable approach for improved growth, quality and antioxidant activity - Samia Elouali; Jihane Elarabi; Fatima El Amerany; Youssef Ait Hamdan; Nadia Eladlani; Samira Benali; Hassan Lamtai; El Hassan El Mouden; Jean-Marie Raquez; Mohammed Rhazi (Euro-Mediterranean Journal for Environmental Integration, 2025)

Evaluation, efficacy and function of essential oils from Lantana camara L. Morocco leaves for the antioxidant activity and as a bio-insecticide against the wheat weevil Sitophilus granarius in post-harvest crops - Nora Baouahi; Mohammed Bouhadi; Chaimaa Elagdi; Hasna Hamdane; Samia Yousfi; Mouna Latifa Bouamrani; M’hammed El Kouali; Mohammed Talbi; Laila Bennani (Euro-Mediterranean Journal for Environmental Integration, 2025)

Eco-friendly algae-based nanoparticles among other green antifouling paints with in vitro and on-site antimicrobial activity - Madelyn N. Moawad; Samia K. Hamdona; Ghada E. Hegazy; Alaa M.F. Alqazzaz; Fedekar Fadel Madkour; Hermine R.Z. Tadros (Algal Research, 2025)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

Chemical Composition and Antifungal Activity of Essential Oils from Lavandula dentata L., Cymbopogon citratus DC. Stapf., and Salvia officinalis L. against Rhizoctonia solani in Potato Tubers - Noura Jemai; Kaouther Ben Mahmoud; Emna Jedidi; Samia Gargouri; Amira Hachana; Ahmed Jemmali; Abdennacer Boulila (Potato Research, 2025)

Orange peel extract and hesperidin attenuate myeloperoxidase activity and oxidative stress in vitro, with anti-inflammatory effects in vivo: a natural approach to gingival protection - Tinhinane Rekeb; Samia Bedouhene; Nassima Senani; Sahra-Amel Belambri; Meriem-Dehbia Chabane; Kahina Ladj; Riadh Ksouri; Pham My-Chan Dang; Jamel El Benna (Inflammopharmacology, 2025)

Trends and sustainability insights in Bio-based PCM composites for thermal energy storage: a bibliometric analysis - Najoua Mekaddem; Hanen Nouri; Samia Ben-Ali (Environment, Development and Sustainability, 2025)

Environmental distribution of biofilm-forming antibiotic-resistant Escherichia coli associated with plastic surface materials - Md. Oliullah Rafi; Md. Abdullah Evna Hasan; Naeem Ahammed Ibrahim Fahim; Md. Tabeer Hossain Antor; Samia Salam; Rony Ibne Masud; Dilruba Akter Jany; Zuhayr Bakhtiyar; Mohammad Ferdousur Rahman Khan; Md. Tanvir Rahman (Environmental Science and Pollution Research, 2025)

Enhancing growth, pigmentation, and health in Penaeus vannamei through zeaxanthin supplementation - Yucai Xue; Samia Fawzy; Meiqin Wu; Ganfeng Yi; Amina S. Moss; Xuxiong Huang; Weilong Wang (Aquaculture, 2025)

Isolation and computational characterization of a novel cyanogenic glucoside from Centaurea microcarpa with antiviral potential against SARS-CoV-2: DFT, ADMET, and molecular docking analysis - Rachida Kerkour; Samia Baatouche; Abir Boublia; Nadjib Chafai; Ramadan Seghiri; Djamel Sarri (Phytochemistry Letters, 2025)

Harnessing the fish gut microbiome and immune system to enhance disease resistance in aquaculture - Mai A.M. El-Son; Samia Elbahnaswy; Mohsen A. Khormi; Ali M. Aborasain; Hanan H. Abdelhaffez; Eman Zahran (Fish & Shellfish Immunology, 2025)

In vitro micropropagation and salt tolerance of Tunisian halophytes: Salicornia fructicosa (L.) A. J. Scott and Arthrocnemum macrostachyum (Moric.) C. Koch: as evidenced by mineral and micromorphological analysis - Badra Bouamama-Gzara; Atrous Ghofrane; Gandoura Samia; Dabebi Afef; Nafati Haythem; Farah Faten; Zemni Hassene; Karim Ben Hamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Identification of a sequence polymorphism in PST_8713 effector of Puccinia striiformis f.sp tritici and its docking with putative interacting wheat pathogenesis-related (PR) proteins - Beena Siddiqua; Saboohi Raza; Sarah Ali; Samia Sattar; Abdul Qayoom Rajput; Shafaq Aiyaz Hasan (European Journal of Plant Pathology, 2025)

Genetic analysis and marker assisted selection using KASP markers in a doubled haploid bread wheat population - Chafika Djenadi; Samia Yahiaoui; Meriem Abdelguerfi-Laouar; Zine El Abidine Fellahi; Meriem Ouakkal; Sripada M. Udupa (Euphytica, 2025)

Seasonal upwelling drives surface water biogeochemistry with implication for ocean acidification along the Northwest African coast - Chaimaa Jamal; Ahmed Makaoui; Melissa Chierici; David Cervantes; Adil Chair; Hasnaa Nait Hammou; Mohammed Idrissi; Fatima Zohra Bouthir; Omar Ettahiri; Samia Yousfi; Mouna Latifa Bouamrani (Frontiers in Marine Science, 2025)
This study assesses the impact of intensified upwelling on the marine carbonate system along the Northwest African coast, from Cape Blanc (21°N) to Cape Cantin (33°N), a region where ocean acidification observations remain limited. We analyze surface water variability using data from two oceanographic surveys conducted aboard the R/V Dr. Fridtjof Nansen in spring and autumn 2022. The analysis is based on observational data of temperature, salinity, dissolved oxygen, chlorophyll a, pH, total alkalinity, and derived carbonate system variables. In spring, upwelling was widespread across the study area, while in autumn it was more localized near Cape Draa (28°30'N), between Cape Boujdour and Dakhla (25°30N–23°30N), and at Cape Blanc (21°N). Both spring and autumn were influenced by low-oxygenated South Atlantic Central Water (SACW), which is rich in DIC (2160–2250 µmol/kg), and upwelled to the surface, lowering pH (~7.85–7.95) and aragonite saturation state (ΩAr ~1.5–2.5). The strongest acidification signals were observed in autumn at Cape Draa (28°30N) and Cape Blanc (21°N), where the lowest pH (7.8) and ΩAr (1.5), along with the highest DIC (2250 µmol/kg), were recorded. The study clearly shows that the lowest pH values and highest DIC concentrations were related to the influence of SACW upwelling at Cape Blanc. It was also evident that areas with high chlorophyll a coincided with higher ΩAr and pH in spring. This suggests that primary production (PP) during spring counteracts the effect of upwelled low-pH water along the coast. Areas of high PP, such as at Cape Draa (28°30N), experienced increased DIC levels and enhanced acidification after the bloom season, potentially influenced by organic matter remineralization. Our findings highlight the influence of upwelling and biological processes on surface carbonate chemistry along the Northwest African coast. This study emphasizes the necessity of long-term monitoring to assess ocean acidification trends and their ecological implications in this vulnerable region.

Minimum information guidelines for VOCs analysis using GC-MS - Samia Mokh; Tania Portoles; Jordi Gamir (Trends in Plant Science, 2025)

Bee venom modulates human neutrophil inflammatory functions in Vitro and exerts an anti- inflammatory effect in Vivo in rats - Meriem-Dehbia Chabane; Samia Bedouhene; Sahra-Amel Belambri; Nassima Senani; Tinhinane Rekeb; Kahina Ladj; Riadh Ksouri; Pham My-Chan Dang; Jamel El-Benna (Inflammopharmacology, 2025)

Integrated morpho-physiological and biochemical description of the mechanisms leading stress responses in cyanobacteria (Arthrospira platensis) upon exposure to Erythromycin - Mahfoud Ainas; Nabil Touzout; Hichem Tahraoui; Houssem Eddine Mokeddem; Hamza Moussa; Samia Kherbouche; Samia Mebrouk; Jie Zhang; Abdeltif Amrane (Ecotoxicology, 2025)

Adsorption of methylene blue by lemon verbena leaf waste: valorization, decontamination and modeling - Samia Yarik; Fatiha Barka Bouaifel; Nacer Bezzi; Imane Akkari; Sofia Kessi; Kenza Bouaouina (Environmental Monitoring and Assessment, 2025)

Evaluation of chalcones as new glycogen phosphorylase inhibitors – an in-vitro and in-silico approach - Talal Ahmed Awad; Fatima Alfatih; Muhammad Shafiq; Mohnad Abdalla; Samia T. Al-Shouli; Amani Bashir; Maaweya E. Awadalla; Hassan A. Alhazmi; Mohammed Albratty; Hafiz A. Makeen; Asaad Khalid; Zaheer Ul-Haq (Natural Product Research, 2025)

Ameliorating the deleterious effect of water deficit stress on pomegranate through soil application of polyphenols-enriched extract from olive mill solid wastes - Samia Abboud; Darine Tlili; Azhar Ouni; Sahar Ben Abdelwaheb; Karim Lahmar; Mourad Jellali; Nour Sghaier; Rania Aydi Ben Abdallah; Soumaya Dbara (Journal of Environmental Chemical Engineering, 2025)

Fate of antibiotic resistance genes under different wastewater treatments and environmental conditions in an Algerian watershed - Dalal Boulainine; Aziz Benhamrouche; Elisenda Ballesté; Samia Mezaache-Aichour; Cristina García-Aljaro (Environmental Pollution, 2025)

First report on the molecular characterization and phylogenetic analysis of meq oncogene from virulent serotype-1 Marek's disease virus in laying hen flocks and broiler breeders in Algeria - Samia Ameziane; Omar Salhi; Nabila Hammami; Salim Zaidi; Amina Amraoui; Aya Bensalem; Meriem Tahraoui; Nassim Ouchene; Nadjet Amina Khelifi Touhami; Sana Hireche; Amir Agabou (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Plant extracts and plant growth promoting rhizobacteria: seed bio-priming approach to improve tolerance of Lactuca sativa L. under salt stress - Wided Gassoumi; Hasna Ellouzi; Imen Ben Slimene; Feten Zar Kalai; Rayda Ben Ayed; Walid Zorrig; Ahmed Debez; Chedly Abdelly; Samia Oueslati (Euro-Mediterranean Journal for Environmental Integration, 2025)

Association of Renin–Angiotensin Pathway Gene Polymorphisms with COVID-19 Susceptibility and Severity in Moroccans: A Case–Control Study - Fatima-Zahra El Yousfi; Samia El Hilali; Jihane Belayachi; Khalid Ennibi; Rachid Razine; Redouane Abouqal; Ahmed Bouhouche (Biochemical Genetics, 2025)

Synergistic defect engineering and z-scheme heterojunction in ultrasonication assisted CuFe LDH and carbon vacancies modified g-C3N4 composite for electrocatalytic water splitting and photocatalytic dye degradation - Muhammad Usman; Khurram Imran Khan; Samia; Sidra Khalid; Faiq Saeed; Abdul Wahab; Muhammad Sajjad Asghar; Ahmad Althobaiti; Alsharef Mohammad; Haitao Dai (Journal of Water Process Engineering, 2025)

Enhancing the generation and stabilization of ZnO nanoparticles on modified clay with polyethylenimine to improve the photodegradation of dyes in textile wastewater - Afef Attia; Noureddine Elboughdiri; Djamel Ghernaout; Benjamin Carbonnier; Raja Ben Amar; Samia Mahouche-Chergui (Journal of Water Process Engineering, 2025)

Mushroom mediated selective bioreduction of S-(+)-carvone to cis -(-)-dihydrocarvone: approach towards a safer biocatalysis - Pranjit Kumar Bora; Begom Rifah Samia; Phirose Kemprai; Saikat Haldar (Natural Product Research, 2025)

Exploring omics solutions to reduce micro/nanoplastic toxicity in plants: A comprehensive overview - Samia Muhammad Arif; Ilham Khan; Muhammad Saeed; Sunbal Khalil Chaudhari; Mansour Ghorbanpour; Murtaza Hasan; Ghazala Mustafa (Science of The Total Environment, 2025)

Theoretical insights into the factors affecting the electrochemical performance of solid oxide electrolysis cells for CO2 reduction - Azeem Mustafa; Yong Shuai; Zhijiang Wang; Guene Lougou Bachirou; Mummad Rafique; Samia Razzaq; Muhamamd Ammad Nasir; Wei Wang; Enkhbayar Shagdar (Journal of Environmental Chemical Engineering, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

First report on the seroprevalence of Egg Drop Syndrome Virus-76 in laying hen flocks in Algeria - Omar Salhi; Samia Ameziane; Mohamed Rahal; Mustapha Nabi; Meriem Tahraoui; Chafik Redha Messaï; Aziz Lounas; Nassim Ouchene; Nadjet Amina Khelifi Touhami (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Antimicrobial activities and beta-lactamase inhibitory property of actinomycetes from Atlas forest soils in Northeastern Algeria - Ines Guehria; Adel Ayari; Nour El-Houda Degachi; Amel Nait Merzoug; Samia Réjiba (World Journal of Microbiology and Biotechnology, 2025)

Optimization of Heavy Metals Removal Through Pecan Shell-Based Modified Activated Carbon from Pharmaceutical Wastewater and Evaluation of the Treated Effluent for Irrigating Pisum sativum - Konain Khurshid; Rab Nawaz; Azeem Khalid; Shahid Mahmood; Samia Qadeer; Marlia Mohd Hanafiah; Muzammil Anjum (International Journal of Environmental Research, 2025)

Microbial conversion of Limonene-containing waste into transesterifiable bio-lipids: Evaluating oleaginous bacterial isolates - Faqin Lian; Samia Qadeer; Muzammil Anjum; Shang-Tian Yang; Shahid Mahmood; Abubakr. M. Idris; Azeem Khalid; Habib Ullah; Qing Huang; Zepeng Rao (Archives of Microbiology, 2025)

Characterization of Lactiplantibacillus plantarum strains isolated from Algerian fruits for probiotic and biotechnological applications - Lylia Ouarabi; Samia Hamma-Faradji; Nacim Barache; Ghania Zidi; Yanath Belguesmia; Djamel Drider (Antonie van Leeuwenhoek, 2025)

Wild-Type TP53 Predicts Poor Prognosis in Lower-Grade Glioma via TP53-CXCL14-GATA3 Axis - Amr Ahmed El-Arabey; Samia S. Alkhalil; Nouf Omar AlAfaleq; Sawsan Al-Shouli; Samah Saif Eldin M. Mohamed; Samia T. Al-Shouli; Mohnad Abdalla (Journal of Molecular Neuroscience, 2025)

Scabiosa artropurperea var.maritima aqueous extracts improve in vivo fertility parameters and in vitro granulosa cell steroidogenesis in Ewe - Wijden Niama; Samia Ben Said; Christelle Rame; Kahena Bouzid; Ahlem Bartakiz; Pascal Froment; Mokhtar Mahouachi; Joëlle Dupont (Theriogenology, 2025)

Novel sustainable bio-composite for latent heat storage based on pomegranate peels and coconut oil - Najoua Mekaddem; Hanen Nouri; Najet Mouguech; Samia Ben-Ali (Waste Disposal & Sustainable Energy, 2025)

Population Structure and Reproductive Biology of the Pebble Crab, Philyra corallicola (Decapoda: Brachyura: Leucosiidae) off Karachi Coast, Pakistan - Samia Aziz; Saima Siddique; Zarrien Ayub (Thalassas: An International Journal of Marine Sciences, 2025)

Nano-interventions for dengue: a comprehensive review of control, detection and treatment strategies - Samia Shaikh; Padakanti Sandeep Chary; Neelesh Kumar Mehra (Inflammopharmacology, 2025)

Morphometrics, geometrics and microstructures of scales of three fish species of genus Gerres from the Red Sea, Egypt - Imam A. A. Mekkawy; Usama M. Mahmoud; Samia M. El-Mahdy; Fatma Essa (Fisheries Science, 2025)

Adsorptive removal of Congo red dye from industrial effluent using cotton calyx iron oxide (CC-Fe3O4) composite - Shoomaila Latif; Amna Zahid; Fozia Batool; Samia Kanwal; Allah Ditta (Environmental Monitoring and Assessment, 2025)

FLTrans-Net: Transformer-based feature learning network for wheat head detection - Samia Nawaz Yousafzai; Inzamam Mashood Nasir; Sara Tehsin; Norma Latif Fitriyani; Muhammad Syafrudin (Computers and Electronics in Agriculture, 2025)

Maize plant development and antioxidant defense influenced by selenium-enriched Cyanobacteria species - Dina A. Refaay; Mostafa M. El-Sheekh; Samia A. Haroun; Amr M. Ayyad; Hoda H. Senousy (South African Journal of Botany, 2025)

Green growth transition and carbon neutrality nexus: A comparative study on the top carbon emitters - Samia Zahra; Eliyathamby A. Selvanathan; Rakesh Gupta; Maneka Savithri Jayasinghe (Journal of Environmental Management, 2025)

Key function mechanism of Na3PO4-modified NaX for enhanced performance and stability in side chain alkylation of toluene with methanol: DFT and experimental perspectives - Faraz Ahmad; Yueli Wen; Muhammad Zeeshan; Bin Wang; Awais Ashraf; Bai Hui; Zheng Cui; Chengda Li; Samia Kausar; Wei Huang (Fuel, 2025)

Design of decentralized water and wastewater management and reuse system for rural India: challenges and opportunities - Reshmi Das; P. S. Ganesh Subramanian; Nazli Koseoglu; Stephanie Connelly; Matteo Tamburini; Rachel Helliwell; Durba Biswas; Priyanka Jamwal; Jagadeesh Yeluripati; Samia Richards; Rowan Ellis; Lakshminarayana Rao (Sustainable Water Resources Management, 2025)

Sustainable Intersections: Minimizing Energy Consumption and Environmental Impact Through Coordination and Communication Technologies - Tarek Othmani; Samia Boubaker; Ferid Rehimi; Ahmed T. M. Halawani; Souheil El Alimi (International Journal of Environmental Research, 2025)

Chitosan from Periplaneta americana L.: a sustainable solution for heavy metals removal - Samia Elouali; Hicham Ait Ali Ouydir; Youssef Ait Hamdan; Nadia Eladlani; Mohammed Rhazi (Euro-Mediterranean Journal for Environmental Integration, 2025)

Correction to: Influence of astaxanthin‑enriched Haematococcus pluvialis microalgae on the growth efficacy, immune response, antioxidant capacity, proinflammatory cytokines, and tissue histomorphology of hybrid red tilapia - Elsayed A. A. Eldessouki; Gehad E. Elshopakey; Samia Elbahnaswy; Medhat S. Shakweer; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Amira Mili; Yasmin M. Abd El‑Aziz; Sameh A. Abdelnour; El‑Sayed Hemdan Eissa (Aquaculture International, 2025)

Nutritional Diagnosis and Morphophysiological Traits of Two Pomegranate Cultivars Under Macronutrient (N, P, K) Deficiencies and Excess - Azhar Ouni; Samia Abboud; Sahar Abdelwahab; Darine Tlili; Soumaya Dbara; Messaoud Mars (Applied Fruit Science, 2025)

Robust methane production from anaerobic digestion of maize silage: Feeding control using sliding mode control strategy with Anaerobic Digestion Model N°01 - Abdelhani Chaabna; Samia Semcheddine (Bioresource Technology, 2025)

Interlayers geo-environmental assessment of phosphate waste rock for sustainable management practices - Safa Chlahbi; Mostafa Benzaazoua; Abdellatif Elghali; Samia Rochdane; Essaid Zerouali; Tikou Belem (Environmental Geochemistry and Health, 2025)

Beyond agrochemicals: potential of nanoparticles as nanofertilizer and nanopesticide in legumes - Samia Saleem; Bushra Solanki; Mohd. Saghir Khan (Theoretical and Experimental Plant Physiology, 2024)

Characterization of anthropogenic impacts in Mediterranean intermittent rivers with chemical, ecological and hydrological indicators - Olga Gómez-Navarro; Anna Maria De Girolamo; Armin W. Lorenz; Samia Khadhar; Taha-Hocine Debieche; Francesco Gentile; Serge Chiron; Sandra Pérez (Journal of Hazardous Materials, 2024)

Maize–fusarium interactions: Tunisian insights into mycotoxin ecology - Samia Gargouri; Mario Masiello; Stefania Somma; Miriam Haidukowski; Rihab Khaterchi; Samira Chekali; Sonia Derouich; Virgilio Balmas; Antonio Moretti (Fungal Biology, 2024)

Evaluating the influence of Nano-GO concrete pavement mechanical properties on road performance and traffic safety using ANN-GA and PSO techniques - Xuguang Zhang; Li Liao; Khidhair Jasim Mohammed; Riadh Marzouki; Ibrahim Albaijan; Nermeen Abdullah; Samia Elattar; José Escorcia-Gutierrez (Environmental Research, 2024)

Eco-friendly nanotechnology in rheumatoid arthritis: ANFIS-XGBoost enhanced layered nanomaterials - Zhiyong Zhang; Mingtao Ye; Yisu Ge; Mohamed Gamal Elsehrawy; Xiaotian Pan; Nermeen Abdullah; Samia Elattar; Ehab El Sayed Massoud; Suxian Lin (Environmental Research, 2024)

Hydrocarbon-Degrading Microbial Consortia for Oil Drilling Waste Treatments in Arid Environments - Samia Haddadi; Christine Cagnon; Djamel Zeriri; Cristiana Cravo-Laureau; Robert Duran (Water, Air, & Soil Pollution, 2024)

Effect of competition, with exotic invasive Bromus inermis and native Quercus stellata, and soil amendment on the performance of native invasive Juniperus virginiana - Samia Hamati; Juliana S. Medeiros; David Ward (Plant Ecology, 2024)

Phaeohyphomycosis Due to Verruconis gallopava: Rare Indolent Pulmonary Infection or Severe Cerebral Fungal Disease? - Laura Terracol; Samia Hamane; Victor Euzen; Blandine Denis; Stéphane Bretagne; Sarah Dellière (Mycopathologia, 2024)

Potassium inwardly-rectifying channel subfamily J member 11 (KCNJ11) gene polymorphism in Egyptian type 2 diabetic patients: a single-center study - Abdallah S. Abdelazem; Osama Abdelaziz Gaber; Samia Hussein; Fatma Mahmoud Elsaid Nasr; Eman A. M. Elshorbagy; Sara Mohammed Ibrahim; Abdullah Mohammad Abdel-hameed; Mai Hamdy Rashad; Amal S. El-Shal; Al-Shabrawy M. Abdelnabi (Molecular Biology Reports, 2024)

Effect of human umbilical cord blood-mesenchymal stem cells on cisplatin-induced nephrotoxicity in rats - Samia Hussein; Mai M. Hasan; Abeer A. Saeed; Asmaa M. Tolba; Reham Sameh; Eman M. A. Abdelghany (Molecular Biology Reports, 2024)

Detection of phylogrouping, adhesin, and extended spectrum β-lactamases genes in hospital acquired uropathogenic Escherichia coli isolates - Hanaa M. El Maghraby; Hend Abdalla El-sayed; Samia Hussein; Doaa Sh. El Azawy; Osama Attia; Eman Elshahat Orabi; Yasmin Ahmed Fahmy (Molecular Biology Reports, 2024)

Growth Disturbance, Mineral Nutrient Imbalance, Specific Symptoms and Leaf Characteristics Changes in Two Pomegranate Cultivars Induced by Deficiencies and Excess of Ca, Mg, Zn and Fe - Azhar Ouni; Samia Abboud; Darine Tlili; Sahar Ben Abdelwaheb; Mourad Jellali; Wafaa Bousetta; Messaoud Mars; Soumaya Dbara (Journal of Soil Science and Plant Nutrition, 2024)

Exploring the potential use of chitosan derived from Hermetia illucens waste for olive oil mill wastewater treatment - Samia Elouali; Oumaima Dahbane; Youssef Ait Hamdan; Nadia Eladlani; Mohammed Rhazi (Euro-Mediterranean Journal for Environmental Integration, 2024)

Recombinant expression, downstream optimization, and therapeutic evaluation of recombinant human interleukin-37 for cancer therapy - Zaheer Abbas; Samia Afzal; Nao Akusa Fujimura; Muhammad Akram; Saad Tahir; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2024)

Influence of astaxanthin-enriched Haematococcus pluvialis microalgae on the growth efficacy, immune response, antioxidant capacity, proinflammatory cytokines, and tissue histomorphology of hybrid red tilapia - Elsayed A. A. Eldessouki; Gehad E. Elshopakey; Samia Elbahnaswy; Medhat S. Shakweer; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Amira Mili; Yasmin M. Abd El-Aziz; Sameh A. Abdelnour; El-Sayed Hemdan Eissa (Aquaculture International, 2024)

In-water Bacillus species probiotic improved water quality, growth, hemato-biochemical profile, immune regulatory genes and resistance of Nile tilapia to Aspergillus flavus infection - El-Sayed Hemdan Eissa; Ekemini Moses Okon; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Heba A. Dowidar; Samia Elbahnaswy; Omaima H. Ezzo; Mohammad Bodrul Munir; Ahmed Jalal Khan Chowdhury; Nadia A. Abd Elghany; Heba H. Mahboub; Moaheda E. H. Eissa; et al. (Aquaculture International, 2024)

Serum 17 Alpha-Hydroxyprogesterone Analysis- Performance Evaluation of Maglumi® X-8 Chemiluminescence Immunoassay - Sibtain Ahmed; Ayra Siddiqui; Shan Lakhani; Samia Khan; Rizwana Kausar; Imran Siddiqui (Indian Journal of Clinical Biochemistry, 2024)

Photolytic degradation of commonly used pesticides adsorbed on silica particles - Boulos Samia; Joanna Socorro; Amandine Durand; Etienne Quivet; Henri Wortham (Science of The Total Environment, 2024)

Advancements in Cr(VI) Removal from Aqueous Solution Using PLA/PBAT/GO/Cloisite 30b Hybrid Nanocomposite Polymer Inclusion Membranes - Meriem Houda Hammadi; Samia Kerakra; Said Bey; Ferhat Sellami; Atmane Djermoune; Abderrahmane Habi (Water, Air, & Soil Pollution, 2024)

Evaluation of performance and estimation of genetic parameters for milk yield and reproductive traits in Awassi and Asaf sheep breeds and crosses in the Palestinian territory - Muayad Salman; Samia Khnissi; Ikram Ben Souf; Jihad Abdallah; Wael Halaweh; Hasan Meydan; Faisal S. Rashaydeh; Naceur M’Hamdi (Tropical Animal Health and Production, 2024)

Cilostazol protects against gastric ulcers by regulating PPAR-γ, HO-1, PECAM-1, pErk-1, NF-κB, Bcl-2, and cleaved caspase-3 protein expression - Nagla A. El-Shitany; Eman A. EL-saidy; Mostafa E. EL-Naggar; Samia S. Sokar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Millions of individuals worldwide, across all age groups, suffer from the widespread health issue of gastric ulcers. In many experiments, cilostazol (Cls), a phosphodiesterase-3 inhibitor, was recently shown to have anti-ulcer activity. Notably, Cls increases the expression and transcriptional activity of PPAR-γ in vitro and in vivo. This study aimed to evaluate the protective effect of Cls against ethanol-induced gastric ulcers and clarify the possible underlying mechanisms with an emphasis on the role of PPAR-γ. Male albino rats were treated with ethanol to induce gastric ulcers, or they were pretreated with Cls, omeprazole (Omp), GW9662, or Cls + GW9662 for 14 consecutive days before receiving ethanol. Cls protects against ethanol-induced gastric ulcers. Cls treatment significantly reduced ethanol-induced upregulation of the pro-inflammatory markers (IL-1β, IL-6, TNF-α, and NF-κB), MDA (a marker of lipid peroxidation), and caspase-3 and cleaved caspase-3 (apoptotic markers). On the other hand, Cls treatment counteracted ethanol-induced downregulation of PPAR-γ, pErk-1, HO-1 and GSH (antioxidant markers), PECAM-1 and NO (healing markers), and Bcl-2 (antiapoptotic marker). However, when combined with GW9662, a potent antagonist of PPAR-γ, Cls loses its effects. In conclusion, these results suggest that PPAR-γ and pErk-1 are essential for Cls’s protective effects against ethanol-induced gastric ulcers. Graphical abstract

Understanding bacterial diversity, infection dynamics, prevention of antibiotic resistance: an integrated study in an Algerian hospital context - Meriem Adouane; Nabil Kadri; Nourelimane Benzitoune; Chafika Lakhdari; Samia Djellal; Lilla Ousmer; Hichem Tahraoui; Abdeltif Amrane; Hocine Remini; Farid Dahmoune; Khodir Madani (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Molecular epidemiology and genetic characterization of hepatitis B virus in two major provinces of Pakistan - Iqra Almas; Saeeda Tariq; Iram Amin; Muhammad Shahid; Muhammad Idrees; Samia Afzal (Archives of Virology, 2024)

The role of microbial coagulants on the physicochemical, proteolysis, microstructure and sensory properties of low-fat Edam cheese manufactured from ultrafiltered buffalo milk - Safaa A.M. El-Aidie; Roberto Castro-Muñoz; Basim Abu-Jdayil; Samia M. El-Dieb (International Dairy Journal, 2024)

Predicting concrete strength early age using a combination of machine learning and electromechanical impedance with nano-enhanced sensors - Huang Ju; Lin Xing; Alaa Hussein Ali; Islam Ezz El-Arab; Ali E.A. Elshekh; Mohamed Abbas; Nermeen Abdullah; Samia Elattar; Ahmed Hashmi; Elimam Ali; Hamid Assilzadeh (Environmental Research, 2024)

The Egyptian Nile estuarine habitats: a review - Khaled M. Abdelsalam; Hermine R. Z. Tadros; Abeer A. Moneer; Mona Kh. Khalil; Samia K. Hamdona; Laila Shakweer; Madelyn N. Moawad; Abeer A. M. El-Sayed; Ghada F. El-Said; Mona M. Ismail; Aida H. Shobier; Shimaa Hosny; et al. (Aquatic Sciences, 2024)
Estuaries are nutrient-rich environments characterized by a gradient in salinity due to the mixing of freshwater and seawater. These bodies of water play vital functions in nature and provide a wide variety of essential ecosystem services. In general, many natural and/or man-made activities have strongly stressed the Egyptian Nile estuarine habitats, as has the water shortage that was expected after the construction of the Grand Ethiopian Renaissance Dam. In recent decades, the Nile Delta has been considered to be one of the most important productive oil-producing petroleum regions due to onshore and offshore gas discoveries alongside gasoline and base oil generation. Up-to-date systematic reviews of the Egyptian estuarine habitats (Rosetta and Damietta) are missing, and the review reported here was undertaken to fill this gap. In this review, we consider the physical, chemical, geological, pollution, and biological parameters of Egyptian Nile estuaries. In this context, our aim is to contribute to a broader understanding of the Egyptian estuarine habitat; moreover, we provide potential warning signals that may aid in estuarine environmental protection. We found that most of the previous studies had focused on the two branches of the Nile or on the marine waters adjacent to these branches, and that only a few studies focused on the estuarine habitats themselves. In most of these previous studies, the salinity gradient of water was reported to be a significant factor in the distribution of the different measured parameters while, in contrast, more recent investigations confirm the importance of potential effluent sources in affecting the distribution of these parameters. We highly recommend that the data reported here be updated in future studies on different environmental aspects.

Comparative analysis of Quercus suber L. acorns in natural and semi-natural stands: Morphology characterization, insect attacks, and chemical composition - Sabrina Kassouar; Dalila Mecellem; Samia Djellal; Nourelimane Benzitoune (Journal of Biosciences, 2024)

Advancing tunnel equipment maintenance through data-driven predictive strategies in underground infrastructure - Xiaoping Zou; Jie Zeng; Gongxing Yan; Khidhair Jasim Mohammed; Mohamed Abbas; Nermeen Abdullah; Samia Elattar; Mohamed Amine Khadimallah; Sana Toghroli; José Escorcia-Gutierrez (Computers and Geotechnics, 2024)

Contaminant and residue profiles in Lebanese food: a comparative analysis with global standards - Khaled El Hawari; Mohammad El Khatib; Mariam Zeineh; Daniel Beh; Farouk Jaber; Samia Mokh (Food Additives & Contaminants: Part A, 2024)

Innovative Approaches for Sustainable Zinc Nutrition and Crop Yield Enhancement in Pea Plants Using Zinc Oxide Nanoparticles - Bushra Hafeez Kiani; Irshad Arshad; Samia Nazir; Ibrahim A. Saleh; Sobia Hafeez Kiani; Naser Zomot; Wahidah H. Al-Qahtani; Akram A. Alfuraydi; Mostafa A. Abdel-Maksoud (Journal of Soil Science and Plant Nutrition, 2024)

Corrigendum to “Modulation of the Sirtuin-1 signaling pathway in doxorubicin-induced nephrotoxicity synergistic amelioration by resveratrol and pirfenidone” [Tissue Cell (2024) 102330] - Samia Mahmoud Manawy; Eman Mohamed Faruk; Rabab Fawzy Hindawy; Mahmoud M. Hassan; Diaa M.G. Farrag; Mansour A.E. Bashar; Hanan Fouad; Rania Abubaker Bagabiri; Dina Allam Abdelmaksoud Hassan; Ahmed Mohammed Zaazaa; Mohamed Ghazy Attia Hablas; Kamal M. Kamal (Tissue and Cell, 2024)

Geochemical characteristics of Neoproterozoic metavolcanic rocks of Ariab Auriferous Volcanogenic Massive Sulfide deposit, Red Sea hills, North-East Sudan - Samia Abdelrahman; Mohammed Abdalla Elsharif Ibrahim; Huan Li; Elsheikh Mohamed Abdel Rahman; Mohamed Faisal (Journal of African Earth Sciences, 2024)

Identification and quantification of flavor compounds in smoked tuna fish based on GC-Orbitrap volatolomics approach - Samia Mokh; Leticia Lacalle-Bergeron; David Izquierdo-Sandoval; M. Carmen Corell; Joaquim Beltran; Juan Vicente Sancho; Tania Portolés (Food Chemistry, 2024)

Encapsulated probiotic Lactiplantibacillus strains with promising applications as feed additives for broiler chickens - Manel Sebouai; Samia Hamma-Faradji; Abdelmalek Rezgui; Widad Sobhi; Hadj Ahmed Belaouni; Riadh Ben Salah; Ali Aksas; Farida Bendali (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Enterobacter cloacae Induces SA-Dependent Systemic Acquired Resistance of Zea mays Against Fusarium oxysporum - Asmaa A. Sallam; Samia A. Haroun; Elhussiny A. Aboulnaga; Amr M. Mowafy (Journal of Plant Growth Regulation, 2024)
Plant Growth Promoting Bacteria have proven themselves in agricultural applications not only as biofertilizers but also as biocontrol agents against different phytopathogens. In this study, we focused on investigating the ability of Enterobacter cloacae to induce the immune response of Zea mays against Fusarium oxysporum infection. The bacterium was transformed with a plasmid to express Green Fluorescence Protein and used in a greenhouse experiment in combination with Fusarium infection in different treatments. E. cloacae successfully colonized the root, resulting in enhanced physical growth with great investment in leaf area, photosynthetic pigment production, and reduced anthocyanin content. E. cloacae left a considerable resistance to root rot caused by Fusarium, as the disease severity was reduced from 74.2% (in the case of Fusarium infection alone) to about 35.8% (in the case of E. cloacae addition 14 days before fungal infection). The amount of salicylic acid (SA) was markedly elevated, and Pathogen-Related Protein showed up to an eightfold increase in the expression level. From these results, we suppose that E. cloacae induces SA-dependent systemic acquired resistance, which allows pre-colonized plants to resist Fusarium infection.

Triphala involved in reducing the susceptibility of Nile tilapia (Oreochromis niloticus) fingerlings to Saprolegnia ferax infection by boosting immune and antioxidant responses, improving growth performance, histological improvement, and gene expression indicators - Samyah D. Jastaniah; Shahira A. Hassoubah; Nesreen Aljahdali; Najah M. Albaqami; Samia Nasr; Najlaa H. Almohmadi; Guillermo Tellez-Isaias (Aquaculture International, 2024)

Does ‘Chetoui’ Olive Cultivar Change Fruit and Oil Characteristics When Grown Outside Its Geographical Origin? - Soumaya Dbara; Samia Abboud (Applied Fruit Science, 2024)

Targeting SRD5A1 and MMP-2/NLRP3/TGF-β1 axis alleviates the amlodipine-induced gingival hyperplasia in rats: Emerging role of saw palmetto and folic acid - Manar Mohammed El Tabaa; Mahmoud Moustafa Aboud; Anis Anis; Eman Rashad; Samia Salem Sokar (Food and Chemical Toxicology, 2024)

Mushroom based biocatalyst for the synthesis of dehydrodieugenol from clove oil: A potent cytotoxic agent - Pranjit Kumar Bora; Phirose Kemprai; Begom Rifah Samia; Pankaj Bharali; Avisek Mondal; Saikat Haldar (Biocatalysis and Agricultural Biotechnology, 2024)

Imatinib pharmacokinetics and creatine kinase levels in chronic myeloid leukemia patients: implications for therapeutic response and monitoring - Mervat M. Omran; Amel B. Ibrahim; Raafat Abdelfattah; Samia A. Shouman; Marwa S. Hamza (European Journal of Clinical Pharmacology, 2024)
Background Imatinib treatment for certain cancers can lead to elevated creatine kinase (CK) levels, potentially indicating muscle injury, and ongoing research aims to understand the correlation between imatinib levels and creatine kinase to assess its impact on treatment response. Methods This single-center observational study involved 76 chronic myeloid leukemia (CML) patients receiving imatinib treatment, focusing on evaluating drug and metabolite levels using liquid chromatography–mass spectrometry (LC–MS-MS) instrumentation. Serum CK and creatine kinase-MB (CK-MB) levels were assessed using Colorimetric kits. Results CK and CK-MB levels were measured, CK showed a median value of 211.5 IU/l and CK-MB showed a median value of 4.4 IU/l. Comparing low and high CK groups, significant differences were found in peak and trough plasma concentrations of imatinib and its metabolites. Correlations between CK levels and pharmacokinetic parameters were explored, with notable associations identified. Binary logistic regression revealed predictors influencing the therapeutic response to imatinib and categorized expected CK levels into high or low, with peak levels of imatinib emerging as a significant predictor for CK level categorization. Conclusion The study highlights the link between imatinib’s pharmacokinetics and elevated CK levels, indicating a possible correlation between specific metabolites and improved treatment response. Individualized monitoring of CK levels and imatinib pharmacokinetics could enhance care for CML patients.

Response of durum wheat vs. bread wheat to Fusarium foot and root rot under semi-arid conditions - Samira Chekali; Sourour Ayed; Eya Khemir; Mohamed Saleh Gharbi; Salem Marzougui; Timothy Paulitz; Samia Gargouri (Journal of Plant Pathology, 2024)

A review of rare earth oxides-based photocatalysts: Design strategies and mechanisms - Chengping Zhang; Irshad Ahmad; Samia Ben Ahmed; Muhammad Danish Ali; Md Rezaul Karim; Hossein Bayahia; Mohammad Ahmad Khasawneh (Journal of Water Process Engineering, 2024)

Analyzing the effectiveness of energy aid for driving the transition towards energy decarbonization; Evidence from Asian developing countries - Zahra Naheed; Samia Nasreen; Aviral Kumar Tiwari; Saira Arsh (Journal of Environmental Management, 2024)

β-Galactosidase isolated from Ranunculus arvensis seeds to synthesize trisaccharide: Kinetics and thermodynamic properties - Suad A. Alghamdi; Khalil ur Rehman; Umber Zaman; Sohad Abdulkaleg Alshareef; Imen Zghab; Amal N. Alanazi; Samia Nasr; Shahid Ullah Khan; Mohammed Alissa; Abdullah A. Alqasem (Food Bioscience, 2024)

Utilizing nanotechnology to boost the reliability and determine the vertical load capacity of pile assemblies - Zhijun Xu; Zhengquan Wang; Du Jianping; Sami Muhsen; Hamad Almujibah; Nermeen Abdullah; Samia Elattar; Mohamed Amine Khadimallah; Riadh Marzouki; Hamid Assilzadeh (Environmental Research, 2024)

Cost-effective seawater desalination by photothermal membranes composed of biopolymers-doped graphene oxide using direct solar steam generation strategy - Mohamed I.A. Ibrahim; Israa S.M. Abozamil; Mervat A. Abdel-Kawi; Moataz Soliman; Samia K. Hamdona (Desalination, 2024)

Boosted Bio-Jet production: Unveiling the potential of a one-stage concurrent process of deoxygenation/upgrading versus two-stage sequential processes using Pt/Cl-Al2O3@Ni/ZSM-5 catalysts - Muhammad A. Abo El-Khair; Samia A. Hanafi; Muhammad G. Abd El-Moghny; Mohamed El Saied; Mamdouh S. Elmelawy; Mohamed S. El-Deab (Chemical Engineering Journal, 2024)

Guar gum, Ulva lactuca L. biomass, and xanthan gum-based copolymer novel biosorbent for adsorptive removal of acid orange 10 - Samia Kanwal; Fozia Batool; Gulnaz Sharif; Hafiza Komal Naeem; Sobia Noreen; Humaira Yasmeen Gondal; Umar Bin Kamal; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Performance evaluation of six RCMs for precipitation and temperature in a semi-arid region - Sahar Sameer Al-Hilali; Ahmed Ali Hassan; Ahmed Moustafa Moussa; Samia Abou El-Fotouh Hassan; Sherien Ahmed Zahran (Modeling Earth Systems and Environment, 2024)

Hydrogeochemical assessment and modeling of groundwater processes and pollution: a case study of the Grombalia aquifer in Northeast Tunisia - Farah khezami; Nouha Khiari; Abdelmalek Drouiche; Anis Chkirbene; Faouzi Zahi; Taha-Hocine Debieche; Samia Khadhar (Modeling Earth Systems and Environment, 2024)

Anti-gouty arthritis and anti-inflammatory effects of curcumin nanoparticles in monosodium urate crystals induced Balb/C mice - Chanda Javed; Razia Noreen; Samia gul Niazi; Mubin Mustafa Kiyani; Qurat Ul Ain (Inflammopharmacology, 2024)

Effects of dietary commercial phytobiotic “Sanacore® GM” on Pacific white shrimp (Litopenaeus vannamei) growth, immune response, redux status, intestinal health, and disease resistance against Fusarium solani - El-Sayed Hemdan Eissa; Samia Elbahnaswy; Amira Hussein El-Baz; Ehab El-Haroun; Mohamed Ashour; Abdallah Tageldein Mansour; Saadea Saadony; Adel F. El-Saeed; Hoda Kabary; Samyah D. Jastaniah; Bothaina A. Alaidaroos; Manal E. Shafi; et al. (Aquaculture International, 2024)
The use of phytobiotic as functional feed additives is a promising inducer for growth performance and immune response in the Pacific whiteleg shrimp ( Litopenaeus vannamei ). It can be also commercially applied in combination with chemotherapeutic agents and vaccines. This study was carried out to evaluate the use of a commercial phytobiotic feed additive, Sanacore® GM, containing vegetable fatty acids and inactivated Saccharomyces cerevisiae with herbal extracts , on growth, body composition, non-specific immune response, antioxidant index, intestinal microflora count, and fungal resistance to Fusarium solani challenge in Pacific white shrimp, Litopenaeus vannamei . Shrimp juveniles (5.00 ± 0.1 g) were randomly distributed into 12 hapas (1 m 3 ) in triplicates at a stocking density of 20 shrimp per hapa and fed increasing levels of Sanacore® (0, 0.1, 0.2, and 0.3%) for 63 days. At the end of the feeding trial, the experimental shrimp were infected with F. solani , and mortality was recorded for 15 days. Results revealed that growth performance, feed utilization, and whole-body protein deposition were improved with increasing dietary sanacore levels. A significant improvement was reported in cellular (hemocyte counts, phagocytosis, phagocytic index, respiratory burst activity) and humoral (lysozyme and phenoloxidase) immune responses with higher dietary sanacore levels. Superoxide dismutase, catalase, and glutathione peroxidase were notably improved in shrimp-fed sanacore-supplemented diets. Meanwhile, malondialdehyde level was significantly decreased in all sanacore-supplemented shrimp. Furthermore, the dietary sanacore consistently increased probiotic bacterial counts and decreased enteric and Clostridium sp. counts in the intestine. Juveniles fed with Sanacore exhibited significantly lower mortality rates when challenged with F. solani . In conclusion, dietary sanacore could exhibit a profitable effect on the growth performance, antioxidant capacity, immunity, intestinal microbial, and the health condition of L. vannamei . Thus, sanacore can be used as an attractive feed supplement in the L. vannamei diet (0.2–0.3%), providing more insights into its application in aquaculture as a functional immunostimulant feed additive.

Enhancing biological activities and phenolic content of wild grapevine roots by severe drought stress - Samia Daldoul; Faouzia Hanzouli; Nadia Fares; Olfa Tabbene; Hassène Zemni; Simone Vincenzi; Ahmed Mliki; Mahmoud Gargouri (Plant Biosystems, 2024)

Unraveling the effect of phenolic extract derived from olive mill solid wastes on agro-physiological and biochemical traits of pomegranate and its associated rhizospheric soil properties - Samia Abboud; Azhar Ouni; Rania Aydi Ben Abdallah; Amani Bchir; Sahar Ben Abdelwaheb; Darine Tlili; Soumaya Dbara (Journal of Hazardous Materials, 2024)

Deciphering the regulatory networks involved in mild and severe salt stress responses in the roots of wild grapevine Vitis vinifera spp. sylvestris - Samia Daldoul; Faouzia Hanzouli; Hatem Boubakri; Peter Nick; Ahmed Mliki; Mahmoud Gargouri (Protoplasma, 2024)

Enumeration of olive derived lignan, pinoresinol for activity against recent Omicron variant spike protein for structure-based drug design, DFT, molecular dynamics simulations, and MMGBSA studies - Samia S. Alkhalil; Shoruq E. Alosaimi; Manal E. Alosaimi; Zuhair M. Mohammedsaleh; Waleed Al Abdulmonem; Abdullah Saleh Alkhamiss; Ruqaih S. Alghsham; Abdullah S. M. Aljohani; Abdullah F. Shater; Fayez M. Saleh; Hailah M. Almohaimeed; Mona H. Soliman (Journal of Applied Genetics, 2024)

The Ornamental white marble use and reuse at the Ottoman palaces of Algiers’ Regency: New knowledge to a provenance study - Aicha Bibimoune; Samia Chergui; Mohamed Chérif Hamza; Walter Prochaska (Archaeological and Anthropological Sciences, 2024)

Removal of benzophenone-4 via chlorination and advanced oxidation processes in aqueous solution: kinetics, by-product identification, and mechanistic studies - Lama Santbay; Mounir Kassir; Rania Nassar; Samia Mokh; Mohamad Al Iskandarani; Ahmad Rifai (Environmental Science and Pollution Research, 2024)

Modulation of the Sirtuin-1 signaling pathway in doxorubicin-induced nephrotoxicity (synergistic amelioration by resveratrol and pirfenidone) - Samia Mahmoud Manawy; Eman Mohamed Faruk; Rabab Fawzy Hindawy; Mahmoud M. Hassan; Diaa M.G. Farrag; Mansour A.E. Bashar; Hanan Fouad; Rania Abubaker Bagabir; Dina Allam Abdelmaksoud Hassan; Ahmed Mohammed Zaazaa; Mohamed Ghazy Attia Hablas; K Mostafa Kamal (Tissue and Cell, 2024)

Land use and land cover mapping using Landsat-8 and Sentinel-2 data in Al Qunfudhah coast, western Saudi Arabia: A comparative study - Samia S. Hasan; Omar A. Alharbi; Amr S. Fahil (Regional Studies in Marine Science, 2024)

Biosecurity, health and disease management practices among the dairy farms in five districts of Bangladesh - Anica Bushra; Md. Rokon-Uz-Zaman; ASM Sadequr Rahman; Monika Akter Runa; Sadia Tasnuva; Samia Sharmin Peya; Mst. Sonia Parvin; Md. Taohidul Islam (Preventive Veterinary Medicine, 2024)

Low-lactose yoghurt production using β-galactosidase: An integrated study for the enzyme and its application - Walaa A. Abdel Wahab; Samia A. Ahmed; Adel M.M. Kholif; Salem Abd El Ghani; Hala R. Wehaidy (International Dairy Journal, 2024)

The potential protective and therapeutic effects of cannabidiol oil on experimental Leukemia induced by DMBA in male rats - Nabil A. Soliman; Samih I. El Dahmy; Tarek Khamis; Reham Sameh; Sara Mohamed Alashqar; Samia Hussein (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Rational design of multi-epitope-based vaccine by exploring all dengue virus serotypes proteome: an immunoinformatic approach - Ahad Amer Alsaiari; Mohammed Ageeli Hakami; Bader S. Alotaibi; Samia S. Alkhalil; Ali Hazazi; Nada Alkhorayef; Khurshid Jalal; Farzana Yasmin (Immunologic Research, 2024)

Effectiveness of cannabidiol (CBD) on histopathological changes and gene expression in hepatocellular carcinoma (HCC) model in male rats: the role of Hedgehog (Hh) signaling pathway - Samia Hussein; Nabil A. Soliman; Samih I. El Dahmy; Tarek Khamis; Reham Sameh; Fatma M. Mostafa (Histochemistry and Cell Biology, 2024)

Microorganism-mediated biodegradation for effective management and/or removal of micro-plastics from the environment: a comprehensive review - Hassan Zahid; Nimra Afzal; Muhammad Maaz Arif; Mahnoor Zahid; Samia Nawab; Malik Muhammad Qasim; Farhat Naseem Alvi; Sumbal Nazir; Ishrat Perveen; Naaz Abbas; Yasar Saleem; Sania Mazhar; et al. (Archives of Microbiology, 2024)

RNA based gene silencing modalities to control insect and fungal plant pests – Challenges and future prospects - Muhammad Waqas Choudry; Pashma Nawaz; Neelam Jahan; Rabia Riaz; Bilal Ahmed; Muhammad Hassan Raza; Zohaib Fayyaz; Kausar Malik; Samia Afzal (Physiological and Molecular Plant Pathology, 2024)

Influence of pesticide mixture on their heterogeneous atmospheric degradation by ozone and OH radicals - Boulos Samia; Loïc Della Puppa; Coraline Mattei; Amandine Durand; Sylvain Ravier; Etienne Quivet; Henri Wortham (Environmental Pollution, 2024)

Molecular prevalence of vector borne bacterial pathogens in the blood samples of wild rodent species trapped from Saudi Arabia - Abdul Ghafar; Samia Q. Alghamdi; Abdullah D. Alanazi; Syed Muhammad Zukhruf Qousain; Maryam Ijaz; Muhammad Naeem; Muhammad Ali; Hira Muqaddas; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Ultrastructural, Secondary Metabolite, and Antioxidant Modulation in Response to Salt-Affected Habitats Induced Oxidative Stress and Their Accumulation in Malva parviflora L. and Rumex dentatus L. - Amany M. Kazamel; Samia A. Haroun; Alshaymaa A. Noureldin; Ghada A. El-Sherbiny; Omer A. El-Shahaby; Mahmoud R. Sofy; Alaa F. AlBakry; Rasha M. E. Gamel (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress is a major abiotic factor that affects medicinal plant growth, performance, and secondary compounds. Malva parviflora L. and Rumex dentatus L. plants were collected from three habitats in the northeastern Nile Delta governorates of Damietta and El-Dakahlia. Conductivity (salinity) classified the habitats as mesophytic, moderately saline, and saline. Chemical and physical soil characteristics varied by habitat. Results show that M. parviflora L. and R. dentatus L. had high soluble sugars, total carbohydrates, electrolyte leakage, and proline in the saline habitat. In contrast, mesophytic habitats showed low content. In addition, R. dentatus L. had more antioxidant enzymes and elements in saline habitats than in mesophytic habitats. In saline habitats, M. parviflora L. and R. dentatus L. were characterized by more calcium and sodium increase than mesophytic habitats. Moreover, R. dentatus L. had more phenols, alkaloids, flavonoids, anthocyanin, and tannins under saline conditions than M. parviflora . Meanwhile, in the saline habitat, plant hormones, i.e., indole acetic acid and gibberellic acid, decreased significantly in both M. parviflora and R. dentatus than in the mesophytic habitat. Scanning Electron Microscopy (SEM) of the tested plants showed the highest stomatal frequency and area on the lower surface of mesophytic plant leaves compared to either its upper surface or both leaf surfaces in saline habitat. Hence, it can be concluded that R. dentatus plant can mitigate the negative effects of salinity by improving the qualitative and quantitative performance under salinity stress more than M. parviflora plant.

Glauconite facies developed sequentially in the Abu Tartur Plateau (Egypt) during the Late Cretaceous - Abdalla M. El Ayyat; Samia El-Helaly; Ezzat A. Ahmed; Mohamed A. Moneim; Mostafa R. Abukhadra (Euro-Mediterranean Journal for Environmental Integration, 2024)

Abundance and operating area by benthic trawl of Atlantic horse mackerel in the central Mediterranean - Samia Fezzani; Okbi Rjeibi; Mourad Cherif; Amira Saoudi; Kamel Zaara; Yassine Ben moumen; Othman Jarboui; Hechmi Missaoui; Sami Mili (Euro-Mediterranean Journal for Environmental Integration, 2024)

Evidence of an active role of resveratrol derivatives in the tolerance of wild grapevines (Vitis vinifera ssp. sylvestris) to salinity - Faouzia Hanzouli; Hassène Zemni; Mahmoud Gargouri; Hatem Boubakri; Ahmed Mliki; Simone Vincenzi; Samia Daldoul (Journal of Plant Research, 2024)

Comparison of the Scolicidal Activity of Two Leaves Extracts of Myrtus communis from Algeria Against Echinococcus granulosus Sensu Lato Protoscoleces - Meryem Benmarce; Assia Haif; M. Celina Elissondo; Samia Bouaziz; Assia Bentahar; AbdElkarim Laatamna (Acta Parasitologica, 2024)

Evaluation of acute toxicity of Scabiosa artropurperea var.maritima aqueous extracts in Swiss mice - Wijden Niama; Samia Ben Said; Christelle Rame; Mohamed Aroua; Mokhtar Mahouachi; Pascal Froment; Joëlle Dupont (Toxicon, 2024)

New insights into changing honey bee (Apis mellifera) immunity molecules pattern and fatty acid esters, in responses to Ascosphaera apis infection - Manar M.M. Elhoseny; Samia E. El-Didamony; Wedad A.A. Atwa; Azza A. Althoqapy; Hend I.A. Gouda (Journal of Invertebrate Pathology, 2024)

Recent progress in practical applications of a potential carotenoid astaxanthin in aquaculture industry: a review - Samia Elbahnaswy; Gehad E. Elshopakey (Fish Physiology and Biochemistry, 2024)
Astaxanthin is the main natural C40 carotenoid used worldwide in the aquaculture industry. It normally occurs in red yeast Phaffia rhodozyma and green alga Haematococcus pluvialis and a variety of aquatic sea creatures, such as trout, salmon, and shrimp. Numerous biological functions reported its antioxidant and anti-inflammatory activities since astaxanthin possesses the highest oxygen radical absorbance capacity (ORAC) and is considered to be over 500 more times effective than vitamin E and other carotenoids such as lutein and lycopene. Thus, synthetic and natural sources of astaxanthin have a commanding influence on industry trends, causing a wave in the world nutraceutical market of the encapsulated product. In vitro and in vivo studies have associated astaxanthin’s unique molecular features with various health benefits, including immunomodulatory, photoprotective, and antioxidant properties, providing its chemotherapeutic potential for improving stress tolerance, disease resistance, growth performance, survival, and improved egg quality in farmed fish and crustaceans without exhibiting any cytotoxic effects. Moreover, the most evident effect is the pigmentation merit, where astaxanthin is supplemented in formulated diets to ameliorate the variegation of aquatic species and eventually product quality. Hence, carotenoid astaxanthin could be used as a curative supplement for farmed fish, since it is regarded as an ecologically friendly functional feed additive in the aquaculture industry. In this review, the currently available scientific literature regarding the most significant benefits of astaxanthin is discussed, with a particular focus on potential mechanisms of action responsible for its biological activities.

Tunisian Eucalyptus essential oils: exploring their potential for biological applications - Sana Khedhri; Marwa Khammassi; Sonia Boukhris Bouhachem; Ylenia Pieracci; Guido Flamini; Samia Gargouri; Ismail Amri; Lamia Hamrouni (Plant Biosystems, 2024)

Occurrence of contaminants of emerging concern and pesticides and relative risk assessment in Tunisian groundwater - Farah Khezami; Olga Gómez-Navarro; Maria Vittoria Barbieri; Nouha Khiari; Anis Chkirbene; Serge Chiron; Samia Khadhar; Sandra Pérez (Science of The Total Environment, 2024)

Green synthesized silver nanoparticles: Characterization, phytostimulatory impacts, and degradation potential for organic pollutants - Ghania Abbas; Fozia Batool; Ambreen Ahmed; Shabana Wagi; Humaira Yasmeen Gondal; Farah Maqsood; Ehab A. Abdelrahman; Hafiza Komal Naeem; Samia Kanwal; Muhammad Mustaqeem; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Spatial distribution and pollution assessment of heavy metals in surface and bottom water along the eastern part of the Egyptian Mediterranean coast - Safaa Abdel Ghani; Samia Hamdona; Laila Shakweer; Abeer El Saharty (Marine Pollution Bulletin, 2023)

Shoreline change rate detection applying the DSAS technique on low and medium resolution data: Case study along Ash Shu’aybah-Al Mujayrimah coastal Area of the Eastern Red Sea, Saudi Arabia - Omar A. Alharbi; Samia S. Hasan; Amr S. Fahil; Ammar Mannaa; Nelson Rangel-Buitrago; Abdullah F. Alqurashi (Regional Studies in Marine Science, 2023)

Analyzing the electrochemical reduction of CO and CO2 as reactants to C1 and C2 products on copper-based flow-through gas diffusion electrodes - Azeem Mustafa; Bachirou Guene Lougou; Yong Shuai; Zhijiang Wang; Haseeb-ur-Rehman; Samia Razzaq; Wei Wang; Ruming Pan; Fanghua Li; Lei Han (Journal of Environmental Chemical Engineering, 2023)

A curious case of monsoon low frequency reverberations from the mighty Himalayas - Mohammad Salam; Imran Khan; Samia Faiz Gurmani; Amir Sultan; Talat Iqbal (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

The relationship between DNA methyltransferase 3B (DNMT3B) and miR 124-3pa expressions in bladder cancer tissues - Mohammed S. Fawzy; Abdel Rahman M. El Faiomy; Ansam M. Z. El Desoky; Samia Hussein (Molecular Biology Reports, 2023)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

A sustainable green–blue revolution in Pakistan: a new perspective from quantile regression analysis - Samia Zahra; Syed Ale Raza Shah; Ramez Abubakr Badeeb (Environment, Development and Sustainability, 2023)

Dietary inclusion of Pediococcus acidilactici probiotic promoted the growth indices, hemato-biochemical indices, enzymatic profile, intestinal and liver histomorphology, and resistance of Nile Tilapia against Aspergillus flavus - Moaheda E.H. Eissa; Fatima S. Alaryani; Samia Elbahnaswy; Marwa S. Khattab; Amal Elfeky; Khaled Youssef AbouelFadl; El-Sayed Hemdan Eissa; Ragaa A. Ahmed; Hien Van Doan; Ehab El-Haroun (Animal Feed Science and Technology, 2023)

Metabolic profiling reveals fumaric acid and GABA as possible markers of Colletotrichum lupini infection of white lupin - Sofia Bitarishvili; Samia Samad; Stepan Boldyrev; Cécile Ben; Polina Volkova; Alexey Shavarda; Mikhail Lukashevich; Ekaterina Bondarenko (Physiological and Molecular Plant Pathology, 2023)

Mitigating seawater intrusion in coastal aquifers: Novel approach with treated wastewater injection and groundwater circulation - Samia Saad; Akbar A. Javadi; Hany F. Abd-Elhamid; Raziyeh Farmani (Journal of Hydrology, 2023)

Adsorption potential of orange rind–based nanosorbents for the removal of cadmium(II) and chromium(VI) from contaminated water - Samia Kanwal; Hafiza Komal Naeem; Fozia Batool; Awais Mirza; Ehab A. Abdelrahman; Gulnaz Sharif; Farah Maqsood; Muhammad Mustaqeem; Allah Ditta (Environmental Science and Pollution Research, 2023)

A Natural Biomass-Sediment as a Hybrid Organic-Mineral Sorbent for the Removal of Zinc in Aqueous Systems - Nouha Khiari; Ali Sdiri; Hajer Chemingui; Samia Khadhar (Water, Air, & Soil Pollution, 2023)

Promoting the growth of Sulla flexuosa L. by endophytic root nodule bacteria authors and affiliations - Samia Hamane; Anass El yemlahi; Mounir Hassani Zerrouk; Ouiam El Galiou; Amin Laglaoui; Mohammed Bakkali; Abdelhay Arakrak (World Journal of Microbiology and Biotechnology, 2023)

Differential effects of methanolic extracts of clove, ginger, garlic and eucalyptus essential oils on anti-parasitic partitivities of G. lamblia and E. histolytica: an in vitro study - Qwait AlGabbani; Abdullah F. Shater; Rasha Assiri; Ghadah Asaad Assiri; Alaa Asaad Assiri; Raafat T. M. Makhlof; Mohammad A. Alsaad; Samia S. Alkhalil; Rawabi Mohamed Almuhimed; Hailah M. Almohaimeed; Hayfa AlDughaishem (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Productivity and Quality Variations in Sugar Beet Induced by Soil Application of K-Humate and Foliar Application of Biostimulants Under Salinity Condition - M. A. A. Nassar; Samia S. El-Magharby; Nada S. Ibrahim; Essam E. Kandil; Nader R. Abdelsalam (Journal of Soil Science and Plant Nutrition, 2023)
Abiotic stresses are the most major limitation to crop production, causing yield losses up to 50%, and consider the major challenges for production of crops. Thus, an experiment was conducted to determine how sugar beet would respond to soil application of K-humate rates and foliar application of biostimulants under salt stress. Split-plot design in three replicates was used in both seasons, where K-humate rates fertigation (control, 12, and 24 kg ha −1 ) allocated in the main plots, and different foliar application of BS arranged within the subplot (i.e., (1) water spray, (2) salicylic acid (SA) at the rate of 100 mg L −1 , (3) fulvic acid (FA) at the rate of 1.2 kg ha −1 , (4) hydroxyproline (HP) 1000 mg L −1 , (5) SA at 100 mg L −1 + FA at 1.2 kg ha −1 , (6) SA at 100 mg/L + HP at 1000 mg L −1 , (7) FA at 1.2 kg ha −1 + HP at 1000 mg L −1 , (8) SA 100 mg L −1 + FA 1.2 kg ha −1 + HP 1000 mg L −1 ) in the two seasons. The finding results revealed that soil application of K-humate, foliar application of BS, and their interaction significantly affected yield, growth, and quality characteristics of sugar beet under soil salinity, furthermore with soil application of K-humate at the rate of 24 kg ha −1 with foliar spray of FA + HP recorded the highest of growth traits, top, root, sucrose %, sugar yields/ha −1 and the lowest values of Na content in the juice and quality of sugar beet under the study conditions, Alexandria, Egypt.

Growth and Metabolic Response of Glycine max to the Plant Growth-Promoting Enterobacter Delta PSK and Bradyrhizobium japonicum Under Salinity Stress - Mona S. Agha; Samia A. Haroun; Mohamed A. Abbas; Mahmoud R. Sofy; Amr M. Mowafy (Journal of Plant Growth Regulation, 2023)
This study was designed to test the ability of some plant growth-promoting bacteria to adverse the effects of salinity on soybean growth. The effect of Bacillus MAP3 and Enterobacter Delta PSK, along with Bradyrhizobium japonicum was studied on soybean at two levels of NaCl salinization (50 and 100 mM). The physical growth parameters of bacterized soybean (21 days old), particularly plants co-inoculated with Bradyrhizobium japonicum + Enterobacter Delta PSK, were significantly enhanced compared to control plants. The shoot length, leaf area, root length, and chlorophyll a content increased by 49.58%, 78.58%, 20.19%, and 57.35%, respectively, indicating the promoting activity of this bacterial combination. After 19 days following the onset of salinity stress, the retarded growth parameters in controls improved significantly due to bacterial treatments, especially by Bradyrhizobium japonicum + Enterobacter DeltaPSK, which increased the values of all growth parameters significantly regardless of the salinity level. Additionally, electrolyte leakage, the amounts of malondialdehyde and hydrogen peroxide decreased considerably due to this combined bacterial treatment . Overall, the combination treatment of Enterobacter Delta PSK and the original symbiont B. japonicum enhanced soybean growth under salt stress, indicating the ability of Enterobacter Delta PSK to mitigate osmotic stress. The effect of this strain on soybean yield should be further evaluated to pave the way for its use as a biofertilizer along with B. japonicum, especially under salt stress.

Diurnal variation in the atmospheric electric field with respect to aerosol and meteorological parameters at Islamabad, Pakistan - Samia Faiz Gurmani; Nabeel Ahmad; Tabinda Shamsher; Tariq Mehmood; Waqas Khalid; Asghari Maqsood; Talat Iqbal; Muhammad Ali Shah (Journal of Earth System Science, 2023)

Exergoeconomic evaluation of a novel multigeneration process using solar driven Kalina cycle integrated with gas turbine cycle, double-effect absorption chiller, and liquefied natural gas cold energy recovery - Sun Yi; Azher M. Abed; Ahmed Deifalla; M. Riaz; Theyab R. Alsenani; Samia Elattar; Chun Yulei; Saleh Al Sulaie (Process Safety and Environmental Protection, 2023)

Alpha-amylase and alphaglucosidase inhibitory properties, beta-galactosidase activity, and probiotic potential of lactic acid bacteria and bifidobacteria from Apis mellifera intermissa and its products - Houda Ben-Miled; Marie-Odile Benoit-Biancamano; Kamel Ben-Mahrez; Samia Réjiba (World Journal of Microbiology and Biotechnology, 2023)

Effect of honey bee forage plants in Tunisia on diversity and antibacterial potential of lactic acid bacteria and bifidobacteria from Apis mellifera intermissa and its products - Houda Ben-Miled; Nabil Semmar; Miguel Sautié Castellanos; Kamel Ben-Mahrez; Marie-Odile Benoit-Biancamano; Samia Réjiba (Archives of Microbiology, 2023)

Bacterial Co-Infection as a Potential Threat to Farmed Flathead Grey Mullet (Mugil cephalus): Phenotypic and Molecular Diagnosis, Histopathology, Immunity Response, and In Vitro Antibacterial Evaluation - Samia Elbahnaswy; Gehad E. Elshopakey; Medhat S. Shakweer; Elsayed A. A. Eldessouki; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Mai A. M. El-Son (Fishes, 2023)
Vibrio alginolyticus, Vibrio chlorea, and Enterococcus cloacae were the main bacterial pathogens investigated during recurrent episodes of mortalities among farmed flathead grey mullet (Mugil cephalus) in the Bahar El-Baqar area, Sharqia governorate, Egypt, during the summer season in 2021. Nevertheless, the contamination of water with heavy metals was evaluated. In this study, a total number of sixty moribund and freshly dead Mugil cephalus were examined clinically and upon post-mortem. Then, the bacterial isolates were subjected to bacteriological phenotypic examination, 16S rRNA gene sequencing, and antibiotic sensitivity testing. Histopathological screening and the immunity response of naturally infected M. cephalus were also implemented. In areas where bacterial strains were recovered in a high percentage, water contamination with Cu, Fe, and Ni was higher than the permissible limit. The results showed a high similarity (99–100%) to Vibrio and E. cloacae strains using phylogenetic analysis of 16S rRNA. Most isolates exhibited sensitivity to florfenicol, ciprofloxacin, and norfloxacin, while they were resistant to erythromycin and amoxicillin. Hemorrhage, oedema, hemosiderosis, and melanomacrophage activation in most affected tissues of infected M. cephalus were detected by light microscopy. Nevertheless, higher levels of AST and ALT, as well as serum inflammatory markers, CRP, and lysozyme activity, were shown in infected fish. There were higher MDA levels, along with a reduction of GSH, SOD, and catalase, in the gills and brain of infected M. cephalus, compared to the control fish. Our obtained data confirmed the high prevalence of Vibrio serovars and E. cloacae in infected grey mullets, describing their histopathological alterations, higher inflammatory response, and oxidative stress impact. These results could be useful indicators for understanding the pathogenesis of these pathogens in correlation with water parameter deterioration. Thus, the emergence of Vibrio and E. cloacae species in this study threatens the brackish water aquaculture industry in Egypt and poses a public health concern.

Quantitative characterizations of mOR-EG activated by vanilla odorants using advanced statistical physics modeling - Ismahene Ben Khemis; Fatma Aouaini; Lamies Bukhari; Samia Nasr; Abdelmottaleb Ben Lamine (Food Chemistry, 2023)

Seronegative acute encephalitis following COVID-19 vaccines: a case series of an overlooked diagnosis with literature review - Khadija Mansour; Zohra Chadli; Ichrak Ghachem; Nadia Ben Fredj; Haifa Ben Romdhane; Najah Ben Fadhel; Naceurs Boughatas; Karim Aouam; Amel Chaabane; Samia Younes (European Journal of Clinical Pharmacology, 2023)

A comprehensive investigation of a water and energy-based waste integrated system: Techno-eco-environmental-sustainability aspects - Yun Bai; Haitao Lin; Azher M. Abed; Ahmed Deifalla; Theyab R Alsenani; Samia Elattar (Chemosphere, 2023)

Clinical, epidemiological and faunistic characterization of scorpionism in Azilal, Central High Atlas (Morocco) - Abdessamad Elmourid; Samia Boussaa; Moulay Abdelmounaim El Hidan; Btissam Bouimeja; Oulaid Touloun (Toxicon, 2023)

Carbon-based materials for CO2 capture: Their production, modification and performance - Ali Zaker; Samia ben Hammouda; Jie Sun; Xiaolei Wang; Xia Li; Zhi Chen (Journal of Environmental Chemical Engineering, 2023)

Substitution of soyabean meal by faba bean improves body weight, sperm production and testosterone concentration in mature Queue Fine de l’Ouest rams - Samia Ben Said; Rima Gmati; Mohamed Aroua; Narjess Lassoued; Mourad Rekik; Mokhtar Mahouachi (Tropical Animal Health and Production, 2023)

The benefits of regular aerobic exercise training on cerebrovascular function and cognition in older adults - Edward S. Bliss; Samia M. Biki; Rachel H. X. Wong; Peter R. C. Howe; Dean E. Mills (European Journal of Applied Physiology, 2023)
We compared the differences in cerebrovascular and cognitive function between 13 aerobic exercise trained, older adults and 13 age-, height- and sex-matched sedentary, untrained controls. We determined whether other measures accounted for differences in cerebrovascular and cognitive function between these groups and examined the associations between these functions. Participants undertook anthropometric, mood, cardiovascular, exercise performance, strength, cerebrovascular, and cognitive measurements, and a blood collection. Transcranial Doppler ultrasonography determined cerebrovascular responsiveness (CVR) to hypercapnia and cognitive stimuli. The trained group had a higher CVR to hypercapnia (80.3 ± 7.2 vs 35.1 ± 6.7%, P < 0.001), CVR to cognitive stimuli (30.1 ± 2.9 vs 17.8 ± 1.4%, P = 0.001) and total composite cognitive score (117 ± 2 vs 98 ± 4, P < 0.001) than the controls. These parameters no longer remained statistically different between the groups following adjustments for covariates. There were positive correlations between the total composite cognitive score and CVR to hypercapnia ( r = 0.474, P = 0.014) and CVR to cognitive stimuli ( r = 0.685, P < 0.001). We observed a relationship between cerebrovascular and cognitive function in older adults and an interaction between regular lifelong aerobic exercise training and cardiometabolic factors that may directly influence these functions.

The impact of stem and root fungal diseases on grain yield and quality of bread wheat under wheat mono-cropping systems in Mediterranean subhumid conditions of Tunisia - Asma Bouatrous; Samia Gargouri; Amir Souissi; Kalthoum Harbaoui; Hatem Cheikh M’hamed; Mohamed Salah Gharbi; Mohamed Annabi (European Journal of Plant Pathology, 2023)

Distinct inter and intrapopulation variation in the otolith shape and size of Mullus barbatus (Actinopterygii: Mullidae) from the Bizerte and Ghar El Melh lagoons in Tunisian waters - Samia Ben Mohamed; Marwa Mejri; Abdellah Chalh; Adel A. Basyouny Shahin; Jean-Pierre Quignard; Monia Trabelsi; Abderraouf Ben Faleh (Marine Biology Research, 2023)

Dehydration study of apple slices by a non-thermal process - Khouloud KRAIEM; Souhir ABDELMOUMEN; Samia BEN-ALI (Environmental Science and Pollution Research, 2023)

Economic, environmental and multi objective optimization of a clean tri-generation system based co-firing of natural gas and biomass: An emergy evaluation - Hao-Feng Lin; Ibrahim B. Mansir; Hawzhen Fateh M. Ameen; A. CHERIF; Abdulkareem Abdulwahab; Mahidzal Dahari; Haitao Lin; Ayman A. Aly; Samia Nasr (Process Safety and Environmental Protection, 2023)

Efficient uncertainty quantification for seawater intrusion prediction using Optimized sampling and Null Space Monte Carlo method - Samia Saad; Akbar A. Javadi; Raziyeh Farmani; Mohsen Sherif (Journal of Hydrology, 2023)

A framework for sustainability evaluation and improvement of radiology service - Zoubida Benmamoun; Widad Fethallah; Samia Bouazza; Ahmad Abu Abdo; Driss Serrou; Houda Benchekroun (Journal of Cleaner Production, 2023)

CO2 storage in porous media unsteady thermosolutal natural convection -Application in deep saline aquifer reservoirs - Souhail Bouzgarrou; Mehdi Akermi; Samia Nasr; Fatma Aouaini; Afzal Husain Khan; Khalifa Slimi; Nadeem A. Khan; Sasan Zahmatkesh (International Journal of Greenhouse Gas Control, 2023)

High Prevalence of blaNDM Among Carbapenem Non-Susceptible Klebsiella pneumoniae in a Tunisian Hospital First Report of blaNDM-9, blaKPC-20, and blaKPC-26 Genes - Emna Zouaoui; Paola Sandra Mercuri; Anis Radaoui; Naouel Ben Salah; Moreno Galleni; Kamel Ben-Mahrez; Samia Réjiba (Current Microbiology, 2023)

Evaluation of Branched-Chain Amino Acids in Children with Autism Spectrum Disorder and Epilepsy - Nagwa A. Meguid; Heba S. Hashem; Mohamed H. Ghanem; Samia A. Helal; Yuliya Semenova; Saher Hashem; Adel Hashish; Salvatore Chirumbolo; Ahmed M. Elwan; Geir Bjørklund (Molecular Neurobiology, 2023)

The effects of financial development and technological progress on environmental sustainability: novel evidence from Asian countries - Samia Nasreen; Faryal Ishtiaq Khan; Xuan-Hoa Nghiem (Environmental Science and Pollution Research, 2023)

Comparison of Immune Response of Litopenaeus vannamei Shrimp Naturally Infected with Vibrio Species, and after Being Fed with Florfenicol - Medhat S. Shakweer; Gehad E. Elshopakey; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon John Davies; Samia Elbahnaswy (Fishes, 2023)
The outbreaks caused by Vibrio spp. are a notable threat to the potential growth of the economy of penaeid culture, which is still controlled by the administration of antibiotics. At first, the infected group was subjected to phenotypic bacteriological examination with subsequent molecular identification via 16S rRNA gene sequencing, which confirmed four strains of Vibrio spp., V. atlanticus, V. natriegens, V. alginolyticus, and V. harveyi, from moribund-infected shrimp during mortality events in an Egyptian hatchery. To better understand the defense mechanism of the most effective antibiotic against Vibrio strains, the immune responses were compared and evaluated in infected Litopenaeus vannamei broodstock after being fed 5 mg kg−1 of florfenicol antibiotic, which was first determined through in vitro antibiogram tests. Therefore, our study aimed to determine the immune response of L. vannamei during Vibrio spp. infection in Egyptian hatcheries and after antibiotic medication. The parameters assessed were the total and differential hemocyte count (THC), granular cells (GC), semi-granular cells (SGC), and hyaline cells (HC). As well as the metabolic and immune enzymes: alanine aminotransferases (ALT), aspartate aminotransferases (AST), alkaline phosphatase (ALP), acid phosphatase (ACP), and lysozyme activity; an antioxidant index, such as superoxide dismutase (SOD) and glutathione (GSH); a phagocytic assay; changes in reactive oxygen species (ROS); and bactericidal activity in the hemolymph of the control, infected, and treated groups. Further evaluation of the mRNA expression levels of the prophenoloxidase (LvproPO), toll-like receptor 1 (LvToll1), and haemocyanin (LvHc) genes were performed in the hepatopancreas of the same groups. A significant drop in the THC, GC, SGC, and HC counts, as well as lysozyme and bactericidal activities, phagocytic assay, ROS, SOD, and GSH index, were represented in infected shrimp compared to control shrimp; however, a marked increase in the activity of ALT, AST, ALP, and ACP was observed. These activities were significantly restored in the treated shrimp compared to the infected shrimp. Nevertheless, no significant changes were noted in the transcriptional levels of the LvproPO and LvToll1 genes in the treated shrimp when compared to the infected shrimp; however, a significant suppression of the LvHc gene was noted. Our study aimed to determine the immune response of L. vannamei during Vibrio spp. infection in Egyptian hatcheries and after antibiotic medication. We concluded that florfenicol in medicated feed could be effective in controlling vibriosis and ameliorating the immune response of shrimp.

Innovation dynamics in the natural resource curse hypothesis: A new perspective from BRICS countries - Ramez Abubakr Badeeb; Kenneth R. Szulczyk; Samia Zahra; Tanusree Chakravarty Mukherjee (Resources Policy, 2023)

A novel trigeneration model using landfill gas upgrading process and waste heat recovery: Application of methanol, desalinated water, and oxygen production - Tao Hai; Haitao Lin; Mahmood Shaker Albdeiri; Theyab R. Alsenani; Samia Elattar; Ahmed M. Abed; Ruicheng Tian (Journal of Cleaner Production, 2023)

Development of more potent anti-microbial drugs from extracts of five medicinal plants resistant to S. aureus in human fluids: an ex vivo and in vivo analysis - Rasha Assiri; Nada Abdullah Alharbi; Thamir Saad Alsaeed; Waleed Al Abdulmonem; Almonther Abdullah Hershan; Rana Abdullah Alghamdi; Abdullah S. M. Aljohani; Nada Alkhorayef; Ahmad Almatroudi; Khaled S. Allemailem; Samia S. Alkhalil; Ameena A. AL-surhanee; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Laser Enhanced Combinatorial Chemo-photothermal Therapy of Green Synthesis Gold Nanoparticles Loaded with 6Mercaptopurine on Breast Cancer Model - Amna H. Faid; Samia A. Shouman; Nadia A. Thabet; Yehia A. Badr; Mahmoud A. Sliem (Journal of Pharmaceutical Innovation, 2023)
Purpose We tend to evaluated a method for loading 6Mercaptopurine (6MP) on green synthesized hybrid chitosan gold nanoparticles (AuNPs) forming 6MP-AuNPs nanocomposite for the first time in combinatorial chemo-photothermal therapy. Methods The AuNPs were synthesized using chitosan as a reducing and capping agent. Different concentrations of 6MP were mixed AuNPs. Cells were incubated with 6MP and 6MP loaded AuNPs for 48 h and then exposed to laser. Results AuNPs and 6MP-AuNPs nanocomposite have small sizes of 18 ± 4 and 25 ± 5 nm and exhibit high stability with Zeta potential of 55.9 ± 6.3 and 57 ± 4 mV. 6MP-AuNPs nanocomposite irradiated with Diode Pumped Solid State (DPSS) laser showed a maximum inhibition in cell viability reaching 63% at 1.25 µM. Conclusions A hybrid chitosan gold nanoparticle is a powerful anti-cancer drug carrier as well as photothermal agent in combinatorial chemo-photothermal therapy.

Ectopic expression of a grapevine alkaline α-galactosidase seed imbibition protein VvSIP enhanced salinity tolerance in transgenic tobacco plants - Anis Ben-Amar; Samia Daldoul; Dorsaf Allel; Thierry Wetzel; Ahmed Mliki (Functional & Integrative Genomics, 2023)

Detoxification of olive mill wastewater by adsorption on activated clay - Younes Dehmani; Soukaina Arif; Ikram Daou; Abdelaziz Ed-Dra; Samia El Oirdi; Hamou Moussout; Hassan Hajjaj; Fouzia Rhazi Filali; Sadik Abouarnadasse (Euro-Mediterranean Journal for Environmental Integration, 2023)

Allopathic potential of essential oil extracts on weeds germination and seedlings growth in sustainable agriculture: the phytochemical study of Tunisia’s two Melaleucaspecies - Sana Khedhri; Marwa Khammassi; Ismail Amri; Yassine Mabrouk; Mohsen Hanana; Samia Gargouri; Lamia Hamrouni (Vegetos, 2023)

Preservation and sanitary status of Algerian grapevine germplasm: management and improvement - Samia Khouni; Ziane Laiadi; Nadia Bertazzon; Elisa Angelini; Daniele Migliaro (South African Journal of Botany, 2023)

Towards a sustainable, and economic production future: Proposing a new process for methanol production based on renewable hydrogen - Haoran Wei; Chenqing Su; Jie Dai; Mahmood Shaker Albdeiri; Theyab R. Alsenani; Samia Elattar; Ahmed M. Abed; Yinhai Hua (Journal of Cleaner Production, 2023)

Activated carbon derived from Dodonaea Viscosa into beads of calcium-alginate for the sorption of methylene blue (MB): Kinetics, equilibrium and thermodynamics - Asim Yaqub; Samia Misbah Syed; Huma Ajab; Muhammad Zia Ul Haq (Journal of Environmental Management, 2023)

Towards comprehensive identification of pesticide degradation products following thermal processing below and above 120 °C: A review - Florian Dubocq; Pierre L'Yvonnet; Eleni Chatzidimitriou; Samia Mahouche-Chergui; Xavier Sarda; Gaëlle Vial; Arnaud Duboisset; Benjamin Carbonnier; Julien Parinet (Food Chemistry, 2023)

Potential candidates from marine and terrestrial resources targeting mitochondrial inhibition: Insights from the molecular approach - Saikat Mitra; Abdur Rauf; Hriday Sutradhar; Samia Sadaf; Md. Jamal Hossain; Mahfuza Afroz Soma; Talha Bin Emran; Bashir Ahmad; Abdullah S.M. Aljohani; Waleed Al Abdulmonem; Muthu Thiruvengadam (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Potential Probiotic Lactic Acid Bacteria with Anti-Penicillium expansum Activity from Different Species of Tunisian Edible Snails - Ghada Rabaoui; Fernando Sánchez-Juanes; Mohamed Tebini; Karim Naghmouchi; Juan Luis Muñoz Bellido; Kamel Ben-Mahrez; Samia Réjiba (Probiotics and Antimicrobial Proteins, 2023)

Incidence and risk factors of SARS-CoV-2 infection among workers in a public health laboratory in Tunisia - Ghassen Kharroubi; Ines Cherif; Wissem Ghawar; Nawel Dhaouadi; Rihab Yazidi; Sana Chaabane; Mohamed Ali Snoussi; Sadok Salem; Wafa Ben Hammouda; Sonia Ben Hammouda; Adel Gharbi; Nabil Bel Haj Hmida; et al. (Archives of Virology, 2023)

Identification of cuticle and midgut fungal microflora of phlebotomine sandflies collected in Tunisia - Samia Layouni; Latifa Remadi; Raja Chaâbane-Banaoues; Najoua Haouas; Hamouda Babba (Archives of Microbiology, 2023)

Probiotic properties and safety aspect of three antifungal lactic acid bacteria strains isolated from wheat and camel milk - Tarik Lakhlifi; Samia El oirdi; Itto Maroui; Rachid Zouhair; Abdelhaq Belhaj (Biologia, 2023)

Rock physics analysis from predicted Poisson's ratio using RVFL based on Wild Geese Algorithm in scarab gas field in WDDM concession, Egypt - Muhammad Nabih; Ashraf Ghoneimi; Ahmed Bakry; Samia Allaoua Chelloug; Mohammed Azmi Al-Betar; Mohamed Abd Elaziz (Marine and Petroleum Geology, 2023)

Topographic evidence of long wavelength active folding in the New Madrid seismic zone, intraplate North America - Samia Noor; Randel Tom Cox; Robert Smalley; Md Rizwanul Hasan (Geomorphology, 2023)

Pathogenic parasites in vegetables in the Middle East and North Africa: Occurrence of Ascaris eggs and Giardia cysts, and epidemiological implications - Omar Amahmid; Youssef El Guamri; Youness Rakibi; Saadia Ouizat; Mohamed Yazidi; Bouchra Razoki; Khadija Kaid Rassou; Hanane Achaq; Safia Basla; Mohamed Amine Zerdeb; Meriyam El Omari; Oulaid Touloun; et al. (Food Control, 2023)

Development and evaluation of clove and cinnamon oil-based nanoemulsions against adult fleas (Xenopsylla cheopis) - Marwa E. Hassan; Samia M.M. Mohafrash; Micheal W. Mikhail; Abdel-Tawab H. Mossa (Biocatalysis and Agricultural Biotechnology, 2023)

Antifungal and antibiofilm activities of bee venom loaded on chitosan nanoparticles: a novel approach for combating fungal human pathogens - Samia E. El-Didamony; Mohamed H. Kalaba; Esmail M. El-Fakharany; Mahmoud H. Sultan; Mohamed H. Sharaf (World Journal of Microbiology and Biotechnology, 2022)
The prevalence of opportunistic human fungal pathogens is increasing worldwide, and antimicrobial resistance is one of the greatest medical challenges the world faces. Therefore, this study aimed to develop a novel agent to control fungal pathogens. The honeybee products (honey, royal jelly, propolis, bee bread, and bee venom) were screened against unicellular fungal (UCF) pathogens ( Cryptococcus neoformans , Kodamaea ohmeri , and Candida albicans ) and the bee venom was only exhibited an inhibitory effect against them. The protein contents of crude bee venom were separated using the gel filtration technique into eight fractions which were visualized on sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) to confirm the presence of five bands with molecular weights of 65, 43, 21, 15, and 3 KDa. Bee venom (BV) of Apis mellifera loaded chitosan nanoparticles were prepared by the ionotropic gelation method. The encapsulation efficiency%, average size, zeta potentials, and surface appearance by Transmission electron microscope (TEM) were evaluated for the prepared nanoparticles. The minimum inhibitory concentration (MIC) of crude BV and BV loaded chitosan nanoparticles (BV-CNPs) was evaluated against the offer mentioned UCF where the MIC values of crude BV were 6.25, 3.12 & 6.25 while MIC values in the case of BV-CNPs were decreased to 3.12, 3.12 & 1.56 mg/ml against C. neoformans , K. ohmeri and C. albicans , respectively. Also, the results showed that BV-CNPs suppressed the biofilm formation as well as yeast to hyphal transition formed by the examined UCF. These results revealed that BV-CNPs are a promising natural compound for fungal pathogens treatment. Graphical abstract

Implication of apoptosis and oxidative stress in mitigation of ivermectin long-term hazards by zinc nanoparticles in male rabbits - Set A. El-Shobokshy; Magda I. Abo-Samaha; Ferial M. Sahwan; Samia M. Abd El-Rheem; Mohamed Emam; Asmaa F. Khafaga (Environmental Science and Pollution Research, 2022)
Ivermectin is the medication of choice for treating human onchocerciasis and is used in veterinary medicine to treat a variety of ectoparasites and endoparasites. This study was designed to investigate the effects of zinc nanoparticles (ZnNPs) on the fertility of male rabbits exposed to experimental ivermectin (IVM) intoxication. A total of 72 mature male rabbits were equally divided into 4 groups ( n = 18). The first group (CTR) served as control; the second group (IVM) received subcutaneous injection of IVM (0.2 mg/kg body weight); the third group (ZnNPs) fed on zinc nanoparticles (60 mg/kg diet); and the fourth group (ZnNPs + IVM) were administered IVM and zinc nanoparticles at the same doses. The experiment lasted for 9 weeks. Results revealed that IVM-intoxicated rabbits showed impaired growth performance parameters, including body weight, total body weight gain (TBWG), total feed intake (TFI), and feed conversion ratio (FCR). Moreover, carcass characteristic and fertility parameters (including semen quality parameters and testosterone levels) were also impaired after IVM administration. Additionally, testicular malondialdehyde (MDA) and antioxidant (reduced glutathione, superoxide dismutase, catalase) levels as well as the histopathology and immunohistochemical expression of caspase 3 and PCNA in the testes and epididymis were detrimentally affected. On the contrary, ZnNP administration efficiently improved most of these parameters in IVM-intoxicated rabbits. In conclusion, ZnNPs exhibited promising ability for improving the growth and fertility status of rabbits and reducing the deleterious effects of IVM possibly through the suppression of apoptotic and oxidative pathways. Graphical Abstract

Synthesis, theoretical investigations and biological evaluation of ibuprofen drug hybrids - Adina Tatheer; Shahzad Murtaza; Naghmana Kausar; Ataf Ali Altaf; Samia Kausar; Safeer Ahmed; Shabbir Muhammad; Amjad Hussain (Medicinal Chemistry Research, 2022)

A plant-type L-asparaginase from Pyrobaculum calidifontis undergoes temperature dependent autocleavage - Muhammad Sajed; Samia Falak; Majida Atta Muhammad; Nasir Ahmad; Naeem Rashid (Biologia, 2022)

LC/MS-MS Analyses and in vitro anticancer activity of Tourneuxia variifolia extracts - Sara Zerrouki; Samia Mezhoud; Mustafa Abdullah Yilmaz; Ayse Sahin Yaglioglu; Derya Bakir; Ibrahim Demirtas; Ratiba Mekkiou (Natural Product Research, 2022)

Unveiling biogeographical patterns in the worldwide distributed Ceratitis capitata (medfly) using population genomics and microbiome composition - María Belén Arias; Katherine Hartle‐Mougiou; Sergi Taboada; Alfried P. Vogler; Ana Riesgo; Samia Elfekih (Molecular Ecology, 2022)
Invasive species are among the most important, growing threats to food security and agricultural systems. The Mediterranean medfly, Ceratitis capitata , is one of the most damaging representatives of a group of rapidly expanding species in the family Tephritidae, due to their wide host range and high invasiveness potential. Here, we used restriction site‐associated DNA sequencing (RADseq) to investigate the population genomic structure and phylogeographical history of medflies collected from six sampling sites, including Africa (South Africa), the Mediterranean (Spain, Greece), Latin America (Guatemala, Brazil) and Australia. A total of 1907 single nucleotide polymorphisms (SNPs) were used to identify two genetic clusters separating native and introduced ranges, consistent with previous findings. In the introduced range, all individuals were assigned to one genetic cluster except for those in Brazil, which showed introgression of an additional genetic cluster that also appeared in South Africa, and which could not be previously identified using microsatellite markers. Moreover, we assessed the microbial composition variations in medfly populations from selected sampling sites using amplicon sequencing of the 16S ribosomal RNA (V4 region). Microbiome composition and structure were highly similar across geographical regions and host plants, and only the Brazilian specimens showed increased diversity levels and a unique composition of its microbiome compared to other sampling sites. The unique SNP patterns and microbiome features in the Brazilian specimens could point to a direct migration route from Africa with subsequent adaptation of the microbiota to the specific conditions present in Brazil. These findings significantly improve our understanding of the evolutionary history of the global medfly invasions and their adaptation to newly colonized environments.

Role of financial inclusion and export diversification in determining green growth: evidence from SAARC economies - Ramsha Saleem; Samia Nasreen; Sidrah Azam (Environmental Science and Pollution Research, 2022)

The role of environmental transformational leadership in employees’ influencing organizational citizenship behavior for environment well-being: a survey data analysis - Muhammad Mansoor Asghar; Syed Anees Haider Zaidi; Zahoor Ahmed; Samia Khalid; Muntasir Murshed; Haider Mahmood; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

The impact of fiscal decentralization, green energy, and economic policy uncertainty on sustainable environment: a new perspective from ecological footprint in five OECD countries - Samia Zahra; Ramez Abubakr Badeeb (Environmental Science and Pollution Research, 2022)

Triggering mechanisms of Gayari avalanche, Pakistan - Bilal Saif; Mohammad Tahir; Amir Sultan; Muhammad Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah; Samia Gurmani (Natural Hazards, 2022)

Molecular taxonomical identification and phylogenetic relationships of some marine dominant algal species during red tide and harmful algal blooms along Egyptian coasts in the Alexandria region - Mona H. El-Hadary; Hosam E. Elsaied; Nehma M. Khalil; Samia K. Mikhail (Environmental Science and Pollution Research, 2022)
Harmful algal blooms (HABs) threaten the aquatic ecosystems due to either poisonous effects on living organisms or oxygen-consuming. So HABs’ accurate identification, including red tide, is crucial. This study aimed to molecular identification of dominant species during tide period in nine stations along Alexandria region at Egyptian costs during one year. Samples were collected weekly before water discoloration but daily during red tide intensive growth from both 50 cm below the surface and 3 m depth over the bottom from the water surface. The red tide detection was highly from early August to half of September, since its highest peak with a maximum frequency inside the Eastern Harbor. The examined cultures samples isolated during red tide had four dominant species. Peroxidase profile showed an expression pattern of three loci (Px1, Px2, and Px3) in most species. The Px2 was the only heterozygous locus among the three loci in all species. Protein profiling showed that 17 bands out of 65 were specific to the species. The phylogenetic relationships derived from profiles of protein and 18S rRNA gene operon sequences for the four isolated species were mostly similar. We identified the four dominant HABs species as Aplanochytrium sp., Chlamydomonas sp., Cryptophyceae sp., and Psammodictyon sp. based on their 18S rRNA sequences and deposited them at DDBJ/EMBL/GenBank database. Aplanochytrium sp. is recorded as a red tide causative species for the first time in the screened region despite belonging to the defunct fungi.

RETRACTED ARTICLE: Alleviation of nicotine-induced reproductive disorder, clastogenicity, and histopathological alterations by fenugreek saponin bulk and nanoparticles in male rats - Karima A. Hamed; Samia A. El-Fiky; Azza M. Gawish; Wagdy K. B. Khalil; Hanan R. H. Mohamed (Environmental Science and Pollution Research, 2022)
Nicotine is the most abundant ingredient in cigarette smoking and has serious side effects on the lung, heart, reproductive system, and many other human organs. Saponins extracted from many plants exhibit multiple biological actions such as anti-cancer effects. Therefore, the possible protective effect of fenugreek saponin (FS) and nanofenugreek saponin (NFS) against nicotine-induced toxicity in male rats was investigated in this study. Animals were divided into a control group and the nicotine (1.5 mg/kg/day), FS (25, 50, and 100 mg/kg/day), or/and NFS (20, 40, and 80 mg/kg/day) administered groups. Micronucleus assay, histopathological, and sperm abnormality examinations as well as measurement of the acetylcholinesterase (AChE) gene expression were conducted. Our findings revealed that nicotine treatment induced significant increases in the incidence of micronucleus, sperm abnormalities, and expression levels of AChE in addition to inducing histopathological changes in rat testis. On the other hand, administration of FS or NFS with nicotine significantly decreased the incidence of micronuclei and the percentage of sperm abnormalities as well as the expression levels of AChE gene. Moreover, nicotine-induced histological alterations were reduced by given FS or NFS with nicotine. In conclusion, nicotine-induced sperm abnormalities, chromosomal damage, and histological injuries were mitigated by administration of FS or NFS with nicotine, and thus, FS and NFS could be used as ameliorating agents against nicotine toxicity. Graphical abstract

The role of Musca domestica and milk in transmitting pathogenic multidrug-resistant Escherichia coli and associated phylogroups to neonatal calves - Noha Bakry; Walid Awad; Samia Ahmed; Mohamed Kamel (Environmental Science and Pollution Research, 2022)

Linking electricity demand and economic growth in China: evidence from wavelet analysis - Hamid Mahmood; Jun Wen; Muhammad Zakaria; Samia Khalid (Environmental Science and Pollution Research, 2022)

Atypical anti-NMDA receptor encephalitis associated with varicella zoster virus infection - Nabli Fatma; Saied Zakaria; Zouari Mourad; Belal Samir; Ben Sassi Samia (Journal of NeuroVirology, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Climate Change Influences on the Potential Distribution of the Sand Fly Phlebotomus sergenti, Vector of Leishmania tropica in Morocco - Mohamed Daoudi; Abdelkrim Outammassine; Mounia Amane; Mohamed Hafidi; Samia Boussaa; Ali Boumezzough (Acta Parasitologica, 2022)

Correction to: Does ( −)‑epigallocatechin‑3‑gallate protect the neurotoxicity induced by bisphenol A in vivo? - Manar Mohammed El Tabaa; Samia Salem Sokkar; Ehab Sayed Ramdan; Inas Zakria Abd El Salam; Anis Anis (Environmental Science and Pollution Research, 2022)

Occupational ocular health problems among marble workers at Shaq El Tho’ban industrial area in Egypt - Enjy A. E. Khorshed; Safaa A. El-Naggar; Samia S. El-Gohary; Ahmed M. B. Awad; Amani S. Ahmed (Environmental Science and Pollution Research, 2022)
Eye health of the working population is an essential condition for productivity. Marble industry is processed at large scale at Shaq El Tho’ban area where much dust, crushed pieces of stone, and fluctuating temperatures are endangering employees’ health generally and eye health specifically. The objectives of this study were assessing the prevalence of the most common ocular health problems associated with marble industry and investigating the impact of the working environment and occupational risk factors on the oculo-visual status of marble workers. A cross-sectional study was conducted among 250 workers, working at Shaq El Tho’ban area in Egypt during the period from August 2020 to September 2021, using a semi-structured questionnaire and eye examination comprised of full ocular history, visual acuity testing (unaided/aided), slit lamp examination, ophthalmoscopy, and Schirmer’s type I and tear break up time tests. The current study showed that gritty sensation (65.2%) and eye dryness (51.2%) were the commonest symptoms complained. By examination, conjunctival hyperemia (59.6%) was the most prevalent finding. By performing dry eye tests, dry eye was diagnosed in 60.4% and 51.2% of workers by Schirmer’s test and tear break up time test respectively. The study’s results indicated that age, working category, smoking, and diabetes had significant impact on development of ocular symptoms, while working duration, diabetes, smoking, ocular symptoms, and ocular foreign body had significant impact on development of dry eye disease. Implementation of engineering control measures, proper designing, and supply of eye PPE together with adequate health education to all workers about occupational health risks and preventive measures are recommended.

Does ( −)-epigallocatechin-3-gallate protect the neurotoxicity induced by bisphenol A in vivo? - Manar Mohammed El Tabaa; Samia Salem Sokkar; Ehab Sayed Ramdan; Inas Zakria Abd El Salam; Anis Anis (Environmental Science and Pollution Research, 2022)
Bisphenol A (BPA) is one of the chemicals that is firmly accompanied by hippocampal neuronal injury. As oxidative stress appears to be a major contributor to neurotoxicity induced by BPA, antioxidants with remarkable neuroprotective effects can play a valuable protective role. Around the world, ( −)-epigallocatechin-3-gallate (EGCG) was one of the most popular antioxidants that could exert a beneficial neuroprotective role. Here, we examined the potential efficiency of EGCG against neurotoxicity induced by BPA in the hippocampal CA3 region of the rat model. This study revealed that EGCG was unable to abrogate the significant decrease in circulating adiponectin level and hippocampal superoxide dismutase activity as well as an increase in hippocampal levels of nitric oxide and malondialdehyde. Notably, EGCG failed to antagonize the oxidative inhibitory effect of BPA on hippocampal neurotransmission and its associated cognitive deficits. In addition, the histopathological examination with immunohistochemical detection of caspase-3 and NF-kB/p65 emphasized that EGCG failed to protect hippocampal CA3 neurons from apoptotic and necrotic effects induced by BPA. Our study revealed that EGCG showed no protective role against the neurotoxic effect caused by BPA, which may be attributed to its failure to counteract the BPA-induced oxidative stress in vivo. The controversial effect is probably related to EGCG’s ability to impede BPA glucuronidation and thus, its detoxification. That inference requires further additional experimental and clinical studies. Graphical abstract

Profiling of minerals, water soluble vitamins and carotenoid in selected unconventional leafy and non-leafy vegetables of Bangladesh - Mohammad Khairul Alam; Samia Sams; Mohammad Sharif Khan; Jannatul Azmir; Monira Ahsan; Mohammad Akhtaruzzaman; Sheikh Nazrul Islam (Natural Product Research, 2022)

Microplastics in Sediment of Kuakata Beach, Bangladesh: Occurrence, Spatial Distribution, and Risk Assessment - Partho Banik; M. Belal Hossain; As-Ad Ujjaman Nur; Tasrina Rabia Choudhury; Samia Islam Liba; Jimmy Yu; Md. Abu Noman; Jun Sun (Frontiers in Marine Science, 2022)
Kuakata beach, known as Daughter of Sea in Bangladesh, has drawn a growing number of tourists from all over the world, leading to the higher use of single plastic products. This study was a first attempt to describe the occurrence, spatial distribution, and ecological risk of microplastics (MPs) in Kuakata beach sediments. A total of 24 surface sediment samples were collected from the intertidal zone of the beach, and MPs were extracted using the density separation method and a stereomicroscope. Fourier transform infrared (FTIR) spectroscopy was used for qualitative and quantitative identification. The results revealed that the average MPs in the beach sediment were 232 ± 52 items kg –1 dry weight, which was much higher than many other sandy beaches throughout the world. Analyses of variance showed a significant ( p < 0.01) difference among the mean abundance of MPs in sampling points. Fibers were dominated in every sampling point with an average of 123 ± 27 item kg –1 . Most of the MPs observed were colored (60%), and the rest were transparent (40%). It was found that the size range of 1–5 mm MPs constituted over half (55%) of total MPs covering an average value of 127 ± 34 items kg –1 . Three polymer types were identified in the sediment samples through FTIR analysis which followed the decreasing order of polyethylene terephthalate > polyethylene > polypropylene. Correlation analysis showed a positive relationship between the abundance of MPs and the finer grain size of sediment ( p = 0.055; r = 0.7), indicating grain size-controlled the density of MPs. The pollution load index was assessed to estimate the ecological risk and found that the beach sediment of Kuakata belonged to the risk category I of the pollution index. This investigation provided preliminary information on MPs pollution in the marine ecosystem that the policymakers can use to take appropriate management approaches.

First international workshop of the ATM and cancer risk group (4-5 December 2019) - Fabienne Lesueur; Douglas F. Easton; Anne-Laure Renault; Sean V. Tavtigian; Jonine L. Bernstein; Zsofia Kote-Jarai; Rosalind A. Eeles; Dijana Plaseska-Karanfia; Lidia Feliubadaló; Alejandro Moles-Fernández; Marta Santamariña-Pena; Alysson T. Sánchez; et al. (Familial Cancer, 2022)

Mitochondrial DNA and Alzheimer’s disease: a first case–control study of the Tunisian population - Nesrine Ben Salem; Sami Boussetta; Itziar de Rojas; Sonia Moreno-Grau; Laura Montrreal; Narjes Mokni; Imene Mahmoud; Samia Younes; Nizar Daouassi; Mahbouba Frih-Ayed; Afef Hammami; Amel Ben Ammar Elgaaied; et al. (Molecular Biology Reports, 2022)

Experimental and numerical simulation of free surface flow over an obstacle on a sloped channel - Samia Boudjelal; Ali Fourar; Fawaz Massouh (Modeling Earth Systems and Environment, 2022)

Solvent-free deoxygenation of low-cost fat to produce diesel-like hydrocarbons over Ni–MoS2/Al2O3–TiO2 heterogenized catalyst - Samia A. Hanafi; Mamdouh S. Elmelawy; Hanan A. Ahmed (International Journal of Energy and Water Resources, 2022)

Sustainable use of agro-industrial wastes as potential feedstocks for exopolysaccharide production by selected Halomonas strains - Ichrak Joulak; Patrícia Concórdio-Reis; Cristiana A. V. Torres; Chantal Sevrin; Christian Grandfils; Hamadi Attia; Filomena Freitas; Maria A. M. Reis; Samia Azabou (Environmental Science and Pollution Research, 2022)

Chromatographic methods for the determination of a broad spectrum of UV filters in swimming pool water - Samia Mokh; Rania Nassar; Atika Berry; Mohammad El Khatib; Samah Doumiati; Mariam Taha; Raed Ezzeddine; Mohamad Al Iskandarani (Environmental Science and Pollution Research, 2022)

Strategies to enhance soluble production of heterologous proteins in Escherichia coli - Samia Falak; Muhammad Sajed; Naeem Rashid (Biologia, 2022)

High Prevalence of Toxoplasma gondii in Industrial Tunisian Poultry Meat - Samia Zrelli; Safa Amairia; Moez Mhadhbi; Oussama Briki; Seifeddine Bouallegue; Fatma Souissi; Mohamed Gharbi (Acta Parasitologica, 2022)

Anthropogenic Aquifer Recharge Effect on Groundwater Resources in an Agricultural Floodplain in Northeastern Tunisia: Insights from Geochemical Tracers and Geophysical Methods - Anis Chekirbane; Omeyma Gasmi; Ammar Mlayah; Hakim Gabtni; Samia Khadhar; Fethi Lachaal; Adel Zghibi; Jean-Denis Taupin (Natural Resources Research, 2022)

Groundwater behavior in a hydrologically-modified watershed by a Managed Aquifer Recharge system (Wadi Khairat, NE of Tunisia) - Anis Chekirbane; Samia Khadhar; Fethi Lachaal; Ammar Mlayah (Arabian Journal of Geosciences, 2022)

Prenatal exome sequencing and chromosomal microarray analysis in fetal structural anomalies in a highly consanguineous population reveals a propensity of ciliopathy genes causing multisystem phenotypes - Mohamed H. Al-Hamed; Wesam Kurdi; Rubina Khan; Maha Tulbah; Maha AlNemer; Nada AlSahan; Maisoon AlMugbel; Rafiullah Rafiullah; Mirna Assoum; Dorota Monies; Zeeshan Shah; Zuhair Rahbeeni; et al. (Human Genetics, 2022)

Fiscal policy and environment: a long-run multivariate empirical analysis of ecological footprint in Pakistan - Samia Zahra; Dilawar Khan; Muhammad Nouman (Environmental Science and Pollution Research, 2022)

Effect of foliar application with Chlorella vulgaris, Tetradesmus dimorphus, and Arthrospira platensis as biostimulants for common bean - Dina A. Refaay; Eman M. El-Marzoki; Mohammed I. Abdel-Hamid; Samia A. Haroun (Journal of Applied Phycology, 2021)

Characterization of groundwater hydrogeochemistry, quality, and associated health hazards to the residents of southwestern Bangladesh - Mohammad Mahbub Kabir; Nobin Hossain; Abu Reza Md Towfiqul Islam; Samia Akter; Konica J. Fatema; Lutfun Naher Hilary; Md Hasanuzzaman; Md Didar-ul-Alam; Tasrina Rabia Choudhury (Environmental Science and Pollution Research, 2021)

A novel approach to baseline water quality assessment at local and catchment scale: a case study from Berambadi, India - Anjali V. Raj; Priyanka Jamwal; Anusree K. Anju; Praveen Kumar; Durba Biswas; Lakshminarayana Rao; Rachel Helliwell; Samia Richards; Rowan Ellis; Nazli Koseoglu; Jagadeesh Yeluripati; Stephanie Connelly (Environmental Monitoring and Assessment, 2021)

Epidemiological Studies on Nematode Parasites of Domestic Geese (Anser anser f. domesticus) and First Molecular Identification and Phylogenetic Analysis of Heterakis dispar (Schrank, 1790) in Egypt - Ismail Elshahawy; Mahmoud El-Siefy; Samia Fawy; Eman Mohammed (Acta Parasitologica, 2021)

Evaluation of the displacements of the permanent GPS stations of Beni-Haroun Dam geodetic network (Algeria) - Sofiane Khelifa; Hicham Dekkiche; Salem Kahlouche; Samia Boudina (Acta Geophysica, 2021)

Lawsozaheer, a new chromone produced by an endophytic fungus Paecilomyces variotii isolated from Lawsonia Alba Lam. inhibits the growth of Staphylococcus aureus - Zaheer Abbas; Bina Shaheen Siddiqui; Saleem Shahzad; Samia Sattar; Sabira Begum; Anum Batool; Mohammad Iqbal Choudhary (Natural Product Research, 2021)

Mantle xenolith-bearing phonolites and basanites feed the active volcanic ridge of Mayotte (Comoros archipelago, SW Indian Ocean) - Carole Berthod; Etienne Médard; Andrea Di Muro; Théo Hassen Ali; Lucia Gurioli; Catherine Chauvel; Jean-Christophe Komorowski; Patrick Bachèlery; Aline Peltier; Mhammed Benbakkar; Jean-Luc Devidal; Pascale Besson; et al. (Contributions to Mineralogy and Petrology, 2021)

Relationship between Body and Otolith Morphological Characteristics of Sabre Squirrelfish (Sargocentron spiniferum) from the Southern Red Sea: Difference between Right and Left Otoliths - Yassein A. A. Osman; Kélig Mahé; Samia M. El-Mahdy; Ashraf S. Mohammad; Sahar F. Mehanna (Oceans, 2021)
Otolith morphology analysis is one of the main tools used for fish or fish stock identification. Moreover, otolith shape can also be used in animal dietary studies (stomach content) for the identification of prey fishes and their size according to the relationship between fish and otolith sizes. In the present study, the relationship between fish length and otolith morphological dimensions was investigated for the sabre squirrelfish, Sargocentron spiniferum (Forsskål, 1775) (family: Holocentridae). Samples of 185 fish were collected from the coast of the Red Sea, Egypt. To analyze the relationship between fish and otolith, otolith morphometric measurements (length, width, area, perimeter, weight, sulcus, and ostium) and shape factors (aspect ratio, compactness, form factor, rectangularity, roundness, ellipticity, squareness) describing the outline shape were extracted using image analysis. Generalized linear models were applied for the relationship between body length and each otolith morphology feature. From the relationships between the total length of fish and fourteen morphology features, only otolith length, caudal length, and squareness were significantly correlated with fish size. Our results provide more information for the relationship between fish length and otolith morphometric features.

Bidirectional promoters: an enigmatic genome architecture and their roles in cancers - Sheikh Shafin Ahmad; Nure Sharaf Nower Samia; Auroni Semonti Khan; Rafeed Rahman Turjya; Md. Abdullah-Al-Kamran Khan (Molecular Biology Reports, 2021)

In vitro anti-inflammatory, antioxidant and antibacterial activities of the Algerian species Micropus bombycinus - Samia Dekkiche; Chaima Mouffouk; Soumia Mouffouk; Hamada Haba (Advances in Traditional Medicine, 2021)

Eco-friendly larvicide of Amphora coffeaeformis and Scenedesmus obliquus microalgae extracts against Culex pipiens - Marwa E. Hassan; Samia M. M. Mohafrash; Sahar A. Fallatah; Abo El-Khair B. El-Sayed; Abdel-Tawab H Mossa (Journal of Applied Phycology, 2021)

ACC deaminase containing endophytic bacteria ameliorate salt stress in Pisum sativum through reduced oxidative damage and induction of antioxidative defense systems - Mahmoud R. Sofy; Akram A. Aboseidah; Samia A. Heneidak; Hoda R. Ahmed (Environmental Science and Pollution Research, 2021)

Optimizing different adaptive strategies by using crop growth modeling under IPCC climate change scenarios for sustainable wheat production - Muhammad Rizwan Shahid; Abdul Wakeel; Wajid Ishaque; Samia Ali; Kamran Baksh Soomro; Muhammad Awais (Environment, Development and Sustainability, 2021)

Detoxification gene expression, genotoxicity, and hepatorenal damage induced by subacute exposure to the new pyrethroid, imiprothrin, in rats - Samia M. M. Mohafrash; Entesar E. Hassan; Nahla H. El-shaer; Abdel-Tawab H. Mossa (Environmental Science and Pollution Research, 2021)

Use of GALDIT model and HFE-Diagram to assess seawater intrusion vulnerability in West Nile Delta, Egypt - Zenhom E. Salem; Samia S. Hasan (Arabian Journal of Geosciences, 2021)

Characteristics and outcome according to underlying disease in non-AIDS patients with acute respiratory failure due to Pneumocystis pneumonia - Gaston Burghi; Lucie Biard; Antoine Roux; Sandrine Valade; Florence Robert-Gangneux; Samia Hamane; Daniéle Maubon; Anne Debourgogne; Soléne Le Gal; Fréderic Dalle; Marion Leterrier; Dominique Toubas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Empirical analysis of CO2 emissions and sustainable use of energy sources in Pakistan - Muhammad Khalid Naeem; Sofia Anwar; Samia Nasreen (Environmental Science and Pollution Research, 2021)

Evaluation of antidiabetic activity of Morus nigra L. and Bauhinia variegata L. leaves as Egyptian remedies used for the treatment of diabetes - Salma Hago; Engy A. Mahrous; Mohamed Moawad; Samia Abdel-Wahab; Essam Abdel-Sattar (Natural Product Research, 2021)

Sertraline-Cyclodextrin Complex Orodispersible Sublingual Tablet: Optimization, Stability, and Pharmacokinetics - Dalia M N Abouhussein; Mohamed A El Nabarawi; Samia H Shalaby; Ahmed Abd El-Bary (Journal of Pharmaceutical Innovation, 2021)

COVID-19: Diagnostics, Therapeutic Advances, and Vaccine Development - Sabhiya Majid; Mosin S. Khan; Samia Rashid; Ayesha Niyaz; Rabia Farooq; Showkat A. Bhat; Hilal A. Wani; Waseem Qureshi (Current Clinical Microbiology Reports, 2021)

Histological and Physiological Studies of the Effect of Bone Marrow-Derived Mesenchymal Stem Cells on Bleomycin Induced Lung Fibrosis in Adult Albino Rats - Dina Mohamed Zakaria; Noha Mahmoud Zahran; Samia Abdel Aziz Arafa; Radwa Ali Mehanna; Rehab Ahmed Abdel-Moneim (Tissue Engineering and Regenerative Medicine, 2021)

Rhizoctonia solani affecting micropropagated Garnem (Prunus amygdalus x Prunus persica) rootstock - characterization and biocontrol with Rhizobia - Noura Jemai; Samia Gargouri; Imen Hemissi; Kaouther Ben Mahmoud; Med Fakhri Ksouri; Ahmed Jemmali (Journal of Plant Pathology, 2021)

Contamination of Fishery Products with Mercury, Cadmium, and Lead in Tunisia: Level’s Estimation and Human Health Risk Assessment - Samia Zrelli; Safa Amairia; Mohamed Chaabouni; Walid Oueslati; Olfa Chine; Amira Nachi Mkaouar; Ali Cheikhsbouii; Roua Ghorbel; Malek Zrelli (Biological Trace Element Research, 2021)

Modeling of a Surface Flow Constructed Wetland Using the HEC-RAS and QUAL2K Models: a Comparative Analysis - Linpeng Xiao; Zhi Chen; Fayi Zhou; Samia ben Hammouda; Yinying Zhu (Wetlands, 2020)

Molecular and histopathological characterization of Photobacterium damselae in naturally and experimentally infected Nile tilapia ( Oreochromis niloticus ) - Mai A. M. El‐Son; Samia Elbahnaswy; Iman Ibrahim (Journal of Fish Diseases, 2020)
Mass mortality has occurred among cultured Nile tilapia, Oreochromis niloticus, on fish farms in Manzala, Dakahlia province, Egypt, in the summer season, 2019. Moribund fish were reported with deep ulcers, septicaemic lesions and sampled for bacterial isolation. In this study, most isolates were subjected to bacteriological examination, antibiotic sensitivity test, 16S rRNA gene sequencing and histopathological examination. Following isolate identification, intraperitoneal challenge of Nile tilapia with a bacterial suspension 2 × 10 6 CFU/ml was performed. Samples from liver, spleen and kidney were collected for histological and biochemical analysis. The results showed a high similarity (99%) to Photobacterium damselae strains using phylogenetic analysis of 16S rRNA. P. damselae exhibited resistance to amoxicillin and erythromycin, as well it was highly sensitive to chloramphenicol and doxycycline. Moreover, haemorrhage, oedema, hemosiderosis and melanomacrophage activation in the liver and head kidney of infected fish were detected by light and electron microscopy. Also, significant higher levels of CAT and SOD in the spleen and head kidney, as well as the serum levels of NO were observed in experimentally challenged O. niloticu s, compared to the control fish. Our data identified P. damselae for the first time from infected Nile tilapia, describing its sensitivity to a variety of antibiotics, histopathological alterations and oxidative stress impact, and it could be useful indicators for understanding P. damselae pathogenesis, which might provide a preventive efficacy for P. damselae .

Towards sustainable management of tomato pomace through the recovery of valuable compounds and sequential production of low-cost biosorbent - Samia Azabou; Ibtihel Louati; Fadia Ben Taheur; Moncef Nasri; Tahar Mechichi (Environmental Science and Pollution Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Engineered magnetic nanoparticles enhance chlorophyll content and growth of barley through the induction of photosystem genes - Huseyin Tombuloglu; Yassine Slimani; Guzin Tombuloglu; Thamer Alshammari; Munirah Almessiere; Ayşe Demir Korkmaz; Abdulhadi Baykal; Anna Cristina S. Samia (Environmental Science and Pollution Research, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Antioxidative and immunoprotective potential of Chlorella vulgaris dietary supplementation against chlorpyrifos-induced toxicity in Nile tilapia - Eman Zahran; Samia Elbahnaswy; Engy Risha; Mansour El-Matbouli (Fish Physiology and Biochemistry, 2020)

The future of landslides’ past—a framework for assessing consecutive landsliding systems - Arnaud Temme; Fausto Guzzetti; Jalal Samia; Benjamin B. Mirus (Landslides, 2020)

MUCO-DIS: a New AFM-Based Nanoscale Dissolution Technique - Muhammad Usman Ghori; Jorabar Singh Nirwan; Taimoor Asim; Younes Chahid; Samia Farhaj; Zara Khizer; Peter Timmins; Barbara R. Conway (AAPS PharmSciTech, 2020)
Mucoadhesion-based drug delivery systems have recently gained interest because of their bio-adhesion capability, which results in enhanced residence time leading to prolonged duration of action with the mucosal surface, potentially improving compliance and convenience. Mucoadhesion testing of these formulations is widely reported; however, this is technically challenging due to the absence of any standard methods and difficulty in conducting mucoadhesion, formulation-mucosal surface interaction, mucosal surface topography and drug release in a single experiment. As these measurements are currently conducted separately, on replicate formulations, results can often be subjective and difficult to correlate. Hence, the aim of the present study was to develop a new AFM-based single-entity ex vivo muco-dissolution (MUCO-DIS) technique to simultaneously evaluate mucoadhesion force, 3D surface topography, polymer dissolution and drug release characteristics. To demonstrate the potential of the current technique, the interactions between model pectin microparticles containing metformin HCl and a range of gastrointestinal mucosal surfaces (gastric, small intestine, large intestine and buccal) were studied. This novel system has not only successfully determined the mucoadhesion force, polymer dissolution and drug release information but has also highlighted the difference in microparticle performance with different mucosal targets. The current work has highlighted the potential of this newly developed MUCO-DIS system and we believe this will be a valuable tool for characterising these popular pharmaceutical formulations. This technique could also provide an opportunity to other scientific fields to evaluate materials, substrate behaviour and their interactions in their hydrated state at nanoscale with real-time chemical and surface mapping.

Enhanced anticancer activity of combined treatment of imatinib and dipyridamole in solid Ehrlich carcinoma-bearing mice - Alaa E. El-Sisi; Samia S. Sokar; Hanaa A. Ibrahim; Sally E. Abu-Risha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The impact of DNA demethylation on the upregulation of the NRN1 and TNFAIP3 genes associated with advanced gastric cancer - Fernanda Wisnieski; Leonardo Caires Santos; Danielle Queiroz Calcagno; Jaqueline Cruz Geraldis; Carolina Oliveira Gigek; Ana Carolina Anauate; Elizabeth Suchi Chen; Lucas Trevizani Rasmussen; Spencer Luiz Marques Payão; Ricardo Artigiani; Samia Demachki; Paulo Pimentel Assumpção; et al. (Journal of Molecular Medicine, 2020)

Molecular characterization of multidrug-resistant Gram-negative pathogens in three tertiary hospitals in Cairo, Egypt - Amani A. El-Kholy; Samia A. Girgis; Mervat A. F. Shetta; Dalia H. Abdel-Hamid; Arwa R. Elmanakhly (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
High rates of antimicrobial resistance (AMR) among Gram-negative pathogens (GNP) have been reported in Egypt. Antimicrobial surveillance and identifying the genetic basis of AMR provide important information to optimize patient care. In this study, we aimed to identify the beta-lactam resistance phenotypes and genotypes of multidrug-resistant (MDR) non-repetitive GNP from 3 tertiary hospitals in Egypt. WZe studied 495 non-repetitive MDR Gram-negative isolates from patients with complicated intra-abdominal infections (cIAI), complicated urinary tract infection (cUTI), and lower respiratory tract infection (LRTI), collected as part of the “Study for Monitoring Antimicrobial Resistance Trends” (SMART) conducted in 3 tertiary hospitals in Cairo, Egypt, from 2015 to 2016. Identification and susceptibility testing of GNP to antimicrobials were tested in each hospital laboratory and confirmed in a reference laboratory (International Health Management Associates (IHMA), Inc., Schaumburg, IL, USA). Molecular identification of extended-spectrum beta-lactamases (ESΒLs), AmpC, and carbapenem resistance genes was conducted in IHMA. Among the 495 MDR isolates, Klebsiella pneumoniae ( K . pneumoniae ) and Escherichia coli ( E . coli ) were the most common (52.7% and 44.2%). K . pneumoniae was most susceptible to colistin, amikacin, ertapenem, and imipenem (92.7%, 72.7%, 69.3%, and 64%, respectively). E . coli was most susceptible to colistin (100%), amikacin (94.1%), imipenem (90.4%), and ertapenem (83.6%). ESBL was detected in 96.2% and ESBL genotypes included bla CTX-M-15 (70.1%), bla TEM-OSBL (48.5%), bla SHV-OSBL (27.9%), and bla CTX-M-14 (10.7%). AmpC resistance genes were identified in 9.7% of the isolates, dominated by bla CMY-2 (5.7%) . Carbapenem resistance genes were detected in 45.3% of the isolates. In K . pneumoniae , bla OXA-48 dominated (40.6%), followed by bla NDM-1 (23.7%) and bla OXA-232 (4.5%). In E . coli , the most frequent genes were bla NDM-5 (9.6%), bla OXA-181 (5.5%), bla OXA-244 (3.7%), and bla NDM-1 (3.7%). bla KPC-2 was identified in 0.4% of isolates. Notably, 32.3% of isolates carried more than one resistance gene. Our findings emphasize the continued need for molecular surveillance of MDR pathogens, implementation of strict infection control measures, and antimicrobial stewardship policies in our hospitals.

Study of organic pollution in superficial sediments of Meliane river catchment area: aliphatic and polycyclic aromatic hydrocarbons - Imen Khabouchi; Samia Khadhar; Rim Driouich Chaouachi; Anis Chekirbene; Laurence Asia; Pierre Doumenq (Environmental Monitoring and Assessment, 2020)

Antimicrobial residues survey by LC-MS in food-producing animals in Lebanon - Samia Mokh; Khaled El Hawari; Haifa Abdul Rahim; Mohamad Al Iskandarani; Farouk Jaber (Food Additives & Contaminants Part B-Surveillance, 2020)

Recent advances in biotechnological studies on wild grapevines as valuable resistance sources for smart viticulture - Samia Daldoul; Hatem Boubakri; Mahmoud Gargouri; Ahmed Mliki (Molecular Biology Reports, 2020)

Blood-based gene expression profile of oxidative stress and antioxidant genes for identifying surrogate markers of liver tissue injury in chronic hepatitis C patients - Muhammad Shahid; Muhammad Idrees; Azeem Mehmood Butt; Syed Mohsin Raza; Iram Amin; Afza Rasul; Samia Afzal (Archives of Virology, 2020)

Irradiation as a phytosanitary treatment for controlling, Bactrocera zonata (Saunders) and its impact on different quality attributes of pomegranate fruits - A. Gabarty; A. Hammad; Amira A. K. H. Negm; Samia M. Abd-El Hameed (International Journal of Tropical Insect Science, 2020)

Herbal syrup from chicory and artichoke leaves ameliorate liver damage induced by deltamethrin in weanling male rats - Samia Mostafa Mohamed Mohafrash; Abdel-Tawab Halim Mossa (Environmental Science and Pollution Research, 2020)

Effective removal of Cu(II) from aqueous solution over graphene oxide encapsulated carboxymethylcellulose-alginate hydrogel microspheres: towards real wastewater treatment plants - Dalia Allouss; Younes Essamlali; Achraf Chakir; Samia Khadhar; Mohamed Zahouily (Environmental Science and Pollution Research, 2020)

Seasonal ecotoxicological monitoring of freshwater zooplankton in Bir Mcherga dam (Tunisia) - Sabria Barka; Imene Gdara; Zouhour Ouanes-Ben Othmen; Samia Mouelhi; Monia El Bour; Amel Hamza-Chaffai (Environmental Science and Pollution Research, 2020)

Artificial neural network for modeling formulation and drug permeation of topical patches containing diclofenac sodium - Sonia Lefnaoui; Samia Rebouh; Mounir Bouhedda; M. Madiha Yahoum (Drug Delivery and Translational Research, 2020)

Behavior of Opuntia ficus-indica (L.) Mill. Heat-Stressed Microspores Under In Vitro Culture Conditions as Evidenced by Microscopic Analysis - Badra Bouamama-Gzara; Hassène Zemni; Néjia Zoghlami; Samia Gandoura; Ahmed Mliki; Marianne Arnold; Abdelwahed Ghorbel (In Vitro Cellular & Developmental Biology - Plant, 2020)

Socio-economic, macroeconomic, demographic, and environmental variables as determinants of child mortality in South Asia - Muhammad Zakaria; Samia Tariq; Muhammad Iftikhar ul Husnain (Environmental Science and Pollution Research, 2020)

Auto-immunity profile evaluation during different clinical manifestations of Behçet disease in Algerian patients: effect of corticosteroid treatment - Fatmazohra Djaballah-Ider; Abdelhamid Djaballah; Zineb Djeraba; Samia Chaib; Chafia Touil-Boukoffa (Inflammopharmacology, 2019)

Assessment of groundwater vulnerability for pollution using DRASTIC Index, young alluvial plain, Western Nile Delta, Egypt - Zenhom E. Salem; Ahmed M. Sefelnasr; Samia S. Hasan (Arabian Journal of Geosciences, 2019)

Centaurea microcarpa Coss. & Dur. (Asteraceae) extracts: New cyanogenic glucoside and other constituents - Samia Baatouche; Thamere Cheriet; Djamel Sarri; Ratiba Mekkiou; Ouahiba Boumaza; Samir Benayache; Fadila Benayache; Ignacio Brouard; Francisco León; Ramdane Seghiri (Natural Product Research, 2019)

Physiological behaviors and fruit quality changes in five peach cultivars during three ripening stages in a semi-arid climate - Monia Guizani; Samira Maatallah; Samia Dabbou; Maria Serrano; Hichem Hajlaoui; Ahmed Noureddine Helal; Soumaya Kilani-Jaziri (Acta Physiologiae Plantarum, 2019)

A meta‐analysis of fish behavioural reaction to underwater human presence - Diogo S. M. Samia; Eduardo Bessa; Daniel T. Blumstein; José A. C. C. Nunes; Ernesto Azzurro; Lorenzo Morroni; Valerio Sbragaglia; Fraser A. Januchowski‐Hartley; Benjamin Geffroy (Fish and Fisheries, 2019)
In an increasingly anthropic world, humans have profound impacts on the distribution and behaviour of marine fishes. The increased human presence has modified fishes’ antipredator behavioural responses, and consequently flight decisions, as a function of their changed perceptions of risk. Understanding how fish react to human presence can help identify the most vulnerable functional groups/species and estimate impacts caused by human disturbance. Shoal and body size are known to influence fish flight initiation distance (FID; the distance between the predator and prey when the prey begins to escape); however, few studies attempt to test the moderators of these relationships. Here, we present a comprehensive meta‐analysis evaluating FID of fish in response to human presence. Specifically, we investigated six candidate moderators that could influence the relationship between FID with shoal and body size. Our results showed that individual fish size was strongly and positively correlated with FID and the most important moderator that explained the variance in individual body size‐FID relationship was shoaling behaviour. However, and somehow surprisingly, we detected no significant relationship between shoal size and FID. We discuss how these results can inform the development of fish conservation strategies and ultimately assist in the management of marine protected areas.

First report of Rhizoctonia solani affecting Prunus rootstock ‘Garnem’ - Noura Jemai; Samia Gargouri; Mohamed Fakhri Ksouri; Kaouther Ben Mahmoud; Ahmed Jemmali (Journal of Plant Pathology, 2019)

Synchrotron micro-X-ray fluorescence shows sulfur accumulation in the middle cortex of N2-fixing legume nodules - Camille Rivard; Laurie Amenc; Samia Benlahrech; Bouchra Makoudi; Mustapha Teffahi; Hiram A. Castillo-Michel; Marine Cotte; Benedikt Lassalle-Kaiser; Jean-Jacques Drevon (Protoplasma, 2019)

Nitric oxide signalling and antidepressant action revisited - Samia R. L. Joca; Ariandra G. Sartim; Aline L. Roncalho; Cassiano F.A. Diniz; Gregers Wegener (Cell and Tissue Research, 2019)

Adaptation of hard gelatin capsules for oral delivery of aqueous radiopharmaceuticals - Samia Mohamed Omar; Rania Safaa Abdel-Rashid; Mohamed Kamal AlAssaly; Tamer M. Sakr (DARU Journal of Pharmaceutical Sciences, 2019)

Pesticide residues in Lebanese apples and health risk assessment - Khaled El Hawari; Samia Mokh; Mohamad Al Iskandarani; Wafaa Halloum; Farouk Jaber (Food Additives & Contaminants Part B-Surveillance, 2019)

Efficiency of bacterial biosurfactant for biocontrol of Rhizoctonia solani (AG - 4) causing root rot in faba bean (Vicia faba) plants - Samia Ageeb Akladious; Eman Zakaria Gomaa; Omima Mohammed El-Mahdy (European Journal of Plant Pathology, 2019)

Prevalence and distribution pattern of intestinal helminths in chicken and pigeons in Aswan, Upper Egypt - Khaled Mohamed El-Dakhly; Mahmoud A. El-Seify; Eman Sayed Mohammed; Ismail Saad Elshahawy; Samia Abdel-Motaleb Fawy; Mossab A. Omar (Tropical Animal Health and Production, 2019)

Bone marrow-derived mesenchymal stem cells ameliorate liver injury in a rat model of sepsis by activating Nrf2 signaling - Sally A. Selim; Samia A. Abd El-Baset; Asmaa A. A. Kattaia; Eman M. Askar; Eman Abd Elkader (Histochemistry and Cell Biology, 2019)

Neuro-fuzzy modeling of ibuprofen-sustained release from tablets based on different cellulose derivatives - Samia Rebouh; Sonia Lefnaoui; Mounir Bouhedda; Madiha M. Yahoum; Salah Hanini (Drug Delivery and Translational Research, 2019)

In situ genotoxicity assessment in freshwater zooplankton and sediments from different dams, ponds, and temporary rivers in Tunisia - Zouhour Ouanes-Ben Othmen; Sabria Barka; Zied Ben Adeljelil; Samia Mouelhi; Mounira Krifa; Soumaya Kilani; Leila Chekir-Ghedira; Joëlle Forget-Leray; Amel Hamza-Chaffai (Environmental Science and Pollution Research, 2019)

Bioconversion of Olive Pomace by Submerged Cultivation of Streptomyces sp. S1M3I - Lamia Medouni-Haroune; Farid Zaidi; Sonia Medouni-Adrar; Ourdia Nouara Kernou; Samia Azzouz; Mouloud Kecha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Deadly outbreak of chickenpox at district Faisalabad, Pakistan: possible causes, and preventive way forward - Muhammad Zubair Yousaf; Sadia Zia; Khalid Mahmood Anjum; Usman Ali Ashfaq; Muhammad Imran; Samia Afzal; Muhammad Sarfaraz Iqbal (Molecular Biology Reports, 2018)

Transformation of sulfaquinoxaline by chlorine and UV light in water: kinetics and by-product identification - Rania Nassar; Samia Mokh; Ahmad Rifai; Fatmeh Chamas; Maha Hoteit; Mohamad Al Iskandarani (Environmental Science and Pollution Research, 2018)

Implementing landslide path dependency in landslide susceptibility modelling - Jalal Samia; Arnaud Temme; Arnold K. Bregt; Jakob Wallinga; John Stuiver; Fausto Guzzetti; Francesca Ardizzone; Mauro Rossi (Landslides, 2018)

Biofilm formation and regulation of salicylic acid-inducible genes expression in Arabidopsis by Algerian indigenous bacteria from wheat and potatoes rhizospheres in semi-arid Sétif region - Asma Benslim; Samia Mezaache-Aichour; Nora Haichour; Kamel Aissat; Mohamed Mihoub Zerroug (Archives of Microbiology, 2018)

Erratum to: Biomass HotSpot distribution model and spatial interaction of two exploited species of horse mackerel in the south-central Mediterranean Sea - Giacomo Milisenda; Germana Garofalo; Samia Fezzani; Okbi Rjeibi; Othman Jarboui; Bachra Chemmam; Luca Ceriola; Angelo Bonanno; Simona Genovese; Gualtiero Basilone; Roberta Mifsud; Valentina Lauria; et al. (Hydrobiologia, 2018)

Biomass HotSpot distribution model and spatial interaction of two exploited species of horse mackerel in the south-central Mediterranean Sea - Milisenda Giacomo; Garofalo Germana; Fezzani Samia; Rjeibi Okbi; Jarboui Othman; Chemmam Bachra; Ceriola Luca; Bonanno Angelo; Genovese Simona; Basilone Gualtiero; Mifsud Roberta; Lauria Valentina; et al. (Hydrobiologia, 2018)

The use of otolith shape to determine stock structure of Engraulis encrasicolus along the Tunisian coast - Sana Khemiri; Adel Gaamour; Lotfi Ben Abdallah; Samia Fezzani (Hydrobiologia, 2018)

Solid Form of Lipid-Based Self-Nanoemulsifying Drug Delivery Systems for Minimization of Diacerein Adverse Effects: Development and Bioequivalence Evaluation in Albino Rabbits - Mohamed Ahmed Naseef; Howida Kamal Ibrahim; Samia Abd El-Kader Nour (AAPS PharmSciTech, 2018)

Sediment-water column exchange of persistent organic pollutants (PAHs and PCBs) and their transport vector in El Bey watershed, Tunisia - Samia Khadhar; Dhouha Achour; Anis Chekirben; Rim Chawachi; Ammar Mlayah; Abdelkrim Charef (Arabian Journal of Geosciences, 2018)

Correction to: Preparation and Optimization of Fast-Disintegrating Tablet Containing Naratriptan Hydrochloride Using D-Optimal Mixture Design - Samia M. Omar; Fathy I. AbdAlla; Noha M. Abdelgawad (AAPS PharmSciTech, 2018)

Preparation and Optimization of Fast-Disintegrating Tablet Containing Naratriptan Hydrochloride Using D-Optimal Mixture Design - Samia M. Omar; Fathy I. AbdAlla; Noha M. Abdelgawad (AAPS PharmSciTech, 2018)

Sodium selenite ameliorates both intestinal and extra-intestinal changes in acetic acid-induced colitis in rats - Samar M. Soliman; Walaa Wadie; Samia A. Shouman; Afaf A. Ainshoka (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Influence of corticosteroid therapy on IL-18 and nitric oxide production during Behçet’s disease - Fatmazohra Djaballah-Ider; Zineb Djeraba; Mourad Chemli; Nadjiba Dammene-Debbihe; Doulkifly Lounis; Houda Belguendouz; Yanis Medour; Samia Chaib; Chafia Touil-Boukoffa (Inflammopharmacology, 2018)

Assessing links between energy consumption, freight transport, and economic growth: evidence from dynamic simultaneous equation models - Samia Nasreen; Samir Saidi; Ilhan Ozturk (Environmental Science and Pollution Research, 2018)

Formulation and characterization of garlic (Allium sativum L.) essential oil nanoemulsion and its acaricidal activity on eriophyid olive mites (Acari: Eriophyidae) - Abdel-Tawab H. Mossa; Sahar I. Afia; Samia M. M. Mohafrash; Badawi A. Abou-Awad (Environmental Science and Pollution Research, 2018)

Sporadic endometrial adenocarcinoma with MMR deficiency due to biallelic MSH2 somatic mutations - Bruno Buecher; Antoine De Pauw; Louis Bazire; Claude Houdayer; Alice Fievet; Virginie Moncoutier; Fereshteh Farkhondeh; Samia Melaabi; Dominique Stoppa Lyonnet; Lisa Golmard (Familial Cancer, 2018)

A Grapevine-Inducible Gene Vv-α-gal/SIP Confers Salt and Desiccation Tolerance in Escherichia coli and Tobacco at Germinative Stage - Samia Daldoul; Anis Ben Amar; Mahmoud Gargouri; Hajer Limam; Ahmed Mliki; Thierry Wetzel (Biochemical Genetics, 2018)

Optimized Ciclopirox-Based Eudragit RLPO Nail Lacquer: Effect of Endopeptidase Enzyme as Permeation Enhancer on Transungual Drug Delivery and Efficiency Against Onychomycosis - Abeer Khattab; Samia Shalaby (AAPS PharmSciTech, 2018)

Assessment of organic pollutants (PAH and PCB) in surface water: sediments and shallow groundwater of Grombalia watershed in northeast of Tunisia - Khadhar Samia; Achouri Dhouha; Chekirben Anis; Mlayah Ammar; Azibi Rim; Charef Abdelkrim (Arabian Journal of Geosciences, 2018)

The use of Elliptical Fourier analysis as a tool for Liza aurata stock discrimination in the gulf of Hammamet - Jmil Imen; Marwa Mejri; Samia BEN MOHAMED; Abdellah CHALH; Jean-Pierre QUIGNARD; Monia TRABELSI (Frontiers in Marine Science, 2018)

Role of circulatory microRNAs in the pathogenesis of hepatitis C virus - Iqra Almas; Samia Afzal; Muhammad Idrees; Muhammad Usman Ashraf; Iram Amin; Muhammad Shahid; Khadija Zahid; Sadia Zahid (VirusDisease, 2017)

Quantitative trait loci for resistance to stripe rust of wheat revealed using global field nurseries and opportunities for stacking resistance genes - Firdissa E. Bokore; Richard D. Cuthbert; Ron E. Knox; Harpinder S. Randhawa; Colin W. Hiebert; Ron M. DePauw; Asheesh K. Singh; Arti Singh; Andrew G. Sharpe; Amidou N’Diaye; Curtis J. Pozniak; Curt McCartney; et al. (Theoretical and Applied Genetics, 2017)

Oleuropein and hydroxytyrosol inhibit the N-formyl-methionyl-leucyl-phenylalanine-induced neutrophil degranulation and chemotaxis via AKT, p38, and ERK1/2 MAP-Kinase inhibition - Samia Bedouhene; Farida Moulti-Mati; Pham My-Chan Dang; Jamel El-Benna (Inflammopharmacology, 2017)

Discarded seeds from red pepper (Capsicum annum) processing industry as a sustainable source of high added-value compounds and edible oil - Samia Azabou; Fadia Ben Taheur; Mourad Jridi; Mohamed Bouaziz; Moncef Nasri (Environmental Science and Pollution Research, 2017)

Application of in-plant control measures in some Egyptian micro-scale dairy enterprises and its impact on heavy metal contents of their products - Magda Magdy Abd El-Salam; Mohamed F. Farahat; Gaber I. Abu-Zuid; Samia G. Saad (Environmental Monitoring and Assessment, 2017)

The HIV aspartyl protease inhibitor ritonavir impairs planktonic growth, biofilm formation and proteolytic activity in Trichosporon spp. - Rossana de Aguiar Cordeiro; Rosana Serpa; Patrícia Bruna Leite Mendes; Antonio José de Jesus Evangelista; Ana Raquel Colares Andrade; Jônatas da Silva Franco; Vandbergue dos Santos Pereira; Lucas Pereira de Alencar; Jonathas Sales de Oliveira; Zoilo Pires de Camargo; Reginaldo Gonçalves de Lima Neto; Débora de Souza Collares Maia Castelo-Branco; et al. (Biofouling, 2017)

Design of Isoniazid Smart Nanogel by Gamma Radiation-Induced Template Polymerization for Biomedical Application - Samia M. Omar; Nabila A. Maziad; Nourhan M. El-Tantawy (Pharmaceutical Research, 2017)

Monitoring of 45 pesticides in Lebanese surface water using Polar Organic Chemical Integrative Sampler (POCIS) - Al Ashi Aisha; Wael Hneine; Samia Mokh; Marie-Hélène Devier; Hélèn Budzinski; Farouk Jaber (Ocean Science Journal, 2017)

A Dialogue on Perspectives of Biochar Applications and Its Environmental Risks - Samia Qadeer; Muzammil Anjum; Azeem Khalid; Muhammad Waqas; Aniqa Batool; Tariq Mahmood (Water, Air, & Soil Pollution, 2017)

Molecular factors regulating E-cadherin expression in urothelial bladder cancer and their correlations with the clinicopathological features - Samia Hussein; Hala Mosaad; Hayam E. Rashed; Shimaa Ahmed; Ahmed Ragab; Eman I. Ismail (Molecular Biology Reports, 2017)

Normative biometry of the fetal brain using magnetic resonance imaging - Vanessa Kyriakopoulou; Deniz Vatansever; Alice Davidson; Prachi Patkee; Samia Elkommos; Andrew Chew; Miriam Martinez-Biarge; Bibbi Hagberg; Mellisa Damodaram; Joanna Allsop; Matt Fox; Joseph V. Hajnal; et al. (Brain Structure and Function, 2017)

Influence of temperature and storage conditions on the hatching behavior of cereal cyst nematodes (Heterodera avenae Wollenweber) from Egypt - Mohamed Baklawa; Björn Niere; Samia Massoud (Journal of Plant Diseases and Protection, 2017)

No correlation between MTHFR c.677 C > T, MTHFR c.1298 A > C, and ABCB1 c.3435 C > T polymorphisms and methotrexate therapeutic outcome of rheumatoid arthritis in West Algerian population - Wefa Boughrara; Ahmed Benzaoui; Meriem Aberkane; Fatima Zohra Moghtit; Samia Dorgham; Aicha sarah Lardjam-Hetraf; Hadjer Ouhaibi-Djellouli; Elisabeth Petit Teixeira; Abdallah Boudjema (Inflammation Research, 2017)

HCV-induced regulatory alterations of IL-1β, IL-6, TNF-α, and IFN-ϒ operative, leading liver en-route to non-alcoholic steatohepatitis - Rabia Nawaz; Sadia Zahid; Muhammad Idrees; Shazia Rafique; Muhammad Shahid; Ammara Ahad; Iram Amin; Iqra Almas; Samia Afzal (Inflammation Research, 2017)

Genetic associations with lipoprotein subfraction measures differ by ethnicity in the multi-ethnic study of atherosclerosis (MESA) - Zhe Wang; Ani Manichukal; David C. Goff; Samia Mora; Jose M. Ordovas; Nicholas M. Pajewski; Wendy S. Post; Jerome I. Rotter; Michele M. Sale; Stephanie A. Santorico; David Siscovick; Michael Y. Tsai; et al. (Human Genetics, 2017)

Experimental Study of Tunis Soft Soil Improved by Deep Mixing Column - Wissem Frikha; Habib Zargayouna; Samia Boussetta; Mounir Bouassida (Geotechnical and Geological Engineering, 2017)

One-pot synthesis of lightly doped Zn1−x Cu x O and Au–Zn1−x Cu x O with solar light photocatalytic activity in liquid phase - Anis Fkiri; Marisa Rico Santacruz; Amine Mezni; Leila-Samia Smiri; Valérie Keller; Nicolas Keller (Environmental Science and Pollution Research, 2017)

Spatio-temporal assessment and trend analysis of surface water salinity in the coastal region of Bangladesh - Mashura Shammi; Md. Mostafizur Rahman; Md. Atikul Islam; Md. Bodrud-Doza; Anwar Zahid; Yeasmin Akter; Samia Quaiyum; Masaaki Kurasaki (Environmental Science and Pollution Research, 2017)

Molecular Diagnostic and Prognostic Subtyping of Gliomas in Tunisian Population - Saoussen Trabelsi; Imen Chabchoub; Iadh Ksira; Nadhir Karmeni; Nadia Mama; Samia Kanoun; Anna Burford; Alexa Jury; Alan Mackay; Sergey Popov; Noureddine Bouaouina; Slim Ben Ahmed; et al. (Molecular Neurobiology, 2017)

Regulatory network analysis of microRNAs and genes in imatinib-resistant chronic myeloid leukemia - Ismael Soltani; Hanen Gharbi; Islem Ben Hassine; Ghada Bouguerra; Kais Douzi; Mouheb Teber; Salem Abbes; Samia Menif (Functional & Integrative Genomics, 2017)

Development and validation of a multiclass method for the determination of antibiotic residues in honey using liquid chromatography-tandem mass spectrometry - Khaled El Hawari; Samia Mokh; Samah Doumyati; Mohamad Al Iskandarani; Eric Verdon (Food Additives & Contaminants: Part A, 2017)

Do landslides follow landslides? Insights in path dependency from a multi-temporal landslide inventory - Jalal Samia; Arnaud Temme; Arnold Bregt; Jakob Wallinga; Fausto Guzzetti; Francesca Ardizzone; Mauro Rossi (Landslides, 2017)

Lactational exposure to abamectin induced mortality and adverse biochemical and histopathological effects in suckling pups - Abdel-Tawab H. Mossa; Mona A. Abdel Rasoul; Samia M. M. Mohafrash (Environmental Science and Pollution Research, 2017)

Downstream flow and upstream movement determine the value of a stream reach for potadromous fish populations - Yasmine Samia; Frithjof Lutscher (Theoretical Ecology, 2017)

Efficacy of some rhizospheric and endophytic bacteria in vitro and as seed coating for the control of Fusarium culmorum infecting durum wheat in Tunisia - Nourhen Mnasri; Cynda Chennaoui; Samia Gargouri; Ridha Mhamdi; Kamel Hessini; Salem Elkahoui; Naceur Djébali (European Journal of Plant Pathology, 2017)

Th9 cells in the pathogenesis of EAE and multiple sclerosis - Wassim Elyaman; Samia J. Khoury (Seminars in Immunopathology, 2017)

Breast Cancer Knowledge Among Male High School Students in Saudi Arabia - Samia Al-Amoudi; Moaiad Tariq Abdul-Aziz AlHomied; Nasser Youssef Nasser AlSayegh; Osama Naseem Ismail Radi; Mohammed Majed Suliman Zagzoog; Omar Faisal Mubarak Aloufi; Abdullah Abdulkarim Ali Al-Harbi; Safwan Tayeb; Mohammed Hassanien; Mahmoud Al-Ahwal; Basem Eldeek; Steve Harakeh (Journal of Cancer Education, 2016)

Assessment of observed behavior of soil reinforced by rigid inclusions - Samia Boussetta; Mounir Bouassida; Mondher Zouabi (Innovative Infrastructure Solutions, 2016)
The numerical behavior of rafted foundation resting on soil reinforced by rigid inclusions is undertaken. Axisymmetric modeling of scaled test model investigated primarily in the framework of ASIRI research project is investigated by the FE code Plaxis V9.2D. The predictions of settlement and efficiency of the reinforced soil are compared to measurements obtained from tests carried out in the calibration chamber. A parametric study was conducted and allowed to observe the effect of the thickness and the constitutive material of mattress layer, the cover rate and type of compressible soil on the efficiency of the reinforcement by rigid inclusion. Main findings were: the best efficiency is obtained for minimum thickness of mattress layer. The increase in cover rate leads to an increased maximum efficiency and settlement reduction.

Megalencephalic leukoencephalopathy with cysts in twelve Egyptian patients: novel mutations in MLC1 and HEPACAM and a founder effect - Ghada M. H. Abdel-Salam; Mohamed S. Abdel-Hamid; Samira I. Ismail; Heba Hosny; Tarek Omar; Laila Effat; Mona S. Aglan; Samia A. Temtamy; Maha S. Zaki (Metabolic Brain Disease, 2016)

Profile of expression of certain markers of apoptosis in chronic hepatitis C and hepatitis B patients in an Egyptian population - Mahmoud El-Bendary; Samia Hawas; Dina El-Hammady; Al-Hadidy Mohammed Al-Hadidy; Heba Eldegla (Archives of Virology, 2016)

Lycopene ameliorates atrazine-induced oxidative damage in adrenal cortex of male rats by activation of the Nrf2/HO-1 pathway - Marwa Ahmed Abass; Shereen Ahmed Elkhateeb; Samia Adel Abd EL-Baset; Asmaa Alhosiny Kattaia; Eman Mosallam Mohamed; Hebatallah Husseini Atteia (Environmental Science and Pollution Research, 2016)

Characterization of Leptospiral Chemoreceptors Using a Microscopic Agar Drop Assay - Samia Affroze; Md. Shafiqul Islam; Kyosuke Takabe; Seishi Kudo; Shuichi Nakamura (Current Microbiology, 2016)

Guillain–Barre syndrome following oral polio vaccination - Salman Naeem; Asma Shabbir; Abdus Salam Khan; Samia Ahmad; Khawaja Junaid Mustafa; Ammad Fahim (Journal of NeuroVirology, 2016)

Geospatial susceptibility mapping of earthquake-induced landslides in Nuweiba area, Gulf of Aqaba, Egypt - Sara Abuzied; Samia Ibrahim; Mona Kaiser; Tarek Saleem (Journal of Mountain Science, 2016)

Evidence of hormesis on human neuronal SK-N-BE cells treated with sodium arsenate: impact at the mitochondrial level - Wafa Kharroubi; Samia Haj Ahmed; Thomas Nury; Pierre Andreoletti; Zohra Haouas; Amira Zarrouk; Rachid Sakly; Mohamed Hammami; Gérard Lizard (Environmental Science and Pollution Research, 2016)

Biosynthesis of single-cell biomass from olive mill wastewater by newly isolated yeasts - Fatma Arous; Samia Azabou; Atef Jaouani; Hela Zouari-Mechichi; Moncef Nasri; Tahar Mechichi (Environmental Science and Pollution Research, 2016)

Effect of long-term irrigation with treated wastewater of three soil types on their bulk densities, chemical properties and PAHs content in semi-arid climate - Rim Azouzi; Abdelkrim Charef; Safa zaghdoudi; Samia Khadhar; Nouha Shabou; Hichem Boughanmi; Bilel Hjiri; Slaheddine Hajjaj (Arabian Journal of Geosciences, 2016)

Dorzolamide synergizes the antitumor activity of mitomycin C against Ehrlich’s carcinoma grown in mice: role of thioredoxin-interacting protein - Belal M. Ali; Sawsan A. Zaitone; Samia A. Shouman; Yasser M. Moustafa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Giant reed for selenium phytoremediation under changing climate - Hassan R. El-Ramady; Neama Abdalla; Tarek Alshaal; Ahmed S. Elhenawy; Mohamed S. Shams; Salah E.-D. A. Faizy; El-Sayed B. Belal; Said A. Shehata; Mohamed I. Ragab; Megahed M. Amer; Miklós Fári; Attila Sztrik; et al. (Environmental Chemistry Letters, 2015)

Erratum to: Distribution, morphological and histochemical characteristics of foliar trichomes of Plectranthus zuluensis (Lamiaceae) - Benita Kalicharan; Yougasphree Naidoo; Samia Heneidak; Arvind Bhatt (Brazilian Journal of Botany, 2015)

Distribution, morphological and histochemical characteristics of foliar trichomes of Plectranthus zuluensis (Lamiaceae) - Benita Kalicharan; Yougasphree Naidoo; Samia Heneidak; Arvind Bhatt (Brazilian Journal of Botany, 2015)

Determination of Some Non-sedating Antihistamines via Their Native Fluorescence and Derivation of Some Quantitative Fluorescence Intensity - Structure Relationships - Michael E. El-Kommos; Samia M. El-Gizawy; Noha N. Atia; Noha M. Hosny (Journal of Fluorescence, 2015)

Performance of concrete containing crushed brick aggregate exposed to different fire temperatures - Samia Hachemi; Abdelhafid Ounis (European Journal of Environmental and Civil Engineering, 2015)

Chemopreventive and therapeutic potentials of thymoquinone in HepG2 cells: mechanistic perspectives - Abeer ElKhoely; Hafez F. Hafez; Abeer M. Ashmawy; Osama Badary; Ahmed Abdelaziz; Adel Mostafa; Samia A. Shouman (Journal of Natural Medicines, 2015)

Effects of climate on the productivity of desert truffles beneath hyper-arid conditions - Lyès Bradai; Samia Bissati; Haroun Chenchouni; Khaled Amrani (International Journal of Biometeorology, 2015)

Phenolic content, antioxidant and anti-inflammatory activities of Tunisian Diplotaxis simplex (Brassicaceae) - Samia Oueslati; Ahlem Ellili; Jean Legault; Andre Pichette; Riadh Ksouri; Mokhtar Lachaal; Najoua Karray-Bouraoui (Natural Product Research, 2015)

Chemical composition, phytotoxic and antifungal properties of Ruta chalepensis L. essential oils - Wafa Bouabidi; Mohsen Hanana; Samia Gargouri; Ismail Amri; Tarek Fezzani; Mustapha Ksontini; Bassem Jamoussi; Lamia Hamrouni (Natural Product Research, 2015)

Development of a new technique to detect living cells of Xanthomonas campestris pv. campestris in crucifers seeds: the seed-qPCR - Samia Laala; Zouaoui Bouznad; Charles Manceau (European Journal of Plant Pathology, 2015)

Effects of Superparamagnetic Iron Oxide Nanoparticles on Photosynthesis and Growth of the Aquatic Plant Lemna gibba - Lotfi Barhoumi; Abdallah Oukarroum; Lotfi Ben Taher; Leila Samia Smiri; Hafedh Abdelmelek; David Dewez (Archives of Environmental Contamination and Toxicology, 2015)

Selenium in soils under climate change, implication for human health - Hassan El-Ramady; Neama Abdalla; Tarek Alshaal; Éva Domokos-Szabolcsy; Nevien Elhawat; Jόszef Prokisch; Attila Sztrik; Miklós Fári; Samia El-Marsafawy; Mohamed S. Shams (Environmental Chemistry Letters, 2015)

Géométrie de l’aquifère du Haouz oriental et Tassaout amont, Maroc occidental: approche géophysique et hydrogéologique - Samia Rochdane; Abdennabi El Mandour; Mohammed Jaffal; Mahjoub Himi; Albert Casas; Mostafa Amrhar; Morad Karroum (Hydrological Sciences Journal, 2015)

Morphological and phylogenetic diversity of thermophilic cyanobacteria in Algerian hot springs - Samia Amarouche-Yala; Ali Benouadah; Abd El Ouahab Bentabet; Purificación López-García (Extremophiles, 2014)

Industrial fire simulation and uncertainty associated with the Emission Dispersion Model - Samia Chettouh; Rachida Hamzi; Fares Innal; Djamel Haddad (Clean Technologies and Environmental Policy, 2014)

Titanium oxide nanoparticle effects on composition of soil microbial communities and plant performance - David J. Burke; Shun Zhu; Michele P. Pablico-Lansigan; Charlotte R. Hewins; Anna Cristina S. Samia (Biology and Fertility of Soils, 2014)

A new flavonol glycoside from the medicinal halophyte Suaeda fruticosa - Samia Oueslati; Riadh Ksouri; André Pichette; Serge Lavoie; Karl Girard-Lalancette; Vakhtang Mshvildadze; Chedly Abdelly; Jean Legault (Natural Product Research, 2014)

Erratum to: Biosynthesis of phenolic compounds in Vitis vinifera cell suspension cultures: Study on Hydroxycinnamoyl CoA: ligase - Samia Lotfy; Annie Fleuriet; Teresa Ramos; Jean-Jacques Macheix (Plant Cell Reports, 2014)

Colour constancy in insects - Lars Chittka; Samia Faruq; Peter Skorupski; Annette Werner (Journal of Comparative Physiology A, 2014)

Influence of thiourea application on some physiological and molecular criteria of sunflower (Helianthus annuus L.) plants under conditions of heat stress - Samia Ageeb Akladious (Protoplasma, 2014)

Synthesis and Characterization of New Light Emitter Symmetrical Phenoxazinium Salt and Its Potential Application as Sensor for Assessment of Hg2+ - M. S. Attia; A. O. Youssef; Abdel-Sattar S. H. Elgazwy; Samia A. El Abady; Samia M. Agami; Safaa I. Elewa (Journal of Fluorescence, 2014)

Rosavirus: the prototype of a proposed new genus of the Picornaviridae family - Tung Gia Phan; Nguyen Phung Vo; Peter Simmonds; Erik Samayoa; Samia Naccache; Charles Y. Chiu; Eric Delwart (Virus Genes, 2013)

Vecteur de la pollution metallique du bassin versant de l’Oued El Bey vers le Golfe de Tunis (Tunisie) - Samia Khadhar; Ammar Mlayah; Anis Chekirben; Abdelkrim Charef; Malika Methammam; Shabou Nouha; Zayanani Khemais (Hydrological Sciences Journal, 2013)

The effect of long-term soil irrigation by wastewater on organic matter, polycyclic aromatic hydrocarbons, and heavy metals evolution: case study of Zaouit Sousse (Tunisia) - Khadhar Samia; Charef Abdelkarim; Hidri Yassin; Higashi Teruo (Arabian Journal of Geosciences, 2013)

Chemical composition of Eucalyptus erythrocorys essential oils and evaluation of their herbicidal and antifungal activities - Asma Ben Ghnaya; Mohsen Hanana; Ismail Amri; Hazar Balti; Samia Gargouri; Bassem Jamoussi; Lamia Hamrouni (Journal of Pest Science, 2013)

The prevalence and prognostic significance of KRAS mutation in bladder cancer, chronic myeloid leukemia and colorectal cancer - Slah Ouerhani; Karim Bougatef; Ismail Soltani; Amel Ben Ammar Elgaaied; Salem Abbes; Samia Menif (Molecular Biology Reports, 2013)

Foliar secretory trichomes of Ocimum obovatum (Lamiaceae): micromorphological structure and histochemistry - Yougasphree Naidoo; Nazeera Kasim; Samia Heneidak; Ashley Nicholas; Gonasageran Naidoo (Plant Systematics and Evolution, 2013)

Effet auto-épurateur de la lithologie des affleurements géologiques dans un climat semi-aride: cas du bassin versant de l'Oued Mellègue (Nord-Ouest de la Tunisie) - Ammar Mlayah; Eduardo Anselmo Ferreira Da Silva; Fethi Lachaal; Samia Khadhar; Abdelkrim Charef; Fernando Noronha (Hydrological Sciences Journal, 2013)

Determination of the aquifers geometry in arid zones by using geoelectrical method - Samia Hadj-Said; Aziz Zeddouri; Larbi Djabri; Belhadj Hamdi-Aissa (Arabian Journal of Geosciences, 2013)

Plasma and Urine Dimercaptopropanesulfonate Concentrations after Dermal Application of Transdermal DMPS (TD-DMPS) - Jennifer P. Cohen; Anne-Michelle Ruha; Steven C. Curry; Kallol Biswas; Benjamin Westenberger; Wei Ye; Kathleen L. Caldwell; Frank LoVecchio; Keith Burkhart; Nasr Samia (Journal of Medical Toxicology, 2013)

Mycobacterium avium subspecies paratuberculosis: an insidious problem for the ruminant industry - Mohamed Salem; Carsten Heydel; Amr El-Sayed; Samia A. Ahmed; Michael Zschöck; George Baljer (Tropical Animal Health and Production, 2013)

Antigens of Coccidioides posadasii as an Important Tool for the Immunodiagnosis of Coccidioidomycosis - Rossana de Aguiar Cordeiro; Kharla Rabelo Nobre Patoilo; Silviane Bandeira Praciano; Delia Jessica Astete Medrano; Francisca Jakelyne de Farias Marques; Liline Maria Soares Martins; Kelsen Dantas Eulalio; Antônio de Deus Filho; Maria do Amparo Salmito Cavalvanti; Maria Auxiliadora Bezerra Fechine; Raimunda Samia Nogueira Brilhante; Zoilo Pires de Camargo; et al. (Mycopathologia, 2013)

Genetic polymorphisms of NQO1, CYP1A1 and TPMT and susceptibility to acute lymphoblastic leukemia in a Tunisian population - Slah Ouerhani; Nouha Cherif; Ikbel Bahri; Ines Safra; Samia Menif; Salem Abbes (Molecular Biology Reports, 2013)

IFNγ expression by an attenuated strain of Salmonella enterica serovar Typhimurium improves vaccine efficacy in susceptible TLR4-defective C3H/HeJ mice - Samia M. Al-Ojali; C. B. Tara Moore; Maria J. Fernandez-Cabezudo; Basel K. al-Ramadi (Medical Microbiology and Immunology, 2013)

Molecular identification of a novel inulinolytic fungus isolated from and grown on tubers of Helianthus tuberosus and statistical screening of medium components - Samia Abd Allah AbdAl-Aziz; Mohammad Magdy El-Metwally; Wesam Eldin Ismail Ali Saber (World Journal of Microbiology and Biotechnology, 2012)

Neocryptolepine analogues containing N-substituted side-chains at C-11: synthesis and antischistosomicidal activity - Ibrahim El Sayed; Fatem Ramzy; Samia William; Mohamed El Bahanasawy; Mostafa M. Abd El-Sattar (Medicinal Chemistry Research, 2012)

Glandular trichomes of Ceratotheca triloba (Pedaliaceae): morphology, histochemistry and ultrastructure - Yougasphree Naidoo; Taariq Karim; Samia Heneidak; Channangihalli Thimmegowda Sadashiva; Gonasageran Naidoo (Planta, 2012)

Chemical composition and biological activities of volatile fractions from three Tunisian cultivars of olive leaves - Faten Brahmi; Guido Flamini; Manel Issaoui; Madiha Dhibi; Samia Dabbou; Maha Mastouri; Mohamed Hammami (Medicinal Chemistry Research, 2012)

Promising antitumor effect of alpha-tocopheryl succinate in human colon and liver cancer cells - Amal A. Abd-El Fattah; Hebatallah A. Darwish; Nevine Fathy; Amira Raafat; Samia A. Shouman (Medicinal Chemistry Research, 2012)

Experimental Model of Arthritis Induced by Paracoccidioides brasiliensis in Rats - Eduardo Alexandre Loth; Samia Khalil Biazin; Claudete Rodrigues Paula; Rita de Cássia Garcia Simão; Marcello Fabiano de Franco; Rosana Puccia; Rinaldo Ferreira Gandra (Mycopathologia, 2012)

Synthesis, anticancer, anti-HIV-1, and antimicrobial activity of some tricyclic triazino and triazolo[4,3-e]purine derivatives - Fawzia A. Ashour; Samia M. Rida; Soad A. M. El-Hawash; Mona M. ElSemary; Mona H. Badr (Medicinal Chemistry Research, 2012)

Changes in phenolic composition and antioxidant activities of the edible halophyte Crithmum maritimum L. with physiological stage and extraction method - Ines Jallali; Wided Megdiche; Baya M’Hamdi; Samia Oueslati; Abderrazek Smaoui; Chedly Abdelly; Riadh Ksouri (Acta Physiologiae Plantarum, 2012)

Chemical composition, phytotoxic and antifungal activities of Pinus pinea essential oil - Ismail Amri; Samia Gargouri; Lamia Hamrouni; Mohsen Hanana; Tarek Fezzani; Bassem Jamoussi (Journal of Pest Science, 2012)

Extraction, characterization, and nematicidal activity of chitin and chitosan derived from shrimp shell wastes - Mohamed A. Radwan; Samia A. A. Farrag; Mahmoud M. Abu-Elamayem; Nabila S. Ahmed (Biology and Fertility of Soils, 2012)

Short-term response of wild grapevines (Vitis vinifera L. ssp. sylvestris) to NaCl salinity exposure: changes of some physiological and molecular characteristics - Hend Askri; Samia Daldoul; Anis Ben Ammar; Saloua Rejeb; Rahma Jardak; Mohamed Nejib Rejeb; Ahmed Mliki; Abdelwahed Ghorbel (Acta Physiologiae Plantarum, 2012)

Molecular cloning and characterisation of a cDNA encoding a putative alkaline alpha-galactosidase from grapevine (Vitis vinifera L.) that is differentially expressed under osmotic stress - Samia Daldoul; Imen Toumi; Götz M. Reustle; Gabi Krczal; Abdelwahed Ghorbel; Ahmed Mliki; Michael U. Höfer (Acta Physiologiae Plantarum, 2012)

Molecular cloning and characterisation of a cDNA encoding a putative alkaline alpha-galactosidase from grapevine (Vitis vinifera L.) that is differentially expressed under osmotic stress - Samia Daldoul; Imen Toumi; Götz M. Reustle; Gabi Krczal; Abdelwahed Ghorbel; Ahmed Mliki; Michael U. Höfer (Acta Physiologiae Plantarum, 2012)

The leaf secretory scales of Combretum molle (Combretaceae): morphology, ultrastructure and histochemistry - Yougasphree Naidoo; Samia Heneidak; Sanjay Gairola; Ashley Nicholas; Gonasageran Naidoo (Plant Systematics and Evolution, 2012)

Testicular oxidative damage and role of combined antioxidant supplementation in experimental diabetic rats - Magda Mohasseb; Samia Ebied; Mona A. H. Yehia; Neveen Hussein (Journal of Physiology and Biochemistry, 2011)

HvFT1 (VrnH3) drives latitudinal adaptation in Spanish barleys - Ana M. Casas; Abderrahmane Djemel; Francisco J. Ciudad; Samia Yahiaoui; Luis J. Ponce; Bruno Contreras-Moreira; M. Pilar Gracia; José M. Lasa; Ernesto Igartua (Theoretical and Applied Genetics, 2011)

Evaluating the Knowledge of Breast Cancer Screening and Prevention among Arab-American Women in Michigan - Samia Arshad; Karen Patricia Williams; Athur Mabiso; Subhojit Dey; Amr S. Soliman (Journal of Cancer Education, 2011)

Chemical composition and antimicrobial activity of extracts from Gliocladium sp. growing wild in Tunisia - Kaouthar Liouane; Dhouha Saïdana; Hayet Edziri; Samia Ammar; Jihane Chriaa; Mohamed Ali Mahjoub; Khaled Said; Zine Mighri (Medicinal Chemistry Research, 2010)

Flexible and stretchable micro-electrodes for in vitro and in vivo neural interfaces - Stéphanie P. Lacour; Samia Benmerah; Edward Tarte; James FitzGerald; Jordi Serra; Stephen McMahon; James Fawcett; Oliver Graudejus; Zhe Yu; Barclay Morrison (Medical & Biological Engineering & Computing, 2010)

Comparing native and irradiated E. coli lactose repressor-operator complex by molecular dynamics simulation - Samia Aci-Sèche; Norbert Garnier; Stéphane Goffinont; Daniel Genest; Mélanie Spotheim-Maurizot; Monique Genest (European Biophysics Journal, 2010)

Anti-inflammatory and antioxidant activities of some extracts and pure natural products isolated from Rhus tripartitum (Ucria) - Mohamed Ali Mahjoub; Samia Ammar; Hayet Edziri; Nabila Mighri; Abderrahman Bouraoui; Zine Mighri (Medicinal Chemistry Research, 2010)

Proteomic and Transcriptomic Analysis of Grapevine PR10 Expression During Salt Stress and Functional Characterization in Yeast - Neila Jellouli; Hatem Ben Jouira; Samia Daldoul; Synda Chenennaoui; Abdelwahed Ghorbel; Asma Ben Salem; Ali Gargouri (Plant Molecular Biology Reporter, 2010)

Physiological and antioxidant responses of Mentha pulegium (Pennyroyal) to salt stress - Samia Oueslati; Najoua Karray-Bouraoui; Houneïda Attia; Mokded Rabhi; Riadh Ksouri; Mokhtar Lachaal (Acta Physiologiae Plantarum, 2010)

Preparation and Evaluation of Microemulsion Systems Containing Salicylic Acid - Alia A. Badawi; Samia A. Nour; Wedad S. Sakran; Shereen Mohamed Sameh El-Mancy (AAPS PharmSciTech, 2009)

Chromium Chloride Administration Causes a Substantial Reduction of Coronary Lipid Deposits, Aortic Lipid Deposits, and Serum Cholesterol Concentration in Rabbits - David A. Price Evans; Mohammad Tariq; Rofaida Dafterdar; Hussa Al Hussaini; Samia H. Sobki (Biological Trace Element Research, 2009)

Antibacterial, antioxidant and cytotoxic activities of extracts of Conyza canadensis (L.) Cronquist growing in Tunisia - Edziri Hayet; Mastouri Maha; Ammar Samia; Mahjoub Mohamed Ali; Brahim Souhir; Kenani Abderaouf; Zine Mighri; Aouni Mahjoub (Medicinal Chemistry Research, 2009)

Improvement of an RNA purification method for grapevine (Vitis vinifera L.) suitable for cDNA library construction - Samia Daldoul; Synda Chenenanoui; Ahmed Mliki; Michael Höfer (Acta Physiologiae Plantarum, 2009)

Profiles of volatile compounds from nine new hybrids obtained by controlled crossings on olive Chemlali cultivar and Mediterranean varieties - Imed Rjiba; Samia Debbou; Nouredine Gazzah; Imed Chreif; Mohamed Hammami (Natural Product Research, 2009)

In Planta Transformation of Tomato - Abida Yasmeen; Bushra Mirza; Samia Inayatullah; Naila Safdar; Maryam Jamil; Shawkat Ali; M. Fayyaz Choudhry (Plant Molecular Biology Reporter, 2009)

Antimicrobial, antioxidant, and antiviral activities of Retama raetam (Forssk.) Webb flowers growing in Tunisia - Edziri Hayet; Mastouri Maha; Ammar Samia; Matieu Mata; Patrich Gros; Hiar Raida; Mahjoub Mohamed Ali; Ali Si Mohamed; Laurent Gutmann; Zine Mighri; Aouni Mahjoub (World Journal of Microbiology and Biotechnology, 2008)

Response of sugar beet to some mechanical management practices, irrigation and plant densities - S. Samia El-Maghraby; M. A. Gomaa; I. F. Rehab; Hala. M. S. Hassan (Sugar Tech, 2008)

Expanding the chemical diversity of CK2 inhibitors - Renaud Prudent; Virginie Moucadel; Miriam López-Ramos; Samia Aci; Beatrice Laudet; Liliane Mouawad; Caroline Barette; Jacques Einhorn; Cathy Einhorn; Jean-Noel Denis; Gilles Bisson; Frédéric Schmidt; et al. (Molecular and Cellular Biochemistry, 2008)

Antimicrobial and antioxidant activities of methanol extracts of Evax pygmaea (Asteraceae) growing wild in Tunisia - Olfa Boussaada; Jihène Chriaa; Rym Nabli; Samia Ammar; Dhouha Saidana; Mohamed Ali Mahjoub; Imed Chraeif; Ahmed Noureddine Helal; Zine Mighri (World Journal of Microbiology and Biotechnology, 2008)

Mutagenic, antimutagenic and antioxidant activities of a new polyphenolic and a flavonoid substances isolated from Anagallis monelli - Samia Ammar; Mohamed Ali Mahjoub; Houda Ben Abdelkader; Kaouther Liouane; Ines Skandarani; Leila Chekir-ghedira; Zine Mighri (Natural Product Research, 2008)

Paired values of serum fructosamine and blood glucose for the screening of gestational diabetes mellitus: A retrospective study of 165 Saudi pregnant women - Haseeb Ahmad Khan; Samia Hasan Sobki; Abdullah Saleh Alhomida; Shaukat Ali Khan (Indian Journal of Clinical Biochemistry, 2007)

Larval rearing of calico scallops, Argopecten gibbus, in a flow-through system - Samia Sarkis; Michael Helm; Claudia Hohn (Aquaculture International, 2006)

Antimicrobial and antioxidant activities of the methanolic extracts of three Salvia species from Tunisia - Karima Bel Hadj Salah; Mohamed Ali Mahjoub; Samia Ammar; Laura Michel; Joelle Millet-Clerc; Jean Pierre Chaumont; Zine Mighri; Mahjoub Aouni (Natural Product Research, 2006)

New insight in staphylococcin research: bacteriocin and/or bacteriocin-like inhibitory substance(s) produced by S. aureus AB188 - Sadia Saeed; Sheikh Ajaz Rasool; Samia Ahmed; Tanweer Khanum; Muhammad Bashir Khan; Atiya Abbasi; Syed Abid Ali (World Journal of Microbiology and Biotechnology, 2006)

Kinase Cak1 functionally interacts with the PAF1 complex and phosphatase Ssu72 via kinases Ctk1 and Bur1 - Carine Ganem; Chaouki Miled; Céline Facca; Jean-Gabriel Valay; Gilles Labesse; Samia Ben Hassine; Carl Mann; Gérard Faye (Molecular Genetics and Genomics, 2006)

Expression of a deregulated tobacco nitrate reductase gene in potato increases biomass production and decreases nitrate concentration in all organs - Samia Djennane; Isabelle Quiller; Marie-Thrse Leydecker; Christian Meyer; Jean-Eric Chauvin (Planta, 2004)

Genetic Variability and Population Structure of the Wheat Foot Rot Fungus, Fusarium culmorum, in Tunisia - Samia Gargouri; Louis Bernier; Mohamed Rabeh Hajlaoui; Mohamed Marrakchi (European Journal of Plant Pathology, 2003)

Cryopreservation of sour orange (Citrus aurantium L.) shoot tips - Samia S. Al-Ababneh; Nabila S. Karam; Rida A. Shibli (In Vitro Cellular & Developmental Biology - Plant, 2002)

Introduction and Expression of a Deregulated Tobacco Nitrate Reductase Gene in Potato Lead to Highly Reduced Nitrate Levels in Transgenic Tubers - Samia Djennane; Jean-Eric Chauvin; Isabelle Quilleré; Christian Meyer; Yves Chupeau (Transgenic Research, 2002)

Synthesis and evaluation of N-acetylneuraminic acid-based affinity matrices for the purification of sialic acid-recognizing proteins - Silvana Ciccotosto; Milton J Kiefel; Samia Abo; Wendy Stewart; Kaylene Quelch; Mark von Itzstein (Glycoconjugate Journal, 1998)

Enzymatic properties of lipase and characteristics production byLactobacillus delbrueckii subsp.bulgaricus - M. M. A. El-Sawah; A. A. Sherief; Samia M. Bayoumy (Antonie van Leeuwenhoek, 1995)